Bridging the domain gap: A transferable dynamic routing enhancer for robust aerial detection under adverse weather - Yu Wan; Jie Li; Liupeng Lin; Zhaowen Lv; Zaiyan Zhang; Qiangqiang Yuan; Huanfeng Shen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Primary biliary cirrhosis and rheumatoid arthritis: a comprehensive study combining genetics and transcriptomics - Mingyi Yang; Honghao Ren; Xiaodong Ren; Pengfei Wen; Jiale Xie; Xianjie Wan; Ke Xu; Lin Liu; Weikun Hou; Zhi Yang; Peng Xu (Mammalian Genome, 2026)

MEK inhibitor cobimetinib increases calreticulin and induces immune modulation in TNBC - Ling-Ming Tseng; Ka-Yi Lau; Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Wan-Lun Wang; Yuan-Ya Chang; Jiun-I Lai; Chi-Cheng Huang; Ming-Shen Dai; Chun-Yu Liu (Journal of Molecular Medicine, 2026)
Immunogenic cell death (ICD) can activate immune cells and potentiate the response to immunotherapy. The mitogen-activated protein kinase (MAPK) signaling pathway regulates the immune response and mediates T-cell receptor signaling. Activation of the MAPK signaling pathway decreases the levels of tumor-infiltrating lymphocytes in triple-negative breast cancer (TNBC) and is associated with worse survival. Here, we investigated the potential of the MEK inhibitor cobimetinib as an ICD inducer in TNBC. We demonstrated that cobimetinib elicited hallmarks of ICD, including elevated levels of damage-associated molecular patterns. Ectopic ERK expression attenuated cobimetinib-induced CRT. Cobimetinib also evoked caspase-8 activation with increased Bax and Bak expression, while caspase inhibitor suppressed cobimetinib-induced CRT expression and apoptosis. In immunocompetent (BALB/c) mice bearing 4T1 tumors, cobimetinib exhibited stronger tumor growth inhibition than in immunodeficient (nude) mice, suggesting an immune-dependent antitumor effect. Furthermore, cobimetinib treatment increased the proportions of naïve CD8 + T cells and effector CD4 + T cells and decreases the proportion of myeloid-derived suppressor cells in immunocompetent mice bearing 4T1 tumors. Notably, we observed differential immunomodulatory effects of cobimetinib in tumor-bearing mice compared to non–tumor-bearing immunocompetent mice. Our findings indicate that MEK inhibition is associated with ICD-related molecular alterations, and that cobimetinib may contribute to immune modulation in TNBC.

Dihydrolipoamide dehydrogenase promotes hepatocellular carcinoma progression and modulates cuproptosis-dependent cell death - Mao-feng Zhong; Yu-yu Guo; Yuan Tian; Tian-xiao Zheng; Lu-yuan Zhu; Juan Du; Wan-fu Lin (Functional & Integrative Genomics, 2026)

Multi-omics integration and machine learning define an iron-sulfur cluster/zinc-binding protein prognostic signature in esophageal squamous cell carcinoma - Wenhuan Chen; Tongtong Chen; Zhixuan Li; Wan Lin; Zefeng Xie; Hansheng Wu; Liyan Xu; Enmin Li; Hefeng Zhang; Yinwei Cheng (Mammalian Genome, 2026)

Second-order memristor-coupled heterogeneous neuron model: multi-attractor, multi-stability, and hardware implementation - Miao Xie; Hairong Lin; Qiuzhen Wan; Fei Yu; Wei Yao (Cognitive Neurodynamics, 2026)

Synchronous Paleo-Tethys closure in northern Iran: Constraints from Paleozoic-Mesozoic sediments in the western Alborz - Yiyang Lei; Yang Chu; Mark B. Allen; Wei Lin; Bo Wan; Ling Chen; Morteza Talebian; Guangyao Xin; Tanjie Liu; Yilin Guo; Lin Guo; Ranran Xia (Journal of Asian Earth Sciences, 2026)

Evolution rule of pore structure and molecular structure in the process of coal adsorbing inert gas - Fei Gao; Zhe Jia; Wan Lin; Jidan Zhang; Xinyu Chang (Fuel, 2026)

Defining optimal elevation thresholds for mangrove restoration through dynamic tidal simulation: Evidence from morphological and physiological assessment of five species in Zhanjiang Bay, China - Jianjian Huang; Bing Yang; Xin Zhou; Jie Chen; Suqing Liu; Kangyi Deng; Xiuxuan Lin; Yiting Chen; Ruixuan Wang; Yuzhong Zheng; Qinghan Wu; Hui Zhu; et al. (Ecological Engineering, 2026)

Polarization phenomena in vacuum membrane distillation for high-concentration ionic liquids separation: Experimental and theoretical investigation - Huanhuan Wu; Jiaxuan Yao; Xiaoyue Wang; Yi Yin; Hong Yao; Yinhua Wan; Fei Shen; Yakai Lin (Desalination, 2026)

Water Management Controls Thiacloprid Degradation in Soil via Iron Redox Cycling with Biochar-Supported Zero-Valent Iron - Lin Pan; Shuai Qu; Longfei Liu; Wan Yang; Muhammad Mahroz Hussain; Shengsen Wang (Water, Air, & Soil Pollution, 2026)

Size matching between laccase and carrier via tunable diamine-derived flexible spacer arms for enhanced phenolic wastewater degradation - Jie Zhang; Yiqi Gong; Zhipeng Qin; Xinyi Liu; Jiao Yu; Tao Feng; Wan Zhang; Wenjing Lin; Kaiyue Kang; Xuemei Tan; Lin Zhuo; Ruiqi Wang; et al. (Journal of Water Process Engineering, 2026)

Multifunctional CaO-enabled persulfate activation for pentachlorophenol degradation in contaminated soil: Calcium-mediated transformation and oxidative enhancement - Dawei Lan; Ping Liu; Fengjiao Zhang; Jiang Lin; Ying Ran; Wan Cheng; Jing Chen; Xiaohui Wu; Anxu Sheng; Linling Wang (Journal of Environmental Chemical Engineering, 2026)

Causality-preserving short-term cooling-load forecasting with online correction for building cooling systems - Dongdong Li; Yizhe Wang; Yunwei Shen; Can Wan; Shunfu Lin; Bo Zhou (International Journal of Refrigeration, 2026)

Process-dependent structural and functional modification of yeast protein: Alkaline extraction-acid precipitation versus high-pressure homogenization-assisted pH shifting - Lin Li; Xiaoyu Ma; Dan Huang; Ming Du; Shuo Wan; Shuzhen Cheng (Food Chemistry, 2026)

Characterization of soybean proteins with various 7S/11S globulin ratios plus machine learning analysis for associating their corresponding physical and chemical functionalities - Yilai Wan; Xinyu Guo; Zhen Liu; Yanhong Lin; Guandi Chen; Yong Zhan; Shengwei Hu; Bing Wang; Chris Blanchard; Zhongkai Zhou; Guohua Zhao (Food Chemistry, 2026)

Multilayer packaging with CO2/O2-selective gas regulation and humidity-responsive release of cinnamon essential oil for cherry tomato preservation - Lin Peng; Jinyu Wang; Lijing Lin; Azadeh Nilghaz; Xueyan Yun; Xiaofang Wan; Shaokai Zhang; Junfei Tian (Food Chemistry, 2026)

Flood-driven nutrient influx and phytoplankton succession in the subtropical waters of the Matsu Archipelago, Taiwan - Supriyadi; Yun-Chi Lin; Wan-Lin Chen; Kuo-Shu Chen; Gwo-Ching Gong; Sheng-Fang Tsai (Continental Shelf Research, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Molecular mechanisms of neutron irradiation damage in CL-20: A multiscale modeling approach from collision cascades to real-space defect mapping - Wei-Yi Li; Tao Wang; Rong Liu; Yu-Heng Li; Wan-Xiao Guo; Xi-Yao Yun; Yi-Lin Fang; Jin-Tao Wang; Ning Gao (Chemical Engineering Journal, 2026)

CRISPR/Cas12a dual-gRNA assay enables precise detection of single-nucleotide mutations via cis-staggered-cleavage - Zhiyun Lin; Yanchi Luo; Hong Li; Baokai Shao; Xiufen Yang; Jianing Wang; Yi Wan; Fengge Song (Analytica Chimica Acta, 2026)

Lithological and structural controls on surface deformation in the mudstone-rich fold-thrust belt of Southwestern Taiwan: Insights from numerical modeling - Wan-Lin Hu; Eh Tan (Tectonophysics, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Multi-level optimized displacement field reconstruction in icebreaker structures using inverse finite element method - Sen Wan; Meng Zhang; Lin Ren; Zhaochun Zhang; Donghui Wang; Ding Chen; Xiaohui Zhang; Haibo Hu; Nan Li (Ocean Engineering, 2026)

S-methoprene affected the population growth of Ephestia elutella (Hübner) - Lin-chong An; Xiao-fei Yu; Si-qi Wan; Mao-fa Yang (Journal of Stored Products Research, 2026)

Recent progress on hydrogen production via catalytic Auto-thermal methane Reforming: A focus on catalysts and operational parameters - Jun Wan; Peng Liu; Feiyi Zhou; Huajie Lyu; Teng Hu; Keyu Cheng; Yihong Song; Jiabiao Zou; Xiao Zhang; Saisai Lin; Chenghang Zheng; Xiang Gao (Fuel, 2026)

Interfacial and emulsifying properties of low-denatured soy protein prepared by self-coacervation - Shumin Zhang; Jiyang Cai; Zhuojia Lin; Chang Yang; Zhihong Lyu; Menghui Wang; Wentao Qian; Zhili Wan; Hongliang Li; Xiaoquan Yang (Food Hydrocolloids, 2026)

Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Wave-adaptive floating platform for hybrid triboelectric-electromagnetic energy harvesting toward marine IoT systems - Shilin Wu; Lingyu Wan; Erming Su; Gaojian Wei; Wei Tang; Siyan Pan; Jiaqi Han; Zhong Lin Wang; Leo N.Y. Cao (Chemical Engineering Journal, 2026)

Combined exposure to hypoxia and 17α-ethinylestradiol alters reproductive traits in marine medaka - Xian Qin; Jiezhang Mo; Huiju Lin; Yi Yang; Emily Sze Wan Wong; Min Pan; Sidney Man Ngai Chan; Rudolf Shiu Sun Wu; William Ka Fai Tse; Keng Po Lai (Aquatic Toxicology, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

THBS2: the key hub linking breast cancer stroma, immunity, and therapeutic response - Xi Wan; Xinchen Zhao; Yao Lin; Shujie Yang; Han Dai; Yi Li; Xiaoshan Wang (Clinical & Experimental Metastasis, 2026)

Long-Term Fermented Chicken Manure (CM) Amendment Enhances Soil Health, Sugar Beet Yield, and Shifts Microbial Functional Diversity - Jianyu Zhang; Songlin Yang; Xiaochen Lin; Shafaque Sehar; Muhammad Ishfaq; Muhammad Riaz; Muhammad Faheem Adil; Saqib Bilal; Xiaoyu Zhao; Jean Wan Hong Yong; Baiquan Song (Sugar Tech, 2026)

Diosmetin alleviates retinal ischemia-reperfusion injury through SIRT1-mediated suppression of oxidative stress, inflammation, and PANoptosis - Peng Fu; Xiaobo Wan; Chunrong Zheng; Xiaonian Wu; Ke Xu; Qiuyu Lin; Minli Huang (Immunologic Research, 2026)

Nanomaterials as plant delivery carriers: transport mechanisms and design principles - Ye Li; Yezhuo Zhang; Zhun Zhang; Xi Zhang; Hongyang Wu; Man Zhang; Zhuo Li; Yinglang Wan; Yujie Fu; Wei Dong; Ruili Li; Jinxing Lin (Science China Life Sciences, 2026)

FBG-based dynamic characterization of a scaled offshore wind turbine foundation model under impact and recorded seismic excitations - Jui-Chi Lin; Yi-Lun Liao; Bor-Yann Chen; I-Hsin Chiu; Wan-Yu Xu; You-Chen Liao; Yi-Heng Yang; Yu-Hsi Huang (Ocean Engineering, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Fe/N Co-doped sludge-derived biochar enables rapid Maduramicin adsorption via coupled hydrophobic partitioning and Fe–N complexation - Xinying Li; Huilin Wan; Zhifu Tian; Min Ji; Siyuan Zhai; Qinghua Ouyang; Na Lin; Yingxin Zhao (Journal of Environmental Chemical Engineering, 2026)

Dazomet fumigation with black film mulching improves soil microecology, reduces the abundance of antibiotic resistance genes, and increases yield of Panax notoginseng - Yameng Lin; Xiufu Wan; Minghua Li; Tao Meng; Guili Xie; Yuan Liu; Qian Yang; Xiuming Cui; Wenping Zhang; Ye yang (Journal of Environmental Management, 2026)

Recovery time patterns of vegetation productivity following anomalies preceding abrupt declines - Maohong Wei; Hailing Li; Xuhao Wan; Lin Zhu; Weiqing Meng; Jianfeng Feng (Journal of Environmental Management, 2026)

BmFOXP1 and BmSGF1 divergently cooperate with BmGATAβ4 to regulate vitellogenin expression during vitellogenesis of the silkworm, Bombyx mori - Na Wan; Hongling Liu; Yanan Wu; An Wang; Yingying Mao; Jiayi Liu; Lei Xin; Yong Hou; Ying Lin; Qingyou Xia (Insect Biochemistry and Molecular Biology, 2026)

Single-walled carbon Nanotube-Encapsulated polyoxometalates for Wide-Range humidity PEM fuel cells - Chenyu Liu; Qinghao Lin; Jujia Zhang; Qin Liu; Xianglong Wan; Wentuan Bi (Fuel, 2026)

An improved LC–MS/MS method for simultaneous determination of deoxynivalenol and its modified forms in grains and feed - Dongying Tian; Gang Lin; Ronghua Zhu; Alexandros Yiannikouris; Yuping Wan; Zhaoqin Wang; Yang Yu; Peilon Wang; Ruiguo Wang (Food Chemistry, 2026)

Multi-omics integrated analysis provides insights into developmental mechanisms, metabolic variations and key component biosynthesis in the rare medicinal fungus Gerronema lapidescens - Zhiyuan Jia; Xiaolei Wan; Yuying Liu; Chao Lin; Ming Zhang; Xiaolong He; Haiqiang Wang; Can Du; Minglei Li; Jianzhao Qi (Food Bioscience, 2026)

The Use of Double-tube Multiplex TaqMan Real-time RT-PCR for the Simultaneous Detection of Foodborne Viruses in Shellfish - Peng Lin; Ling Chen; Qiang Wan; Zhihe Cai; Liang Xue; Qinghua Ye; Fufeng Jiang; Xiaoying Qu; Jiahui Huang; Huishu Huang; Yu Ding; Moutong Chen; et al. (Food Control, 2026)

Design, preparation and performance study of DAP-1 based conductive energetic composite - Wan-Jun Wei; Rui Pu; Yu-Ruizhi Lin; Ying-Qi Mao; Qi-Long Yan; Shao-Li Chen (Chemical Engineering Journal, 2026)

Integrated electrochemistry enables deep decontamination and resource recovery of rare earth wastewater - Kaibo Hu; Luyu Mei; Chao Wang; Hong Liu; Jiuyang Lin; Yinhua Wan; Xuewei Li (Chemical Engineering Journal, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Plant–soil feedback persists beyond host death to shape density-dependent plant competition - Ching-Lin Huang; Joe Wan; Shuo Wei; Chia-Hao Chang-Yang; Po-Ju Ke (Plant and Soil, 2026)

Portable Upper-limb Muscle Tone Assessment by Integrating Multi-sensor Signals - Yue Zhang; Ying Zheng; Hao ShangGuan; Ting Chen; Wan-Zhu Wang; Ya-Lan Wang; Peiqiang Lin; Bingwei He; Wenyao Hong; Xin-Yuan Chen (Annals of Biomedical Engineering, 2026)

Efficient removal of atrazine by phosphorylated nano zero-valent iron activated persulfate process: Performance, reaction mechanism and degradation pathway - Jun Lin; Menghua Cao; Guohong Qiu; Hengliang Huang; Tianying Wan; Shuxin Tu; Shuanglian Xiong; Mingming Zheng (Process Safety and Environmental Protection, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Revealing the impact of low-temperature fermentation by Weissella cibaria MXJSHZ8-3 on soymilk quality through volatile flavor compounds and metabolite profiles - Yanhong Lin; Guandi Chen; Zhen Liu; Yilai Wan; Jingru Zhang; Hexi Yuan; Shiyang Yu; Yang Jiang; Ming Ning; Peng Yu; Zhongkai Zhou (Food Chemistry, 2026)

Sn-2 palmitate ameliorates dyslipidemia in high-fat-fed aged mice via bile acid-mediated gut-liver-adipose cross-talk - Lin Zhu; Mingzhe Deng; Hong Zhang; Zhenbo Xu; Peijin Tong; Jianchun Wan; Boyan Gao; Liangli (Lucy) Yu; Yaqiong Zhang (Food Bioscience, 2026)

Resource-efficient numerical computing and elastic wave behavior analysis in complex poroelastic media - Zhitao Zhang; Yuhang Guo; Zhuwen Wang; Baozhi Pan; Yibo Wang; Lin Gan; Wubing Wan; Zhaoqi Sun; Wenqiang Wang; Ruiyi Han; Jiaxu Guo; Yitong Cui (Computers and Geotechnics, 2026)

Ultrastable Pt clusters confined on CeO2 nano-islands for efficient low-temperature propane dehydrogenation over carbon nanotube - Jian Tao; Shu-Lin Liu; Zi-Dan Li; Wan-Yi Wang; Chuan-Feng Huang; Bao-Lian Su; Zhao Wang (Chemical Engineering Journal, 2026)

Tailoring charge redistribution to suppress lattice oxygen release in Ni-rich single–crystal cathodes - Qianqian Jiang; Zhencheng Huang; Xi Chen; Tao Huang; Jingguo Gao; Yingqi Xu; Jinqi Dong; Wei Zeng; Haoran Wei; Feifan Wan; Lin Chen; Bin Liao; et al. (Chemical Engineering Journal, 2026)

Laser-induced hybrid interphase for corrosion dispersion toward durable metal–polymer interfaces in marine environment - Shuangshuang Li; Man Gu; Hailang Wan; Jianping Lin (Chemical Engineering Journal, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Efficient Underwater Image Super-Resolution via Learnable Color Conversion and Dual-Branch Mamba Network - Yu-Yang Lin; Wan-Jen Huang; Chia-Hung Yeh; Yi-Shiuan Yang; Chua-Chin Wang (Journal of Marine Science and Engineering, 2026)
Underwater image super-resolution plays an important role in marine exploration, as it aims to recover clearer and higher-resolution images from degraded low-resolution observations. However, in underwater environments, this task is particularly challenging due to non-uniform spectral attenuation and particle scattering. Underwater, red light fades quickly, leading to color distortion and loss of details. To address this while keeping the model lightweight, we propose a dynamic color-space network for single-image super-resolution. Traditional methods use fixed color conversion and cannot handle non-uniform attenuation well. We instead use a learnable module to adaptively obtain luminance (Y) and chrominance (CbCr) representations. Building upon this representation, we employ a highly efficient dual-branch architecture where the Y-channel features are processed using light Mamba blocks to capture spatial dependencies with linear complexity, while the CbCr-channel features are restored by a lightweight convolutional neural network. Finally, a lightweight residual model utilizing depth-wise separable convolutions (DSC), deformable convolutions, and pixel attention mechanisms is introduced to refine the features and suppress artifacts. Experimental results demonstrate that while achieving competitive restoration quality, the proposed method drastically reduces computational complexity and parameter count compared to other large-scale models. This balance between visual quality and computational efficiency makes the proposed method well-suited for real-time deployment on resource-constrained autonomous underwater vehicles (AUVs).

Tinosporoside E and tinosporane A: two new clerodane diterpenes from the tuberous roots of Paratinospora sagittata - Li Fan; Yu-Jie Zhang; Shi-Peng Zhang; Wan-Shu Li; Ling-Juan Zhu; Hang-Juan Lin (Natural Product Research, 2026)

Seismic dynamic response and sensitivity analysis of high-speed railway catenary systems under multidirectional excitations and traveling wave effects - Jin Chen; Qing-Bing Wan; Hao-Lin Xin; Bo Fu; Deliang Ma (Bulletin of Earthquake Engineering, 2026)

Sulfur-autotrophic treatment of Sb(V)-contaminated water across concentration levels: Toward effective antimony pollution control - Yahui Shi; Zhixiang Zhang; Heyu Wan; Lin Ma; Heng Chen; Ying Li; Jiahui Dai; Dongjin Wan (Process Safety and Environmental Protection, 2026)

Eremophilane-type sesquiterpenes from Ligularia hodgsonii: isolation, structural characterization, and pro-angiogenic potential - Zhenhua Wan; Huilin Peng; Chunping Tang; Jiangjiang Qin; Bintao Hu; Changqiang Ke; Sheng Yao; Ligen Lin; Yang Ye (Phytochemistry, 2026)

Multi-sensor fusion for autonomous vertical docking in kilometer-scale deep-sea environments - Suohang Zhang; Lin Yu; Shipang Qian; Jiaxuan Song; Ziyang Wan; Ruiheng Liu; Lu Wang; Xinyu Fei; Canjun Yang; Yanhu Chen (Ocean Engineering, 2026)

Mechanically engineered multi-oxide heterojunctions for bifunctional antibacterial and photocatalytic environmental remediation - Juan Pei; Jialan Mi; Shuhan Yao; Mingxing Guo; Ye Zhang; Xiaoling Wan; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Haichun Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

Manure and sewage dominate nitrate sources in runoff from key headwaters area in China - Xin Chen; Guoce Xu; Zhanbin Li; Shun Wan; Yang Lin; Bin Wang; Mingzhu Xu; Kang Fang; Yanming Qi (Journal of Cleaner Production, 2026)

Revealing performance and environmental thresholds of mangrove nature-based solutions: A nonlinear blue carbon response framework from coastal Hainan - Kaiyue Wang; Penghua Qiu; Dezhi Wang; Xinqing Zou; Meihuijuan Jiang; Tingting Si; Zhihang Wang; Yi Lin; Yanli Yang; Siang Wan; Yang Li (Journal of Environmental Management, 2026)

Selective enrichment of rare earth ions from high-magnesium/calcium leaching solutions via extraction-precipitation - Meng Zhang; Xuewei Li; Jiuyang Lin; Yinhua Wan; Weijie Song (Journal of Environmental Chemical Engineering, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

A power-law relationship between bulk modulus and permeability in fractured sandstone: Insights from tidal analysis - Xu-Lin Tang; Xiao-Wei Jiang; Zhe-Ming Shi; Zhi-Yu Qi; De-Qiang Mao; Xu-Sheng Wang; Yan Zhang; Li Wan; Hong-Bin Yan (Engineering Geology, 2026)

Secondary interfacial polymerization seals defects to repurpose water treatment thin film composites membranes for CO2 capture - YiKai Wang; Zixue Zhao; Long Shi; Tianyi Zhou; Haohan Wan; Gang Zhang; Chuanrong Liu; Wenju Jiang; Lin Yang; Lu Yao; Junfeng Zheng; Zhongde Dai; et al. (Chemical Engineering Journal, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Diversity of arbuscular mycorrhizal fungi of Taiwan cypress along altitude in tropical forests - Wan-Rou Lin; Hsuan-Min Cheng; Ren-Cheng Liu; Tzu-Chao Lin; Lei-Chen Lin; Pi-Han Wang (Tropical Ecology, 2026)

ZDHHC14-driven RUNX2 S-palmitoylation attenuates ferroptosis and enhances chemoresistance in ovarian cancer via the YAP1/GLS1 axis - Tao Li; Bin Lv; Hai Lin; Hong Zhang; Yingchun Wan (Apoptosis, 2026)

L-arginine enhances skeletal muscle energy metabolism and maintains mitochondrial homeostasis to promote locomotor function in zebrafish embryos - Qiu-Yan Chen; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2026)

Facile and inherently safer synthesis of double-base propellants: Correlating microstructural homogeneity with combustion behavior - Chuanxiang Guo; Weihan Wan; Le Wang; Yitao Liu; Yuhang Bao; Yuqi Huang; Zucheng Wu; Xiangyang Lin (Process Safety and Environmental Protection, 2026)

Late Quaternary occurrences of Zoophycos in a high sedimentation rate setting on the continental margin off southwestern Taiwan: Implications for trace maker ecology - Ludvig Löwemark; Radha Krishna Pillutla; Andrew Tien-Shun Lin; Jen-Chu Yeh; Gueorgui Ratzov; Nathalie Babonneau; Shu-Kun Hsu; Chih-Chieh Su; Serge Lallemand; Wan-Ling Tseng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A hybrid ligament configuration design for metal foam flow fields boosts water management in proton exchange membrane fuel cells - Shiqi You; Yixiong Lin; Yun Sun; Qinglian Wang; Zhongmin Wan; Wang Yin; Ting Qiu; Chen Yang (Fuel, 2026)

Phylogeny, species diversity and divergence time of Diaporthe causing leaf blight on Acer palmatum in China - Yu Wan; De-Wei Li; Qiu-Yue Zhang; Yuan-Zhi Si; Jian-Wei Sun; Xiaolei Ding; Lin Huang; Li-Hua Zhu (Fungal Biology, 2026)

Structural and functional characterization of pectic polysaccharide fractions isolated from Choerospondias axillaris flesh - Qian Li; Rui Kang; Hongyi Lin; Yuanhang Wan; Taotao Dai; Panting Tian; Huashan Ling; David Julian McClements; Peiyi Shen; Jun Chen (Food Chemistry, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Preserving the functional integrity of BiP1 is essential for rice storage protein export from the endoplasmic reticulum - Wenkun Yang; Tian Pan; Fan Wang; Yun Zhu; Kunneng Zhou; Binglei Zhang; Gexing Wan; Yu Chen; Yu Zhang; Xiejun Sun; Cailin Lei; Jie Wang; et al. (Plant Science, 2026)

Cryoprotective effect of water extractable arabinoxylan on different molecular weights of wheat glutenins - Han Tao; Ya-Ni Li; Hai-Yuan Zhou; Shan Li; Wan-Hao Cai; Hui-Li Wang; Dong-Lin Su (Food Hydrocolloids, 2026)

Assessing organic substitution thresholds in smallholder farms: Results from a 34-year experiment on crop—livestock integration systems - Yu Ning; Shuai-lin Li; Xin-hui Zhang; Zhu-qing Xia; Yun Gao; Lu Sun; Qiang Ma; Wan-tai Yu (European Journal of Agronomy, 2026)

Thin film nanocomposite membrane incorporated with sulfonic acid-based HOFs for efficient reverse osmosis desalination - Yu-ting Liu; Zi-yue Tang; Zi-ao Zong; Wan-zhen Wang; Xiao-yin Zhang; Xin-ping Song; Xiang-min Meng; Rijia Lin; Jingwei Hou (Desalination, 2026)

Co-solvent-modulated polyamide nanofiltration membranes for high-temperature separation - Wan-Long Li; Xiao-Wei Luo; Wan-Ting Lin; Si-Yuan Zhang; Zi-Lu Zhang; Zi-Jun Zhang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2026)

Landslide susceptibility assessment based on Bayesian optimization and geographical similarity - Jiayu Yan; Shengwu Qin; Wendi Rao; Chaobiao Zhang; Jiangfeng Lv; Zhijun Lin; Feng Wan; Jiasheng Cao (Natural Hazards, 2026)

METTL14 mitigates osteoporosis progression by promoting osteogenic differentiation of BMMSCs through improving mitochondrial dysfunction - Biao-Lin Wan; Zi-Hua Chen; Hong-Sheng Zeng (Journal of Molecular Histology, 2026)

Seismic-induced dynamic response and instability characteristics of high mountain slopes in the Yarlung Tsangpo Grand Canyon, Tibetan Plateau, China - Mengchen Wang; Jiawei Wan; Bin Li; Yang Gao; Wenpei Wang; Haowen Li; Hewei Li; Qixing Lin; Jiangshan Li (Bulletin of Engineering Geology and the Environment, 2026)

Spatio-temporal variation of air quality and environment-economy-urban driving factors: a case study of Hohhot, Inner Mongolia during 2015–2023 - Chuanxi Yang; Shuotong Feng; Xiaoning Wang; Lingxia Chen; Ziheng Wan; Qianqian Guo; Yue Yin; Yanan Luan; Huxiang Lin; Weihua Zhao; Guofu Huang (Air Quality, Atmosphere & Health, 2026)

Hyphosphere metabolic reprogramming in lipids and aromatic amino acids drives differential mycorrhizal growth promotion in trifoliate orange - Hao-Ran Jiang; Wan-Lin Fu; Ci Deng; Ying-Ning Zou; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Colletotrichum species associated with anthracnose of Camellia oleifera in Jiangxi Province, China - Weigang Kuang; Wenna Gao; Liangpeng Wan; Yimei Li; Yachun Lin; Xugen Shi; Lianhu Zhang; Ruqiang Cui (Physiological and Molecular Plant Pathology, 2026)

High-value poly(3-hydroxybutyrate-co-3-hydroxyvalerate) from kitchen waste via mixed anaerobic-aerobic consortia: fermentation performance, metabolic networks, and carbon footprint - Tao Wan; Shengwang Luo; Lin Zhou; Qin Cai; Ruoqi Zhang; Leizhen Zhao; Qi Zhang; Xiao-Ming Ji (Journal of Water Process Engineering, 2026)

Boron-doped secondary shell coordination architectures in iron single-atom catalysts boosts peroxymonosulfate activation and high-valent iron-oxo species formation for superior aquatic micropollutant purification - Junli Zheng; Shanhong Lan; Junjie Hu; Junjun Ma; Yajie Wu; Ceng Zeng; Hao Luo; Jinquan Wan; Qintie Lin; Junlong Xie (Journal of Environmental Sciences, 2026)

Pea proteins prepared by self-coacervation: Physicochemical characterization and emulsifying properties - Zhuojia Lin; Jialing Chen; Zixi Liu; Xiang Li; Zhili Wan; Xiaoquan Yang (Food Hydrocolloids, 2026)

Dietary silymarin improves gut–liver health by enhancing intestinal barrier integrity and modulating TLR4/NF-κB and NLRP3-mediated inflammatory responses in Aeromonas hydrophila–infected grass carp - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Hong-Yun Zhang; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Coated ferrous sulfate requirement for alleviating hypoxia-induced hepatopancreatic inflammation in sub-adult grass carp (Ctenopharyngodon idella) - Yu-Juan Yang; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Hong-Yun Zhang; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Ying-Gu Kuang; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Towards low-carbon construction: Nature-inspired internal patterns for thermal insulation in lightweight concrete component cast using 3D-printed formwork - Hanmo Wang; Yujia Wan; Shawn Owyong; En Tian Connie Lim; Abhimanyu Goel; Anqi Shi; Zhuyin Lu; Tam H Nguyen; Harn Wei Kua; Sunmi Shin; Alexander Lin (Energy and Buildings, 2026)

Utilizing conjugation effect of nitrogen unshared electron to architect redox-active polymer for sodium-ion storage - Liang-Yu Wang; Shun-Yu Yao; Jing-Zhe Wan; Qi-Hang Wang; Chao Ma; Jiu-Lin Wang; Kai-Xue Wang (Chemical Engineering Journal, 2026)

Ecological responses of the largest lake-wetland system (North China Plain) to hydrological regulation and cultural eutrophication over the past 70 years - Longjuan Cheng; John P. Smol; Qi Lin; Chaoran Wei; Shuyi Yang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Bin Xue (Anthropocene, 2026)

Mechanistic Links Between Suspended Sediment Dynamics and Metal Partitioning Under Tidal Forcing: A Case Study of Quanzhou Bay - Yanbin Fan; Yunhai Li; Yunpeng Lin; Shangshang Yang; Zhijie Chen; Xiang Cao; Chenyang Wang; Shanshan Zhang; Jinzeng Jiang; Mingyang Jiang; Kaichao Wan (Journal of Marine Science and Engineering, 2026)
The coupling of physical transport and phase-transfer processes represents a fundamental mechanism governing metal cycling in estuarine systems under tidal oscillations. Taking Quanzhou Bay as a model system, we conducted continuous observations and sample collection at the river channel (Q1), the turbidity maximum zone (Q2), and the outer bay channel (Q3). The metals (Al, Ti, Ba, Cu, Mn, and Zn) were measured by ICP-MS to systematically investigate the distribution, transport, and inter-media transfer across multiple water layers under varying estuarine processes. Our findings demonstrate that particulate metal concentrations in Quanzhou Bay exhibit strong synchrony with suspended sediment concentrations (SSC) over tidal cycles, displaying a distinct sediment-following pattern controlled by alternating end members. Particulate metal fluxes during flood and ebb-tides generally followed the hierarchy Q1 > Q2 >> Q3. Notably, stations Q1 and Q2 were dominated by flood-tide fluxes with net transport directed landward, whereas Q3 was characterized by ebb tide dominance with net flux directed seaward—revealing a spatial division of labor between “inner bay retention/reallocation” and “outer bay channel export”. In contrast, dissolved metals exhibited marked element-specific responses to tidal forcing: Al and Ti increased during flood tides at stations Q1 and Q2, while Ba and Cu showed opposite trends, and Mn and Zn displayed more conservative behavior. Concurrently, solid/liquid partition coefficient (logKd) values for Al, Ti and Ba, Cu exhibited inverse patterns over tidal cycles, suggesting divergent adsorption–desorption regulation under identical hydrodynamic conditions that drives differential phase-transfer dynamics. These disparities likely reflect intrinsic chemical properties and source variations among the elements. This study elucidates, at the tidal timescale, the coupled processes of “alternating end-member control—estuarine filter modulation—concurrent channelized export and inner bay retention” in Quanzhou Bay, providing critical process-level insights for metal flux quantification and bay pollution remediation initiatives in an ecological restoration project.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Captive breeding and early development of tank-reared lyretail anthias Pseudanthias squamipinnis (Peters, 1855): Assessments of hatching success, larval survival, and ontogeny - Ting-Chan Chou; Ang Lu; Yi-Yang Lin; Cheng-Chieh Wu; Hei-Wan Wong; Ho-Fai Yik; Bo-Kai Liao; Hong-Yi Gong; Yen-Ju Pan (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Bio-inspired rigid-Soft interaction for robust picking underwater - Shuqiao Zhong; Wanghongjie Qiu; Xudong Han; Chaoyang Song; Zhiyuan Zhou; Fang Wan; Jian Lin (Ocean Engineering, 2026)

CSP-YOWO-TrajNet: A spatio-temporal detection method for laying hen heat stress behavior - Zhenwei Yu; Liyin Zhang; Liqing Wan; Hai Lin; Khurram Yousaf; Geqi Yan; Hongchao Jiao; Chaoyuan Wang; Fuyang Tian (Journal of Thermal Biology, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

An enhanced sorting method for second-life lithium-ion batteries based on two-step clustering - Fu Wan; Yupeng Lin; Da Yang; Shufan Li; Ruiqi Liu; Lei Zhu; Wenwei Yin; Weigen Chen (Journal of Cleaner Production, 2026)

Fabrication and functionalisation of poly(ε-caprolactone)-based materials for water treatment: A comprehensive review - Yuzhuo Wang; Yixin Li; Wan Zhang; Leteng Lin (Journal of Environmental Chemical Engineering, 2026)

Adsorption mechanism of hydrogen bromide and 2-bromophenol on CuO, Cu2O, α-Fe2O3, and NiO catalysts: A density functional theory study - Lushi Sun; Jiaxing Du; Tao Chen; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Chemical Engineering, 2026)

W-induced reconstruction of NiFe (oxy)hydroxides with abundant O-vacancies as efficient electrocatalysts for water oxidation - Zhiqun Bai; Huifang Chen; Weihao Sha; Junru Lin; Jinyuan Miao; Ao Xie; Junqing Pan; Ran Pang; Kai Yan; Pingyu Wan; Yang Tang (Fuel, 2026)

Alkali promotion in nonmetallic boron-based catalysts: Establishing structure–activity correlations for selective methane oxidation - Ran Yan; Penghui Li; Siyu Liu; Xindi Zhang; Leisu Li; Chenxin Zhang; Shaolong Wan; Jingdong Lin; Xiaodong Yi; Lingtao Liu; Shuai Wang (Chemical Engineering Journal, 2026)

Unraveling the critical role of nanoplastics in governing the interfacial behavior and toxicity evolution of ciprofloxacin during Fenton oxidation process - Hanjun Zhu; Haishuai Cui; Guopei Huang; Hai Yang; Jukun Xiong; Meimei Ran; Xiaoping Lin; Quan Wan; Lele Yang; Zelin Xu; Xin Nie (Chemical Engineering Journal, 2026)

Injectable near-infrared–responsive silk fibroin nanocomposite hydrogel enabling spatiotemporally controlled photothermal chemotherapy - Ling-Chu Yang; Ching-Wen Hwang; Shao-Hsuan Tsao; Hsin-Yao Lin; Yunching Chen; Dehui Wan (Chemical Engineering Journal, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

A bezafibrate bearing Pt(IV) prodrug triggers ferroptosis via modulating lipid metabolism in lung cancer cells - Neng Wan; Xuan-Lin Ren; Xiang-Yu Ma; Tao Zhu; Cheng-Zhi Xie; Jing-Yuan Xu; Xin Qiao (JBIC Journal of Biological Inorganic Chemistry, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Histidine deficiency-induced hepatic steatosis in teleost fish probably linked to the formimidoyltransferase cyclodeaminase - Xin Zeng; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Digital mapping of soil fauna abundance and diversity using Sentinel-1/2 and environmental attributes - Luping Ye; Xiaoyuan Lin; Ligai Huang; Kang Ji; Tibor A. Drost; Wenjie Wan; Yong Zheng; Chuanqin Huang; Juan Zuo (Soil and Tillage Research, 2026)

Electrode Net: tailoring deep learning with signed distance field for fast and accurate multiscale design of porous electrodes - Pengzhu Lin; Jing Sun; Yinglun Tang; Jiayou Ren; Xiaosa Xu; Jin Li; Changxiang He; Shuaibin Wan; Wenjia Li; Tianshou Zhao (Science Bulletin, 2026)

Formononetin protects against oxaliplatin-induced peripheral neurotoxicity via Nrf2/HO-1 antioxidant pathway without impairing anticancer efficacy - Yang-Chen Chang; Wan-Hsuan Lin; Horng-Huey Ko; Yi-Ching Lo; Hsun-Shuo Chang; Hui-Ching Lin; Yih-Fung Chen (NeuroToxicology, 2026)

Conductive forward osmosis membranes modified with rGO-ZnO composites for improving aquaculture wastewater reclamation - Yi-Li Lin; Nai-Yun Zheng; Wan-Ru Tsai (Journal of Water Process Engineering, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Effects of galactomannan on the quality and component structure of hot-dry noodles during freeze-thaw cycles - Liuyu Wan; Yang Fu; Zhonghua Yuan; Peili Lin; Nian Cheng; Shensheng Xiao; Wenping Ding; Xuedong Wang (Food Chemistry, 2026)

Dietary chromium picolinate alleviates hypoxia-induced liver inflammation in juvenile grass carp (Ctenopharyngodon idella): Involving the synergistic regulation of ion homeostasis and mitochondrial DNA integrity - Chuan-Shuai Xiong; Lin Feng; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Hong-Yun Zhang; Jun Jiang; Xiao-Qiu Zhou; Pei Wu (Fish & Shellfish Immunology, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Association between urinary metabolites of 1,3-butadiene and toluene exposure with kidney function indices in Taiwanese school-aged children living near a petrochemical complex - Po-Keng Cheng; Vinoth Kumar Ponnusamy; Wei-Hong Lin; Jeganathan Chinnadurai; Pei-Chien Tsai; Cai-Yu Chen; Wan-Ting Chang; Po-Chin Huang (Environmental Pollution, 2026)

4D printing of a bioadhesive shape memory elastomer - Sonia Norouzi Esfahany; Alireza Mahjoubnia; Zehua Chen; Yuchao Wu; Wen Zhao; Hanwen Zhang; Caixia Wan; Shi-You Chen; Zheng Yan; Jian Lin (Chemical Engineering Journal, 2026)

Multi-objective Joint Optimization Operation of Cascade Reservoirs Considering River Hydrological Health Assessment - Chongxun Mo; Zihan Lin; Na Li; Xiaoyu Wan; Gang Tang; Yi Huang (Water Resources Management, 2026)

Deciphering the causes of getting lost in complex urban space: A multi-scale examination of spatial environmental indicators using multi-source data - Lin Yang; Mingxia Luo; Zejun Zuo; Mei-Po Kwan; Daping Xi; Bo Wan; Shunping Zhou (Applied Geography, 2026)

A Novel, Dual-Response Chemosensor Based on Ferrocene Derivative for the Selective Detection of Al3+ Ions : Fluorescence and Electrochemical Signaling - Wenqin Liu; Yanping Liu; Zenghui Li; Santai Zou; Pingnan Wan; Yan Lin (Journal of Fluorescence, 2025)

Path dependence meets export-driven decarbonization: A historical institutional analysis of Taiwan's renewable energy policies - Wan-Ching Wang; Tze-Luen Lin (Utilities Policy, 2025)

Divergent impacts of partial manure substitution on soil nitrous oxide emissions dependent on phosphorus availability - Yuheng Cheng; Jinbo Zhang; Hang-Wei Hu; Xiangyin Ni; Jianbo Fan; Song Wan; Mengmeng Feng; Christoph Müller; Ji-Zheng He; Yongxin Lin (Soil Biology and Biochemistry, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Sustainable recycling of spent graphite anodes: The critical role of thermal-assisted organic acid leaching in structural and performance restoration - Fu Wan; Wenwei Yin; Da Yang; Kaida Hu; Ruiqi Liu; Yupeng Lin; Weigen Chen (Journal of Environmental Chemical Engineering, 2025)

Unique ectomycorrhizal fungal association is a major conservation dilemma for the threatened ectomycorrhizal tree species - Ren-Cheng Liu; Wan-Rou Lin; Alija Bajro Mujic; Pi-Han Wang (Journal for Nature Conservation, 2025)

Laccase Co3(PO4)2 hybrid nanoflowers and multi-walled carbon nanotubes-based electrochemical sensor for bisphenol A analysis - Yang Wan; Jia Li; Xi Wu; Pan Wu; Lin Zhang (Food Research International, 2025)

Identification of new coumarin-cinnamic acid hybrid FtsZ inhibitors as potential bactericides for enhancing the yield and quality of rice - Ling Zhang; Si-yue Ma; Wan Chen; Lin-li Yang; Yue Ding; Xiang Zhou; Li-wei Liu; Zhi-bing Wu; Song Yang (Food Chemistry, 2025)

Structural insights and disinfection breakthroughs in shell eggs:A comprehensive review - Jun Sun; Xuhua Yang; Wanyue Zhang; Wan Lin; Bin Xu (Food Bioscience, 2025)

Tartary buckwheat-soy protein isolate composite gels: gelling, rheological, water-retention, and texture characteristics at different ratios - Xiao Han; Gen Ma; Lin Wang; Ting Cheng; Yangyang Guo; Liangzhen Jiang; Yan Wan; Xiaoqin Zheng; Changying Liu; Lianxin Peng; Gang Zhao; Xiulan Guo; et al. (Food Hydrocolloids, 2025)

Fire performance and post-fire residual behavior of insulated CFRP shear-strengthened RC beams: An experimental and numerical study - Wan-Yang Gao; Jun-Cong Lin; Ke-Xu Hu; Jian Yang (Engineering Structures, 2025)

Storm water management model simulations of the non-point source pollution load in the northern Anhui plain - Yun Wan; Mingjun Li; Nan Zhang; Mengwan Lin; Yuxuan Li; Peiqing Huang; Yuqi Feng; Bai Sun; Wei Wei; Shuguang Zhu (Ecohydrology & Hydrobiology, 2025)

Upcycling plastic waste into high-value gases via pulsed joule heating for economic and carbon benefits - Zitong Wan; Xuan Xie; Yunfeng Ma; Guohua Zhu; Rong Jin; Bingcheng Lin; Minghui Zheng (Chemical Engineering Journal, 2025)

Nanoconfined enzymatic cascade strategy for highly efficient synthesis of D-allulose - Kan Zhan; Anni Bao; Suhai Zhang; Liang Chen; Yichen Wan; Keke Hou; Jian Hao; Lin Chaoping; Zhiyong Sun; Renchao Zheng; Yuguo Zheng (Chemical Engineering Journal, 2025)

Structure-property synergy in functionalized triphenylamine-modified molecules: defect passivation and charge transport enhancement in perovskite solar cells - Changjian Huang; Xuefeng Xia; Jinfu Zeng; Tianxiang Zhao; Qianying Lin; Qixin Wan; Xia Yang; Zonghu Xiao; Zhihua Xiong (Chemical Engineering Journal, 2025)

Flexible bifunctional electrode with a record-breaking ΔE = 0.55 V for fast charging fiber zinc-air batteries - Long Jiang; Yumin Chen; Jing Zhou; Huangjian Chen; Yunzhan Ying; Shikun Liang; Yulong Wan; Shifan Zheng; Ju Lin; Yuyuan Yao; Lihua Gan; Lie Wang (Chemical Engineering Journal, 2025)

Exploring the protein complexity of lipid droplets in DHA-producing Schizochytrium sp. and potential applications of lipid droplet-associated proteins in lipid production - Chu-Bin Lin; Jun-Jie Wu; Xue-Qiang Chen; Jia-Xue Zhao; Shan Jiang; Xue-Rong Zhou; Peng-Yang Liu; Feng-Hong Huang; Xia Wan (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

Construction of a prognostic risk model for clear cell renal cell carcinomas based on centrosome amplification-related genes - Bingru Zhou; Fengye Liu; Ying Wan; Lin Luo; Zhenzhong Ye; Jinwei He; Long Tang; Wenzhe Ma; Rongyang Dai (Molecular Genetics and Genomics, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Historical spatiotemporal trends in global mangrove productivity and its response to the environment: Perspectives from multiple satellite-based productivity proxies - Qian Liu; Luoma Wan; Fei Xu; Ruikun Gou; Guanghui Lin; Xiaolin Zhu (Agricultural and Forest Meteorology, 2025)

High-Resolution Three-Pressure Prediction of Lianggaoshan Formation in LT1 Well block of Eastern Sichuan Risk Exploration Area - Yu-wei Wang; Ke-zhen Wan; Rong-rong Zhao; Wen-hao Li; Yang Lin; Hao Long; Hu Zhao (Applied Geophysics, 2025)

Potent phenolics with antimigratory and anti-MRSA powers from fungus associated with Saussurea involucrata - Wei-hua Yuan; Meng-ting Teng; Lin Ma; Yan-feng Wan; Kai-yue Lu; Yan-hui Shi; Peng Zhang (Natural Product Research, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Synergistic Fe S sites on paper sludge-derived biochar activating peroxymonosulfate via a singlet oxygen-enhanced pathway for efficient 2,4,6-trichlorophenol degradation - Weihua Lin; Lifeng Zhang; Xingxiang Ji; Jinquan Wan; Yongwen Ma (Journal of Water Process Engineering, 2025)

Clay sediment adhesion-dominated clogging and its recovery under infiltration washing in statically compacted pervious concrete - Yu Ding; Yapei Xia; Lin Guo; Qi Wan; Zhenyao Xia; Hai Xiao; Yunkang Rao (Journal of Hydrology, 2025)

Synergistic effects of biochar and E. coli on reducing cadmium bioavailability and improving soil fertility through enhanced bacterial-fungal interactions - Quan Chen; Rongrong Lin; Wan-Rong Zhang; Yafeng Wang; Yanqing Xiong; Pengfei Wang; Yu Huang; Min Wu; Peng Yi; Bo Pan (Journal of Hazardous Materials, 2025)

Multi-functional Fe-metallohydrogel with peroxidase/oxidase activities for dye degradation and nitrite detection - Xiao-Juan Wang; Kai-ting Liu; Chuan-Wan Wei; Shu-Qin Gao; Ying-Wu Lin (Food Chemistry, 2025)

Tyramine injection enhances immune function and disease resistance in Penaeus monodon - Wan-Lin Tsai; Li-Yang Hsu; Cheng-Ying Li; Hsin-Wei Kuo; Winton Cheng (Fish & Shellfish Immunology, 2025)

Humid heat’s nonlinear impact on school-age children’ sleep health: Evidence from Guangdong, China - Yuan Gao; Li-Zi Lin; Wen-Wen Bao; Wan-Ting He; Yun-Ting Zhang; Guang-Hui Dong; Shenjing He (Environmental Research, 2025)

Revealing the role of Fe particle size in soft magnetic geopolymer for enhancing energy conversion in airport pavement induction heating - Gonghui Gu; Xinchi Xu; Jinsheng Han; Lin Wan-Wendner; Zhiji Gao; Rongze Fu; Chuanqing Fu; Tao Ma (Energy and Buildings, 2025)

Single-stage reverse-structured solar evaporator from two to three dimensional by transparent hydrogel - Shen Du; Bing-Lin Bai; Ya-Ling He; Mingyun Dai; Jia-Cheng Wan (Chemical Engineering Journal, 2025)

Platinum-copper nanocubezyme facilitate spinal cord recovery via synchronously alleviating oxidative stress and mitigating BNIP3-mediated mitochondrial dysfunction - Xiangge Liu; Cheng Peng; Huiyi Yang; Jiajun Deng; Ping Wu; Yongchun Xiao; Li Wan; Ke Wang; Guowei Zhang; Hua Yang; Jianyu Zou; Judun Zheng; et al. (Chemical Engineering Journal, 2025)

Mechanochemical synthesis of ZnO@TiO2 II heterojunction material: Photocatalytic degradation and antibacterial synergistic effect - Juan Pei; Xiaoling Wan; Mingxing Guo; Jialan Mi; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Siwei Xiang; Qianyu Zhang; Haichun Zeng; et al. (Chemical Engineering Journal, 2025)

CFD simulation of multifluid mixing and structure optimization of rotating liquid film reactor for magnesium hydroxide production - Wenwen Lin; Jiahao Wan; Yingying Zhang; Wenyan Liu; Kaitao Li; Xiongzhong Yan; Jicang Li; Shengting Li; Wendi Liu; Yanjun Lin (Chemical Engineering Journal, 2025)

Protective Effects of Deinoxanthin on Brain Oxidative Damage and Gut Microbiota in the D-Galactose-Induced Aging Mice - Huijuan Su; Yutao Li; Jiayi Wan; Jieyu Lin; Jiayao Wang; Rui Fan; Dingming Liu; Jing Wei; Hongbo Xin; Yuejin Hua; Shengjie Li (Molecular Neurobiology, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Vitamin E alleviates ammonia‑nitrogen and hypoxia co-exposure-induced intestinal damage in grass carp (Ctenopharyngodon idella) by modulating mitochondrial function, cellular autophagy and apoptosis - Rui Su; Ke Yao; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Pei Wu (Aquaculture, 2025)

Stable two dimensional copper(II) based metal-organic framework as an efficient peroxymonosulfate activator for tetracycline degradation - Jia-Ting Chen; Wan-Yi Wang; Si-Tong Chen; Wen-Bin Chen; Yan-Yong Lin; Meng Yang; Wen Dong (Journal of Environmental Chemical Engineering, 2025)

Carbon-nitrogen-phosphorus level regulation of potentially toxic elements and enzyme activities in paddy soil aggregates: Straw and organic fertilizer effects - Keqi Zhao; Wenbo Xiao; Nanyi Wang; Xiaobing Zhang; Ying Wang; Hua Peng; Jiachao Zhang; Anwei Chen; Renli Qi; Fangying Yu; Dan Wan; Lin Luo; et al. (Journal of Environmental Chemical Engineering, 2025)

Multi-level Priors-Guided Diffusion-based Remote Sensing Image Super-Resolution - Lijing Lu; Zhou Huang; Yi Bao; Lin Wan; Zhihang Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Investigation of physical mechanisms behind full-scale engineered barrier systems through coupled thermal-hydraulic-mechanical (THM) simulations - Chia-Wei Kuo; Wan-Jung Kuo; Chung-Yi Lin (International Journal of Rock Mechanics and Mining Sciences, 2025)

Virtual screening and molecular mechanism of novel anti-benign prostatic hyperplasia peptides from Syngnathus schlegeli - Ailing Duan; Xiangxi Yi; Xiangtan Zhao; Si Li; Xinjian Qu; Geng Qin; Qiang Lin; Hua Chen; Peng Wan; Deke Chen; Xin Chen; Weimao Zhong; et al. (Food Research International, 2025)

A generalized chemical kinetics explains heterocyclic amine formation in high-temperature processed meats - Kuen-Yuh Wu; Yu-Hsuan Kuo; Pei-Chen Chao; Yu-Syuan Luo; Wan-Yu Lin; Su-Yin Chiang (Food Chemistry, 2025)

Reinforcement mechanism of black tea on the gel properties of preserved egg protein: Metal ion “pore-blocking effect” and EWP denaturation-aggregation-reorganization - Baochang Li; Yishu Wang; Wan Lin; Ruipeng Ma; Bin Xu; Jun Sun (Food Chemistry, 2025)

Differential electric field homogenization postponed dendrite formation of zinc anodes at limiting current for long-life aqueous zinc batteries - Yin Yang; Xin Chen; Jingying Li; Jia Yao; Yi Gan; Junjie Zheng; Luyang Ge; Lin Lv; Li Tao; Jun Zhang; Hanbin Wang; Hao Wang; et al. (Chemical Engineering Journal, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Integrated core-shell structured dual-mode thermoresponsive optical-electrical sensing fiber for accurate temperature recognition and early fire warning - Hualing He; Jie Xu; Md Hasib Mia; Zhonghe Yu; Yuhang Wan; Qing Jiang; Xueru Qu; Jinru Liu; Lin Hou; Yueyue Song; Zhicai Yu (Chemical Engineering Journal, 2025)

Self-reconstructed Cu2O/Co3O4@NC heterostructured catalyst for efficient tandem electrocatalytic conversion of nitrate to ammonia - Lin Zhu Dai; Guo Yu Yong; Wan Ni Gan; Ting Li; Zhi Cheng Chen; Lun Yao Pan; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2025)

Self-healing and thickness-insensitive perylene diimide-based cathode interfacial layers for organic solar cells - Wei Chen; Dan Zhou; Lin Hu; Jiangang Ma; Guobin Shen; Wentian Wan; Shuhua Wang; Fang Wang; Ruizhi Lv; Bin Hu; Haitao Xu; Zaifang Li; et al. (Chemical Engineering Journal, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Upregulation of PD-1 on Peripheral T cells Subsets is Associated with Parkinson's Disease - Zhi-Ling Zhang; Pang-Hai Ye; Wei-Xin Kong; Jin Li; Si Zhu; Yu-Wan Lin; Ping-Yi Xu; Wen-Yuan Guo (Molecular Neurobiology, 2025)

Development and application of InDels and SNPs markers based on whole-genome resequencing in Chinese cabbage - Kai-Wen Liu; Wan-Jie Men; Jin-Xia Feng; Iqbal Hussain; Hui Sheng; Li-Wei Zhang; Zhong-Ren Dai; Hai-Jiang Hu; Jian-Hao Yang; Na Lei; Xiao-Lin Yu (Horticulture, Environment, and Biotechnology, 2025)

Impact of SNP Variants in PON-1 or UGT1A1 on Iron Chelation Therapy Outcomes and Zinc Status in Thalassemia Major Patients - Meng-Yao Lu; Wan-Fu Tsai; Chang-Shiann Wu; Chien-Sheng Wang; Nailis Syifa; Mong-Liang Lu; Jiahn-Haur Liao; Wei J. Chen; Kai-Hsin Lin; Tzu-Hua Wu (Biological Trace Element Research, 2025)

Phosphorus mitigates nitrite stress-induced liver damage in adult grass carp (Ctenopharyngodon idellus) by alleviating mitochondrial dysfunction and inhibiting apoptosis - Jia-Hao Zhang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Lu Zhang; Hai-Feng Mi; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

New perspective on mechanism of L-arginine in promoting skeletal muscle growth of grass carp (Ctenopharyngodon Idella): Via enhancing skeletal muscle functions and regulating energy metabolism - Qiu-Yan Chen; Yu-Long Ma; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

Integrating machine learning and metabolomics to uncover new biomarkers for predicting pesticide exposure among patients with kidney function decline - Junne-Ming Sung; Yu-Chi Hung; Wan-Ru Wang; Chiau-Jun Chu; Yen-Ping Lin; Kuan-Hung Liu; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2025)

Performance of separating rare earth enrichment from aqueous solution by flat ceramic membrane process and pollution control strategy - Chonggang Wang; Youming Yang; Jiuyang Lin; Feifei Yang; Hongmei Ye; Xuewei Li; Yinhua Wan (Minerals Engineering, 2025)

Nitrogen doping enhances PMS activation by MnFe2O4-NBC through generating active sites and establishing an internal electric field - Xiaoni Lin; Qiang Ge; Xianbo Zhou; Yan Wang; Congyun Zhu; Kuanyong Liu; Jinquan Wan (Journal of Water Process Engineering, 2025)

Recent advances in bioassays for assessing the toxicity of environmental contaminants in effect-directed analysis - Yao Liu; Minjie Li; Qi-Lin Wan; Xun Wang; Monika Mortimer; Wen-Di Fang; Liang-Hong Guo (Journal of Environmental Sciences, 2025)

Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Yan-Jun Bao; Yuan-Yuan Sun; Di Zhang; Jian-Fei Yan; Yu-Peng Men; Wei Sun; Jia-Shan Lin; You-Li Wan; Jian-Wei Kang; Wen-Hua Wang; Qiangba Zhaxi (Journal of Asian Earth Sciences, 2025)

Forest and mosaic vegetation cut off savanna corridors during the Last Glacial Maximum in Southeast Asia recorded by marine pollen - Gang Lin; Chuanxiu Luo; Dileep Bandara Herath; Sui Wan; Xiang Su; Yiping Yang; Mingzhen Zhong; Zhiying Wang; Xun Yuan; Rong Xiang (Global and Planetary Change, 2025)

Navigating crowds: Reconsidering visitor recreational experience and crowding preference for a forest park in Taiwan - Wan-Yu Liu; Chin-Chun Yen; Rachel S.K. Lee; Chun-Cheng Lin (Forest Policy and Economics, 2025)

High-efficiency blue fluorescent OLEDs enabled by a cost-effective blade-coated planar source evaporation strategy - Wan-Zhen Fo; Jun Li; Zhi-Lin Zhang; Bin Wei; Qisheng Zhang (Chemical Engineering Journal, 2025)

Identification of a dominant stripe rust resistance gene YrXY on chromosome 6R in hexaploid triticale - Yu Lin; Yahan Yang; Yichang Gou; Zhenzhen Xue; Genxi Huang; Hongshen Wan; Zhiqiang Wang; Lin Huang; Houyang Kang; Yi Wang; Yonghong Zhou; Haiqin Zhang (Theoretical and Applied Genetics, 2025)

Evaluation and Dissection of Sensory Quality Traits for Potato Taste - Ying Wang; Wan-lin Yang; Fan-kui Zeng; Chun-ni Lei; Qiong-fen Yang; Jian Wang (Potato Research, 2025)
The sensory qualities of potatoes significantly influence consumer preference. This study evaluated the sensory qualities of 66 potato varieties, focusing on representatives of distinct taste types for detailed analysis: sensory evaluation, taste, nutritional components, texture properties, physicochemical characteristics of starch, and volatile aroma compounds. Sensory evaluation of these potato varieties identified the landrace “Kaihua Yangyu” as the most favoured by consumers. The favourable taste of Kai Hua Yang Yu was attributed to (1) soft, dry, and non-sticky texture; (2) starch with higher peak viscosity, easier gelatinisation (below 70 ℃), higher setback value (2776 RVU), and larger granule size (41.63 ± 9.90 μm) compared with other such as YS105 and Cooperation88; and (3) distinctive umami flavour, a trait notably associated with elevated levels of aspartic acid and glutamic acid.

Tremella fuciformis Polysaccharides Alleviate Early Brain Injury in Experimental Subarachnoid Hemorrhage by Inhibiting the KDR-Mediated P38 MAPK/NF-κB Pathway - Yu-hui Wan; Zeng-jing Cheng; Ling-xiang Fan; De-hong Yang; Bing-lin Chen; Xiang-xin Chen; Qing Zhu (Molecular Neurobiology, 2025)

Responses of plant community drought resistance and resilience to warming and nitrogen addition vary with recurrent droughts in a semi-arid grassland - Haidao Wang; Jian Song; Yongge Fan; Jianyang Xia; Lin Jiang; Qingshan Zhang; Heng Li; Jingyi Ru; Jiayin Feng; Lingjie Kong; Jiajun Zhang; Xueli Qiu; et al. (Agriculture, Ecosystems & Environment, 2025)

Multichannel deconvolution based on spatial structurally constraint and its applications - Wan-Li Wang; Hu-Gao Jian; Wei Wang; Lin Li (Applied Geophysics, 2025)

YOLO-CMST: Towards accurate pineapple flowering induction using YOLO-based models with the Cross Multi-Style Translator - Kuang-Yueh Pan; Wan-Ju Lin; Jian-Wen Chen; Yi-Hong Lin (Computers and Electronics in Agriculture, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Assessment of the combined response of heavy metals and human pathogens to different additives during composting of black soldier fly manure - Nanyi Wang; Yong He; Xiaobing Zhang; Ying Wang; Hua Peng; Jiachao Zhang; Xichen Zhao; Anwei Chen; Renli Qi; Dan Wan; Lin Luo; Liuqin He (Journal of Hazardous Materials, 2025)

Tea polyphenols: A promising alternative to antibiotics for preventing bacterial enteritis in grass carp (Ctenopharyngodon idella) - Yao-Bin Ma; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng (Food Research International, 2025)

Evaluating palm olein and palm stearin on hepatic lipids in C57BL/6 J mice under low and high fat intakes: A quantitative lipidomic approach - Liting Wan; Lin Li; Xia Zhang; Bing Li; Kristen J. Brao; Janette M. Harro; Mark E. Shirtliff (Food Chemistry, 2025)

Rheological and tribological properties of skimmed milk gels: The impact of fish collagen peptides-polysaccharides complexes during acidification - Xiaoxuan Zhang; Shijie Wan; Shuojia Liang; Yuanyuan Jiang; Xueke Chen; Yijiao Zou; Cuilan Fang; Xiang Lu; Yun Zhou; Guohua Zhao; Lin Lei (Food Chemistry, 2025)

Interface molecular reconstruction with scarcity active factor for long-life aqueous zinc batteries at thermal environment - Xin Chen; Yin Yang; Runzhi Liang; Junjie Zheng; Jia Yao; Jingying Li; Yi Gan; Xin Liu; Xiaodong Liang; Ze Wang; Qin Liu; Lin Lv; et al. (Chemical Engineering Journal, 2025)

Iron-modified electroactive material mediated chain elongation: Bridging pseudocapacitance and caproate biosynthesis - Zi-Lin He; Yong-Yao Zhang; Tian Lan; Wei-Tong Ren; Hua-Zhe Wang; Juan-Shan Du; Qing-Lian Wu; Wan-Qian Guo (Chemical Engineering Journal, 2025)

Novel sequential ozonolysis-hydrolysis treatments for microcrystalline cellulose synthesis from oil palm empty fruit bunch - Pavitra Thevi Arnandan; Wan Nor Nadyaini Wan Omar; Zhahidah Husna Hassan; Muhammad Sufri Abd Muhaimin; Danish Akmal Jihat@Ahmad; Makam Mba Michele Raissa; Amnani Shamjuddin; Ken-Lin Chang; Nor Aishah Saidina Amin (Biomass and Bioenergy, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Lactiplantibacillus plantarum GMNL-661 Ameliorates Clostridioides difficile Infection and Reconfigures Intestinal Microbiota in a Murine Model - Meng-Jia Li; Hong-Ming Chen; Yueh-Lin Chen; Yi-Hsin Lai; Cheng-Yu Lai; Jhen-Wei Ruan; Jenn-Wei Chen; Wan-Hua Tsai; Wen-Chien Ko; Pei-Jane Tsai (Probiotics and Antimicrobial Proteins, 2025)

Improving grain yield in crop/forage intercropping systems by altering forage cutting date - Fangru Wan; Lin Xiang; Guanrong Dai; Xiaozheng Wang; Jiena Li; Yinjuan Li; Baoqing Zhang; Longshuai Ma (Plant and Soil, 2025)

Antarctic circumpolar current evolution and its relation to southern hemisphere westerly winds during the holocene - Lingfeng Wan; Dapeng Li; Chenyu Zhu; Zhengyu Liu; Shaoqing Zhang; Xiaopei Lin; Jiuyou Lu (Climate Dynamics, 2025)

Impact of Chlorine Substitution on the Interaction Between Amide Herbicides and Alkaline Phosphatase: Insights into Molecular Mechanisms and Structure-Activity Relationships - Xiaoning Wang; Jiayin Ding; Yiyong Xu; Jingyan Lin; Yongkun Wu; Yuhan Zhao; Wenyue Wang; Shan Hong; Ziheng Wan; Kaipeng Sun; Dong Chen; Chuanxi Yang; et al. (Bulletin of Environmental Contamination and Toxicology, 2025)

Skillful Prediction of East Asian Surface Air Temperature One Season ahead Using QBO in March - Tian Wan; Chang-Hyun Park; Jung Choi; Seok-Woo Son; Lin Wang (Journal of Meteorological Research, 2025)

The Arctic Oscillation Response to the QBO in an EOF-Based QBO Phase Space - Tian Wan; Lin Wang; Seok-Woo Son; Yixiong Lu; Xiaocen Shen; Chang-Hyun Park (Journal of Meteorological Research, 2025)

Exploration of complex physical and chemical processes of a severe haze episode over central Taiwan - Chuan-Yao Lin; Wen-Mei Chen; Yang-Fan Sheng; Wan-Chin Chen; Hing Cho Cheung; Charles; C.K. Chou (Science of The Total Environment, 2025)

Mitigation of the toxic effects of nitrite: Role and mechanism of isoleucine in mitigating mitochondrial DNA leakage-induced inflammation in grass carp (Ctenopharyngodon idella) under nitrite exposure - Kai-Xuan Ren; Lin Feng; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Cheng-Bo Zhong; Xiao-Qiu Zhou; Wei-Dan Jiang (Journal of Hazardous Materials, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

The chemical basis of aroma/taste and color formation in green tea infusion during cold brewing revealed by metabolomics analysis - Chen Yang; Zhaojun Wang; Minghui Xu; Kaikai Wei; Qianying Dai; Xiaochun Wan; OiPo Leong; Runze Lin; Chuanjian Cui; Ruyan Hou (Food Chemistry, 2025)

Conformational and rheological property comparison for three exudates gums containing type II arabinogalactans - Xing Jia; Zhiyuan Xu; Meng Xiao; Yueru Jiang; Lin Ma; Wan Wang; Qiaomei Zhu; Ji Kang; Qingbin Guo; H. Douglas Goff (Food Hydrocolloids, 2025)

Fundamental insights into Brønsted acid-induced adduction improve small metabolite profiling in mass spectrometry - Wanshan Liu; Wei Chen; Yanyan Li; Shouzhi Yang; Jing Cao; Jiao Wu; Yida Huang; Ruimin Wang; Xiaonan Chen; Lin Huang; Jiayi Wang; Kun Qian; et al. (Chemical Engineering Journal, 2025)

Remediation of Heavy Metal Contaminated Soil by Functional Pellets of Charcoal Organic Fertilizer: Rhizosphere and Non-Rhizosphere Soil Microorganisms - Fanghong Li; Xichen Zhao; Renli Qi; Liuqin He; Dan Wan; Jiachao Zhang; Xiaobing Zhang; Ying Wang; Genyi Wu; Hongli Huang; Lin Luo; Lihua Zhang (Water, Air, & Soil Pollution, 2025)

Infrared Laser Stimulation of Purkinje Cells Primarily Depends on TRP Channel Activation - Bin-Bin Dong; Chen Wang; Wan-Qi Huang; Yu-Peng Bian; Jun Liu; Wei Chen; Lin Zhou; Ying Shen; Luxi Wang (Neuroscience Bulletin, 2025)

Interactions of nematodes and ammonia-oxidizing bacteria mediate nitrification in two contrasting soils - Qing Wan; Lin Chen; Jianming Xu; Donghao Ma; Wei Li; Shixiu Zhang; Yong Li; Weiwei Jin; Jiabao Zhang (Journal of Environmental Management, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Mercury migration characteristics and the re-emission inhibition in seawater flue gas desulfurization system - Chuanwei Li; Gan Wan; Linlin Xu; Jiaxing Du; Lushi Sun; Li Lin (Journal of Environmental Chemical Engineering, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

Long-term exposure to zearalenone: Assessing risks and effects on aquatic food safety and quality - Hong-Yun Zhang; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Xiao-Qiu Zhou; Lin Feng (Food Bioscience, 2025)

Untargeted metabolomics and network pharmacology reveal the uric acid-lowering effects of alcohol extract of Gnaphalium affine and its extracts in hyperuricemic rats - Chen Wang; Xinchao He; Lijuan Rao; Jiajing Liao; Jin Qian; Xuefeng Yu; Sen Mei; Suqin Lin; Linqian Xu; Guiming Fu; Yin Wan (Food Bioscience, 2025)

In situ multifunctional gel for hormone-immune therapy of ovarian cancer and prevention of postoperative adhesion - Yankun Zhang; Yanbin Shi; Hengchang Zang; Xiaogang Zhao; Xianglei Fu; Shengnan Qiu; Yuan Zhang; Yingying Liu; Xiaoyu Wan; Zengmei Li; Yaqi Li; Jiamin Zhou; et al. (Chemical Engineering Journal, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Mito-Apocynin Protects Against Kainic Acid-Induced Excitotoxicity by Ameliorating Mitochondrial Impairment - Miaomiao Lin; Huanchen Wu; Xiaorui Wan; Na Liu; Yiyue Jiang; Yichao Sheng; Jing Wang; Haidong Xu; Jie Xue; Zhenghong Qin; Yan Wang (Molecular Neurobiology, 2025)

Identification and stability of QTLs for grain traits in the elite wheat variety ‘Chuanmai104’ - Zehou Liu; Hao Tang; Yuanyuan Lin; Xiaojiang Guo; Huixue Dong; Li Cai; Ying Liu; Qin Wang; Hongshen Wan; Fan Yang; Ning Yang; Jirui Wang; et al. (Cereal Research Communications, 2025)

New perspectives on the immune regulatory role of dietary silymarin in the intestines of juvenile grass carp (Ctenopharyngodon idella) - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Low-level exposure to environmental lithium element affects male reproductive outcomes: Results from the MARHCS cohort study in Chongqing, China and in vivo animal experiments - Lihong Wang; Guanghui Zhang; Xi Ling; Mei Wan; Qing Chen; Lei Sun; Huan Yang; Tong Wang; Jinyi Liu; Jia Cao; Lin Ao; Peng Zou (Reproductive Toxicology, 2025)

The calcined Mg-Al hydrotalcite for copper adsorption and passivation of copper-contaminated soil - Chun-Yan Cao; Ming-Hui Nie; Si-Lin Chen; Wen-Ling Long; Min Wang; Shuang Zhao; Xin Wan; Zhi-Guo Song (Process Safety and Environmental Protection, 2025)

Histidine improves flesh quality: An assessment of grass carp (Ctenopharyngodon idella) muscle in terms of texture, nutritional value and flavor - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Lin Feng (Food Chemistry, 2025)

Optimizing plant density and nitrogen fertilization in jujube/cotton intercropping systems for sustainable yield and reduced greenhouse gas emissions - Nan Cao; Guodong Chen; Shuang Wang; Huqiang Li; Jiao Lin; Qiang Hu; Sumei Wan (Field Crops Research, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Eggshell-inspired heterogeneous bilayer paper window with selective gas permeability for preserving fresh produce - Lin Peng; Junyu Chen; Yongye Chen; Azadeh Nilghaz; Xueyan Yun; Xiaofang Wan; Huanhuan Zhan; Junfei Tian (Chemical Engineering Journal, 2025)

Remediation of Pb-contaminated soils using thermally activated Mg-Al hydrotalcite - Chun-Yan Cao; Wen-Ling Long; Si-Lin Chen; Ming-Hui Nie; Min Wang; Shuang Zhao; Xin Wan (Journal of Soils and Sediments, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Using end-member model algorithm to infer sedimentary processes from mangrove sediment grain-size in Guangdong, South China - Zhanyi Lin; Qiuchi Wan; Fan Zhang; Jing Zhong; Zhongle Zhou; Kunshan Bao (Regional Studies in Marine Science, 2025)

The dewatering performance of streptomycin mycelial residue promoted by the Fenton process synergistic with biochar - Lushi Sun; Jiaxing Du; Xingxing Zhou; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Management, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Horizontally oriented 2D skin structures on fiber interface for long-life flexible energy storage devices - Guangyu Fang; Xiaorui Ma; Rong Hu; Jiao Dai; Haoran Tian; Lin Li; Weilin Xu; Yonggang Yao; Jun Wan (Chemical Engineering Journal, 2025)

Boosted catalytic soot oxidation by hierarchical hollow cobalt oxide constructed from a Template-Sacrificial Method: Promoting Roles of morphologies and oxygen vacancies - Yu-Chih Tsai; Mei-Chen Wan; Shen Yan Lin; Vo Thi Thanh Thuy; Nguyen Nhat Huy; Duong Dinh Tuan; Jechan Lee; Kun-Yi Andrew Lin (Chemical Engineering Journal, 2025)

Preferred crystal plane growth orientation induced by low-energy ions for highly reversible zinc anodes - Guanzhong Wang; Xiyan Bao; Xiaofang Wang; Xize Chen; Wei Lai; Di Wu; Chen Zhang; Lin Gao; Minglei Cao; Xingxing Li; Qin Wang; Hao Wang; et al. (Chemical Engineering Journal, 2025)

Perylene diimide cathode interface layer with siloxane bay-modification for efficient and stable organic solar cells - Dan Zhou; Yujie Pu; Yanyan Wang; Lin Hu; Jianwei Quan; Senmei Lan; Jiangang Ma; Fang Wang; Wentian Wan; Yongfen Tong; Ruizhi Lv; Haitao Xu; et al. (Chemical Engineering Journal, 2025)

Retraction notice to “Activities of functional enzymes involved in C, N, and P conversion and their stoichiometry during agricultural waste composting with biochar and biogas residue amendments” [Bioresour. Technol. 345 (2022) 126489] - Nanyi Wang; Liheng Ren; Jiachao Zhang; Mukesh Kumar Awasthi; Binghua Yan; Lihua Zhang; Fachun Wan; Lin Luo; Hongli Huang; Keqi Zhao (Bioresource Technology, 2025)

Decade-long application of preimplantation genetic testing for DMD/BMD: analysis of five clinical strategies and embryo recombination patterns - Weili Wang; Jing Dai; Xiao Hu; Wenbin He; Yifan Gu; Zhenxing Wan; Yi Zhang; Keli Luo; Wen Li; Qianjun Zhang; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2025)

Polyploid crape myrtle was produced through hybridizing with 2n gametes induced by high-temperature - Yu Xu; Qi Hu; Qifang Lin; Xiufeng Chi; Ping Shen; Xin Wang; Zhiting Wan; Xinwei Jiang; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Euphytica, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Associations between lifestyle factors, physiological conditions, and epigenetic age acceleration in an Asian population - Yu-Ru Wu; Wan-Yu Lin (Biogerontology, 2025)
Epigenetic clocks use DNA methylation (DNAm) levels to predict an individual’s biological age. However, relationships between lifestyle/biomarkers and epigenetic age acceleration (EAA) in Asian populations remain unknown. We here explored associations between lifestyle factors, physiological conditions, and epigenetic markers, including HannumEAA, IEAA, PhenoEAA, GrimEAA, DunedinPACE, DNAm-based smoking pack-years (DNAmPACKYRS), and DNAm plasminogen activator inhibitor 1 level (DNAmPAI1). A total of 2474 Taiwan Biobank (TWB) individuals aged between 30 and 70 provided physical health examinations, lifestyle questionnaire surveys, and blood and urine samples. Partial correlation analysis (while adjusting for chronological age, smoking, and drinking status) demonstrated that 29 factors were significantly correlated with at least one epigenetic marker (Pearson’s correlation coefficient | r |> 0.15). Subsequently, by exploring the model with the smallest Akaike information criterion (AIC), we identified the best model for each epigenetic marker. As a DNAm-based marker demonstrated to predict healthspan and lifespan with greater accuracy, GrimEAA was also found to be better explained by lifestyle factors and physiological conditions. Totally 15 factors explained 44.7% variability in GrimEAA, including sex, body mass index (BMI), waist-hip ratio (WHR), smoking, hemoglobin A1c (HbA1c), high-density lipoprotein cholesterol (HDL-C), creatinine, uric acid, gamma-glutamyl transferase (GGT), hemoglobin, and five cell-type proportions. In summary, smoking, elevated HbA1c, BMI, WHR, GGT, and uric acid were associated with more than one kind of EAA. At the same time, higher HDL-C and hemoglobin were related to epigenetic age deceleration (EAD). These findings offer valuable insights into biological aging.

Plant Acquisitive Strategies Promote Resistance and Temporal Stability of Semiarid Grasslands - Pu Yan; Nianpeng He; Marcos Fernández‐Martínez; Xian Yang; Yiping Zuo; Hao Zhang; Jing Wang; Shiping Chen; Jian Song; Guoyong Li; Enrique Valencia; Shiqiang Wan; et al. (Ecology Letters, 2025)
Among ecologists, it is widely believed that conservative growth strategies of plants are crucial for sustaining ecosystem stability, while the potential stabilising role of acquisitive strategies has received little attention. We investigated the relationships between plant traits and three stability dimensions—temporal stability, resistance and resilience—using two complementary datasets from drought‐affected semi‐arid grasslands: a temporal plant community survey from a single site and a 1000‐km transect survey with satellite‐derived productivity estimates. We found strikingly consistent patterns from the two datasets, with grasslands dominated by acquisitive strategies exhibiting greater resistance and temporal stability of productivity. Acquisitive strategies enhance stability by facilitating drought escape and avoidance, rather than drought tolerance typically associated with conservative strategies. These results highlight the important but underappreciated role of acquisitive strategies in enhancing ecosystem resistance to disturbances and maintaining temporal stability in semi‐arid grasslands.

Mercury (II) adsorption and gaseous mercury re-emission inhibition from seawater flue gas desulfurization (SFGD) wastewater by Fe-Cu bimetallic modified activated carbon - Lushi Sun; Gan Wan; Ke Tang; Linlin Xu; Li Lin (Fuel, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Harnessing multi-target nanosweepers inhibiting β-amyloid aggregation, scavenging reactive oxygen species and overcoming the blood brain barrier for rescuing Alzheimer’s disease - Yixuan Wang; Chaoren Yan; Yuming Qi; Ruobing Zhao; Yan Wan; Zhaoyuan Lyu; Yansong Li; Zhijuan Wang; Changqing Li; Yuehe Lin; Qian Chen; Shichao Ding; et al. (Chemical Engineering Journal, 2025)

Effects of biochar and compost on the bioavailability of heavy metals in soil aggregates with varying particle sizes - Fanghong Li; Shilin Jiang; Ge Chen; Dan Wan; Liuqin He; Jiachao Zhang; Keqi Zhao; Hongli Huang; Lin Luo; Genyi Wu; Lihua Zhang (Journal of Soils and Sediments, 2025)

Enhancing astaxanthin production in Schizochytrium sp.: Insights from orthogonal experiments and transcriptome analysis - Jiaxue Zhao; Dan Chen; Chubin Lin; Xia Wan (Algal Research, 2025)

Color variation and mate choice in a lacertid lizard - Wan-Xin Jian; Tsui-Wen Li; Fitra Arya Dwi Nugraha; Chen-Pan Liao; Tsung-Chen Lee; Ko-Huan Lee; Si-Min Lin (Behavioral Ecology and Sociobiology, 2025)

Aggregative Infestation of Nine Bostrichidae Species on the Madagascar Almond Tree, Terminalia neotaliala Capuron (Myrtales: Combretaceae) - Xiao-Lu Cao; Li Yu; Jian-Song Wei; Qiu-Hong Tao; Qian Lu; Wan-Xuan Wei; Xia-Lin Zheng (Neotropical Entomology, 2025)

Identification and characterization of Alternaria spp. causing leaf blotch on Salix matsudana: A study from Rudong city, China - Yi-Lin Chen; Bing-Yao Peng; Yu Wan; De-Wei Li; Li-Hua Zhu (Crop Protection, 2025)

Protective effects of dietary protein against nitrite stress in grass carp (Ctenopharyngodon idella): A new perspective - Hong-Ju Liu; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Hai-Feng Mi; Min Dong; Lu Zhang; Lin Feng (Aquaculture, 2025)

Induction of GPX4-regulated ferroptotic stress promotes epithelial-to-mesenchymal transition in renal tubule cells induced by PM2.5 - Chien-Hung Lin; Wen-Sheng Liu; Chuan Wan; Hsin-Hui Wang (Toxicology and Applied Pharmacology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Discovering potential fumigants against Tribolium castaneum from essential oils using GC-MS and chemometric approaches - Yan Yan Lin; Min Xing Zhang; Miao Sun; Lu Sheng Wan; You Zhou; Jing Sheng Chen (Journal of Stored Products Research, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

Flowering in aged white tea: Recovering umami taste and amplifying of stale aroma - Wan Zhu; Xinyu Feng; Yani Pan; Haowei Guo; Yunqing Liu; Xingchen Lin; Fangyuan Fan; Shuying Gong; Ping Chen; Qiang Chu (Food Chemistry, 2025)

Comprehensive suitability assessment of fish habitat by integrating mechanism model and bayesian network model - Yuliang Yuan; Ran Li; Jingjie Feng; Hang Wan; Honghui Lin; Xiaolong Cheng (Ecological Engineering, 2025)

MEHP induced mitochondrial damage by promoting ROS production in CIK cells, leading to apoptosis, autophagy, cell cycle arrest - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

The Proteomic Analysis of Chronic Migraine Exosomes Reveals Disease Patterns and Potential Biomarkers - Weiyun Zhang; Fen Wan; Lihui Duan; Wen Tao; Jun Wang; Lin Huang; Lanyun Yan (Molecular Neurobiology, 2025)

Knocking Down HN1 Blocks Helicobacter pylori-Induced Malignant Phenotypes in Gastric Mucosal Cells and Inhibits Gastric Cancer Cell Proliferation, Cytoskeleton Remodeling, and Migration - Ying Huang; Xiaofei Wang; Hao Liu; Xiangkun Meng; Hua Yin; Ruirui Hou; Wan Lin; Xu Zhang; Jun Ma; Xiaoxu Zhang; Feixiong Zhang; Yu Miao (Biochemical Genetics, 2025)

Dual-CycleGANs with Dynamic Guidance for Robust Underwater Image Restoration - Yu-Yang Lin; Wan-Jen Huang; Chia-Hung Yeh (Journal of Marine Science and Engineering, 2025)
The field of underwater image processing has gained significant attention recently, offering great potential for enhanced exploration of underwater environments, including applications such as underwater terrain scanning and autonomous underwater vehicles. However, underwater images frequently face challenges such as light attenuation, color distortion, and noise introduced by artificial light sources. These degradations not only affect image quality but also hinder the effectiveness of related application tasks. To address these issues, this paper presents a novel deep network model for single under-water image restoration. Our model does not rely on paired training images and incorporates two cycle-consistent generative adversarial network (CycleGAN) structures, forming a dual-CycleGAN architecture. This enables the simultaneous conversion of an underwater image to its in-air (atmospheric) counterpart while learning a light field image to guide the underwater image towards its in-air version. Experimental results indicate that the proposed method provides superior (or at least comparable) image restoration performance, both in terms of quantitative measures and visual quality, when compared to existing state-of-the-art techniques. Our model significantly reduces computational complexity, resulting in a more efficient approach that maintains superior restoration capabilities, ensuring faster processing times and lower memory usage, making it highly suitable for real-world applications.

Metabolomics Revealed Cadmium Exposure Associated with Alterations in Serum Metabolism in Children - Miaoqian Li; Ping Wan; Lichun Qiao; Xinyue Wen; Huan Deng; Xue Lin; Jingke Lei; Jing Han (Biological Trace Element Research, 2025)

Homemade isothermal amplification-initiated Cas14a assay for rapid quantitative detection of aquatic RNA virus gene with no PAM - Xiufen Yang; Lin Lu; Yanchi Luo; Qingwei Wang; Jianing Wang; Yihua Ren; Yuwei Wu; Masoud Negahdary; Khaydar E. Yunusov; Sherzod A. Yuldoshov; Abdushkur A. Sarimsakov; Haimei Mao; et al. (Aquaculture, 2025)

New insights of 4-Methylesculetin in alleviating the effect of aflatoxin B1 on flesh quality of grass carp (Ctenopharyngodon idella) - Xiang-Ning He; Jia-Jia Zhang; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; He-Qun Shi; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Establishment of appropriate conditions for the efficient determination of multiple mycotoxins in tea samples and assessment of their drinking risks - Ying-Chun Wan; Zwe-Lin Kong; Yi-Hsieng Samuel Wu; Chien-Ni Huang; Tomohisa Ogawa; Jau-Tien Lin; Deng-Jye Yang (Food Chemistry, 2025)

3,5-Dicaffeoylquinic acid promotes intestinal urate excretion via the MAPK signaling pathway based on Caco-2 Cell model - Jiajing Liao; Jin Qian; Lijuan Rao; Suqin Lin; Chen Wang; Linqian Xu; Bing Yuan; Jiayi Yuan; Yin Wan; Guiming Fu (Food Bioscience, 2025)

Metal/organic interface carrier quenching suppression for stable and efficient near-infrared quantum dot light-emitting diodes - Wan-Shan Shen; Yang Liu; Xingtong Chen; Hong-Wei Duan; Jia-Lin Pan; Zhong-Da Zhang; Feng Zhao; Zeke Liu; Sui-Dong Wang; Wanli Ma; Song Chen; Ya-Kun Wang; et al. (Chemical Engineering Journal, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

Isomerase and epimerase: overview and practical application in production of functional sugars - Liqun Jin; Qing Wan; Shuiping Ouyang; Lin Zheng; Xue Cai; Xiaojian Zhang; Jidong Shen; Dongxu Jia; Zhiqiang Liu; Yuguo Zheng (Critical Reviews in Food Science and Nutrition, 2024)

Design and experimental analysis of real-time detection system for The seeding accuracy of rice pneumatic seed metering device based on the improved YOLOv5n - He Xing; Yikai Wan; Peng Zhong; Junjiang Lin; Mingtao Huang; Ru Yang; Ying Zang (Computers and Electronics in Agriculture, 2024)

Carbon chain elongation characterizations of electrode-biofilm microbes in electro-fermentation - Wei-Tong Ren; Zi-Lin He; Yang Lv; Hua-Zhe Wang; Lin Deng; Shan-Shan Ye; Juan-Shan Du; Qing-Lian Wu; Wan-Qian Guo (Water Research, 2024)

Potato Protein Hydrolysate (PPH902) treatment in adipocytes inhibits lipogenesis by activating AMPK - Yi-Ju Chen; Ching-Fang Chang; Rathinasamy Baskaran; Chih-Hung Liang; Hsin-Ning Kuo; Mosleh Mohammad Abomughaid; Wan-Teng Lin (South African Journal of Botany, 2024)

Can digital technology adoption promote environmental innovation in small and medium-sized enterprises (SMEs)? Evidence from China - Huanyong Ji; Lei Lin; Jun Wan; Jiyuan Zang (Science of The Total Environment, 2024)

Cd indirectly affects the structure and function of plankton ecosystems by affecting trophic interactions at environmental concentrations - Zhendong Jiang; Xuhao Wan; Xue Bai; Zhongzhi Chen; Lin Zhu; Jianfeng Feng (Journal of Hazardous Materials, 2024)

Effects of microplastics on soil physicochemical properties and vertical migration and transformation of chromium - Jia-li Li; Na-ying Li; Jia Ni; Rui-lin Wan; Jin-yan Yang (Journal of Environmental Chemical Engineering, 2024)

Surface in situ Co-Mn modification over LaMnO3 perovskite with enhanced activity for ethane combustion - Peng Zhao; Jingwei Liu; Wei Zhu; Jie Meng; Zhuang Li; Jinwei Qin; Xiaohui Wang; Haiqin Wan; Chao Yao; Lin Dong (Journal of Environmental Chemical Engineering, 2024)

Automatic extraction of Transverse Aeolian Ridges (TARs) and analysis of landform influence for the Zhurong landing area on Mars - Jie Zhang; Sicong Liu; Kecheng Du; Xiaohua Tong; Huan Xie; Yongjiu Feng; Yanmin Jin; Yizhang Lin; Bo Wan (Geomorphology, 2024)

Interface engineering of Platinum–Copper alloy/titanium dioxide for enhanced photocatalytic carbon dioxide reduction - Xin Wang; Wei Tan; Bo Peng; Shangcong Sun; Xue Li; Kaiqiang Wang; Jiawei Ji; Haohong Liao; Jingfang Sun; Qing Tong; Haiqin Wan; Lin Dong (Environmental Research, 2024)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

Association of PM2.5 exposure in early pregnancy and maternal liver function: A retrospective cohort study in Shenzhen, China - Zhijian Chen; Minting Zhu; Weigui Ni; Bo Wu; Tao Liu; Bingyi Lin; Lijuan Lai; Yi Jing; Long Jiang; Zhongai Ouyang; Jianxiong Hu; Haoqu Zheng; et al. (Environmental Research, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Peroxynitrite-Triggered Carbon Monoxide Donor Improves Ischemic Stroke Outcome by Inhibiting Neuronal Apoptosis and Ferroptosis - Xin-Jian Guo; Lin-Yan Huang; Shi-Tong Gong; Ming Li; Wan Wang; Jie Chen; Yi-De Zhang; Xicun Lu; Xiaohua Chen; Lan Luo; Youjun Yang; Xiao Luo; et al. (Molecular Neurobiology, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

Lactobacillaceae-mediated eye-brain-gut axis regulates high myopia-related anxiety: from the perspective of predictive, preventive, and personalized medicine - Yuze Mi; Ke Chen; Shaokai Lin; Luyao Tong; Jiawei Zhou; Minghui Wan (EPMA Journal, 2024)

Simulation of red mud/phosphogypsum-based artificial soil engineering applications in vegetation restoration and ecological reconstruction - Yong Liu; Lishuai Zhang; Binbin Xue; Li Chen; Guocheng Wang; Jingfu Wang; Hefeng Wan; Xiaohong Lin; Guangxu Zhu (Science of The Total Environment, 2024)

Insufficient FUNDC1-dependent mitophagy due to early environmental cadmium exposure triggers mitochondrial redox imbalance to aggravate diet-induced lipotoxicity - Cai-Yu Lian; Hui-Jia Li; Wei-Hao Xia; Yue Li; Xue-Lei Zhou; Du-Bao Yang; Xue-Mei Wan; Lin Wang (Environmental Pollution, 2024)

Moderate strategy for efficient recovery of rare earth elements from scintillation crystal waste - Hao Chen; Yucheng Liu; Xiaowen Zhou; Wenyi Zhang; Peihai Ju; Xiaoyu Zhong; Jiuyang Lin; Yinhua Wan; Xuewei Li (Chemical Engineering Journal, 2024)

Novel flow field design for redox flow battery using algorithmic channel generation and self-adaptive network model and experimental verification - Wei-Wei Yang; Ren-Zhong Zhang; Meng-Yue Lu; Yi-Wan Lin; Lan-Xin Liang; Qian Xu (Chemical Engineering Journal, 2024)

Enhanced performance of photocatalytic oxidation of indoor toluene over Pd/TiO2 catalyst by tuning surface defect concentrations - Gehui Wang; Cong Wu; Qinglong Liu; Haiqin Wan; Lin Dong (Chemosphere, 2024)

Heat acclimation alleviates the heat stress-induced impairment of vascular endothelial cells - Jirui Wen; Zhengdong Lin; Juan Cheng; Can Li; Ling Wang; Yuhao Zou; Xuehong Wan; Jifeng Liu; Jiang Wu (Tissue and Cell, 2024)

Partial dynamic ( u − p ) integrated model for both oscillatory and residual soil response in a poro-elastic seabed - Zhipeng Wan; Lin Cui; Dong-Sheng Jeng (Ocean Engineering, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Supplementation with a phenolic-rich fraction from Ilex kudingcha improves inflammatory stress, gastrocnemius weights, and foreleg muscle grip strength in murine squamous cell carcinoma (SCC7)-bearing mice - Han-Chen Chao; Wan-Li Yang; Li-Wha Wu; Jin-Yuarn Lin (Food Bioscience, 2024)

The role of aroA and ppk1 in Aeromonas veronii pathogenicity and the efficacy evaluation of mutant strain AV-ΔaroA/ppk1 as a live attenuated vaccine - Jiahui Lu; Wan'e Ding; Jinming Wei; Hua Ye; Hui Luo; Yun Li; Ying Lin; Yongyao Yu; Jiayun Yao; Ronghua Wu (Fish & Shellfish Immunology, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Sex-Specific Associations of Five Serum Essential Metal Elements with Thyroid Nodules in Euthyroid Adults: a Cross‑sectional Study - Qintao Ma; Ying Li; Genfeng Yu; Siyang Liu; Yuqi Jiang; Hualin Duan; Dongmei Wang; Yajun He; Xingying Chen; Nanfang Yao; Xu Lin; Heng Wan; et al. (Biological Trace Element Research, 2024)

Verification of Seasonal Prediction by the Upgraded China Multi-Model Ensemble Prediction System (CMMEv2.0) - Jie Wu; Hong-Li Ren; Jianghua Wan; Jingpeng Liu; Jinqing Zuo; Changzheng Liu; Ying Liu; Yu Nie; Chongbo Zhao; Li Guo; Bo Lu; Lijuan Chen; et al. (Journal of Meteorological Research, 2024)

Characterization of the novel bequatrovirus vB-BcgM and its antibacterial effects in food matrices - Yunfei Gong; Lin Sun; Xiaofu Wan; Peiling Geng; Xiaomin Hu (Archives of Virology, 2024)

Toll-like receptor expression in Pacific white shrimp (Litopenaeus vannamei) reveals differential responses after fungal (Fusarium solani) infection - Yusuf Jibril Habib; Chengjie Yao; Haifu Wan; Jiaming Lin; Hui Ge; Akram Ismael Shehata; Mayada Alhoshy; Muhammad Mohsin; Yilei Wang; Ziping Zhang (Aquaculture International, 2024)

Silicon balance in an integrated multi-tropical aquaculture ecosystem, Sanggou Bay, China - Ruihuan Li; Zengjie Jiang; Fan Lin; Yitao Zhang; Weixin Wang; Kai Zhang; Weiwei Li; Dongjie Wan; Yazhou Shi (Frontiers in Marine Science, 2024)
Farmed aquaculture species play an important role in regulating nutrient cycles in farming systems. Compared with nitrogen and phosphorus, the role of farmed species in the silicon (Si) cycle remains poorly understood. To help reduce this uncertainty, we clarified the sources and sinks of silicate and quantified the Si pools in an aquaculture system in Sanggou Bay (SGB). The results showed that dissolved inorganic nutrient levels were significantly lower during the dry season than during the wet. Dissolved silicate (DSi) is a potential limiting factor for phytoplankton growth during spring, and phosphorus limitation occurs during summer. The budget results indicated that large amounts of nitrogen, phosphate (DIP), and DSi were buried in the sediment or transformed into other forms during both the wet and dry seasons. The nitrogen and DIP cycles were strongly influenced by bivalve excretion and farmed species harvesting; however, these processes had little impact on the Si cycle. Si availability depends on both external inputs and internal recycling. DSi was primarily supplied from the Yellow Sea, with a minor contribution from the river due to river discharge during spring. However, during summer, riverine inflow (accounting for 83% of the total influx) was the major DSi source followed by benthic flux (12%). Biogenic silica (BSi) burial efficiency in the sediment was estimated to be 78% during spring and 23% during summer. The BSi preservation efficiency in bivalves during spring was high (53%), leading to a higher Si retention than in river discharge. Bivalves biodeposition plays an important role in the Si burial process. We suggest that this high retention is essentially controlled by the biodeposition mechanism, which is directly controlled by the exotic suspension feeders. Bivalves have the potential to alter Si retention in the bay by producing large amounts of biodeposits and accelerating the silica cycle, which may lead to more carbon dioxide being absorbed by diatoms.

C 19 -diterpenoid alkaloids from Aconitum refractum var. circinatum - Zhen-Ling Wan; Min Zhang; Yan Xiao; Lin Chen; Jiang Xie; Shuai Huang; Xian-Li Zhou (Natural Product Research, 2024)

DEM-CFD coupling simulation and optimisation of rice seed particles seeding a hill in double cavity pneumatic seed metering device - He Xing; Xiaoman Cao; Peng Zhong; Yikai Wan; Junjiang Lin; Yu Zang; Guozhong Zhang (Computers and Electronics in Agriculture, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Vibration reduction and efficiency enhancement effects of twisted rudders in submarines under small rudder angle conditions - Di Zhang; Jin-ming Ye; Wan-li Yang; Yuan-run Wu; Jian-lin Shou (Ocean Engineering, 2024)

A culture-dependent analysis of anaerobic methylotrophs in oil reservoir systems - Lin-Yuan Huang; Yi-Fan Liu; Wan-Qi Qin; Shi-Yi Wang; Yuan-Hao Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

A remote-controlled portable workstation for highly sensitive and real-time chemiluminescent detection of cadmium - Shiyu Zeng; Haoyu Zhu; A.S.M. Muhtasim Fuad Sohan; Jun Liu; Xinhua Wan; Xiaodong Lin; Binfeng Yin (Food Chemistry, 2024)

Golden-flower fungus (Eurotiwm Cristatum) presents fungal flower aroma as well as accelerates the aging of white tea (Shoumei) - Wan Zhu; Su Zhou; Haowei Guo; Jiali Hu; Yanyan Cao; Yingxin Xu; Xingchen Lin; Baoming Tian; Fangyuan Fan; Shuying Gong; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Declined flesh quality resulting from niacin deficiency is associated with elevated glycolysis and impaired mitochondrial homeostasis in grass carp (Ctenopharyngodon idella) - Shun-Shi Sun; Lin Feng; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Xiao-Qiu Zhou; Pei Wu (Food Chemistry, 2024)

Transcriptomics to evaluate the influence mechanisms of ethanol on the ester production of Wickerhamomyces anomalus with the induction of lactic acid - Wenqin Cai; Yin Wan; Yanru Chen; Haowei Fan; Mengxiang Li; Shengwen Wu; Pei Lin; Tingting Zeng; Huibo Luo; Dan Huang; Guiming Fu (Food Microbiology, 2024)

Caspase-8 promotes NLRP3 inflammasome activation mediates eye development defects in zebrafish larvae exposed to perfulorooctane sulfonate (PFOS) - Lu-Yin Wu; Jing-Lin Zhang; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Wan-Ting He; Nanxiang Jin; Ye Dai; Wei Chi; Zejin Ou; Guang-Hui Dong; Li-Zi Lin (Environmental Pollution, 2024)

Thiophene-containing conjugated polymers modified Zn0.5Cd0.5S inorganic/organic S-scheme heterojunction for boosting photocatalytic hydrogen production coupled with benzyl alcohol oxidation - Lele Wei; Ru Song; Jiarui Song; Yaping Li; Yina Nie; Lin Liu; Jun Wan (Chemical Engineering Journal, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Boosting gas-phase radical reactions for efficient oxidative dehydrogenation of propane over boron-based macropore catalyst - Shuya Qian; Peiling Zhang; Xiaohong Xiao; Shaolong Wan; Zhaoxia Zhang; Shuai Wang; Yong Wang; Jingdong Lin (Chemical Engineering Journal, 2024)

Algal-mediated nitrogen removal and sustainability of algal-derived dissolved organic matter supporting denitrification - Huiqin Wan; Kangpeng Wang; Xianxin Luo; Chao Zhang; Kai Deng; Shusen Lin; Jingming Xie; Qi Luo; Xu Lei; Lin Ding (Bioresource Technology, 2024)

Nonlinear contributions of surface solar brightening to maize yield gains in the US Corn Belt - H. Zhao; H. Yang; T.J. Avenson; G.F. Sassenrath; MB. Kirkham; S.W. Welch; L. Zhang; N. Wan; A.M. Nelson; P. Gowda; X. Lin (Agricultural and Forest Meteorology, 2024)

Endothelial Cells Promote Pseudo-islet Function Through BTC-EGFR-JAK/STAT Signaling Pathways - Lin Wang; Jian Wan; Yang Xu; Yan Huang; Dongzhi Wang; Donghui Zhu; Qiyang Chen; Yuhua Lu; Qingsong Guo (Annals of Biomedical Engineering, 2024)

New perspectives on the role of vitamin D in the mucosal barrier system of fish gills infected with Flavobacterium columnare - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Lu Zhang; Hai-Feng Mi; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2024)

The role of tissue-derived extracellular vesicles in tumor microenvironment - Jin Lin; Wan Lu; Bo Huang; Weiming Yang; Xiaozhong Wang (Tissue and Cell, 2024)

Emamectin benzoate exposure induced carp kidney injury by triggering mitochondrial oxidative stress to accelerate ferroptosis and autophagy - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Pesticide Biochemistry and Physiology, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Experimental investigation into coal wettability changes caused by reactions with scCO2-H2O - Ke Li; Chuanjie Zhu; Jiamin Wan; Tetsu K. Tokunaga; Na Liu; Cong Ma; Baiquan Lin (Gas Science and Engineering, 2024)

Effects of microbial electrolysis cell on anaerobic digestion of food waste: Acidification and recovery - Benyi Xiao; Xindong Wang; Eerdunmutu He; Yanxin Zuo; Liguo Wan; Lin Li (Fuel, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Water management and performance enhancement in proton exchange membrane fuel cell through metal foam flow field with hierarchical pore structure - Yun Sun; Yixiong Lin; Zhongmin Wan; Qinglian Wang; Chen Yang; Wang Yin; Ting Qiu (Chemical Engineering Journal, 2024)

Feedback of chain elongation microorganisms on iron-based conductive materials: Enhanced microbial functions and biotoxicity adaptation mechanisms - Wei-Tong Ren; Yang Lv; Zi-Lin He; Hua-Zhe Wang; Lin Deng; Shan-Shan Ye; Qing-Lian Wu; Wan-Qian Guo (Bioresource Technology, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

TAG encodes an adenine nucleotide transport protein that regulates leaf color in rice - Xinfang Zhang; Wenwen Xiao; Mi Wei; Ruhui Wu; Jinyan Liu; Jing You; Jianyan Mu; Jichao Zhang; Yanling Yang; Yitao Wan; Yinghua Lin; Guanghua He; et al. (Euphytica, 2024)

Correction to: The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2024)

Caspase-12 is Expressed in Purkinje Neurons and Prevents Psychiatric-Like Behavior in Mice - Lin-Yan Huang; Yi-Ning Liu; Jie Chen; Hai-Xue Zhu; Li-Li Li; Zhi-Yan Liang; Jin-Xiu Song; Yu-Jie Li; Zhao-Li Hu; Dieter Demon; Andy Wullaert; Wan Wang; et al. (Molecular Neurobiology, 2024)

Norditerpenoid alkaloids from Aconitum refractum var. circinatum as autophagy inducers - Mei-Zhen Ye; Zhen-Ling Wan; Hong-Yu Ruan; Yu-Qi Yang; Ying Chen; Lin Chen; Shuai Huang; Xian-Li Zhou (Phytochemistry, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Electron-transferring flavoprotein and its dehydrogenase contributed to growth development and virulence in Beauveria bassiana - Dongmei Lin; Min Wan; Yanhua Fan (Journal of Invertebrate Pathology, 2024)

Pb isotopic fingerprinting of uranium pollution: New insight on uranium transport in stream-river sediments - Jin Wang; Haiyao Hu; Ke Lin; Xudong Wei; Jingzi Beiyuan; Xinni Xiong; Yuebing Wan; Pengyuan Deng; Hanyu Wu; Mingliang Kang; Juan Liu; Xuhui Dong (Journal of Hazardous Materials, 2024)

Dynamic changes and the effects of key procedures on the characteristic aroma compounds of Lu’an Guapian green tea during the manufacturing process - Jieyao Yu; Jingzhe Li; Zhi Lin; Yin Zhu; Zhihui Feng; Dejiang Ni; Shengchun Zeng; Xuehong Zeng; Yijun Wang; Jingming Ning; Liang Zhang; Xiaochun Wan; et al. (Food Research International, 2024)

An untargeted metabolomics study of cardiac pathology damage in rats caused by low selenium diet alone or in combination with T-2 toxin - Xue Lin; Lichun Qiao; Haobiao Liu; Miaoye Bao; Huan Deng; Lianxu Jia; Xinyue Wen; Feidan Deng; Ping Wan; Yizhen Lyu; Jing Han (Food and Chemical Toxicology, 2024)

Electrospun multi-functional medicated tri-section Janus nanofibers for an improved anti-adhesion tendon repair - Lin Xu; Qisheng Li; Haibing Wang; Hui Liu; Deng-Guang Yu; Sim-Wan Annie Bligh; Xuhua Lu (Chemical Engineering Journal, 2024)

Selective amination of furfuryl alcohol to furfurylamine over nickel catalysts promoted by alumina encapsulation - Yuqing Wei; Hao Wang; Yingxue Qin; Yafei Hu; Jingdong Lin; Shaolong Wan; Shuai Wang (Chemical Engineering Journal, 2024)

Nitrogen aerosols in New Delhi, India: Speciation, formation, and sources - Qiaomin Pei; Xin Wan; David Widory; Kirpa Ram; Bhupesh Adhikary; Guangming Wu; Xing Diao; Hemraj Bhattarai; Yan-Lin Zhang; Mark Loewen; Zhiyuan Cong (Atmospheric Research, 2024)

High intra-patient variability of tacrolimus within post-operative 1 month predicted worse 1-year outcomes in pediatric liver transplant recipients - Fang Chen; June-Kong Yong; Chuan Shen; Tao Zhou; Mingxuan Feng; Ping Wan; Yi Luo; Houwen Lin; Yongbing Qian; Qiang Xia (European Journal of Clinical Pharmacology, 2024)

The Association Between Dietary Magnesium Intake with Chronic Obstructive Pulmonary Disease and Lung Function in US Population: a Cross-sectional Study - Zhi-Feng Lin; Hua-Wei Lin; Wan-Zhe Liao; Ze-Min Huang; Xiao-Yue Liao; Yi-Yao Wang; Xu-Guang Guo (Biological Trace Element Research, 2024)

Exploring mycorrhizal diversity in sympatric mycoheterotrophic plants: a comparative study of Monotropastrum humile var. humile and M. humile var. glaberrimum - Ren-Cheng Liu; Wan-Rou Lin; Pi-Han Wang (Mycorrhiza, 2024)

Confined Compressibility of Fine-Grained Marine Sediments with Cavities after Complete Dissociation of Noduled Natural Gas Hydrates - Lei Yang; Lele Liu; Tao Liu; Jinbo Lin; Yizhao Wan; Yongchao Zhang; Zhihui Wang; Xiang Liu (Journal of Marine Science and Engineering, 2024)
Due to natural and anthropogenic disturbances, natural gas hydrates with morphologies of nodules and chunks dissociate and release massive free gas, creating large cavities within fine-grained marine sediments. However, it is still a challenge to quantify the impact of gas cavities on mechanical properties of cavitied fine-grained marine sediments as there is a lack of efforts focusing on the inner structure visualization. In this study, an oedometer test and X-ray computed tomography scans are jointly conducted on marine clayey silt with gas cavities, and the confined compressibility as well as the inner structure change under an undrained condition are explored, followed by development of a theoretical model depicting the void ratio change. The results show that vertical loading induces a void ratio reduction, and the reduced void ratio can fully recover after being unloaded. Although being fully recovered, unrecovered changes of the inner structure still remain after being unloaded. Examples include closed cracks in the lower matrix, new occurring cracks in the upper matrix, and the fragmented gas cavity. In addition, the void ratio linearly increases with the increasing inverse of normalized pore gas pressure, while the coefficient of the effective stress linearly decreases with the increasing inverse of normalized vertical loading stress. The proposed theoretical model captures the essential physics behind undrained confined deformation of fine-grained marine sediments with gas cavities when subjected to loading and unloading.

Thermal infrared hyperspectral image band selection based on dynamic metric-guided particle swarm optimization for quantitative analysis of potash - Liqin Cao; Lin Gao; Yuting Wan; Xuan Zhang; Lyuzhou Gao; Yanfei Zhong (International Journal of Remote Sensing, 2024)

Sunlight enhanced the formation of tribromomethane from benzotriazole degradation during the sunlight/free chlorine treatment in the presence of bromide - Ming-Chi Hsieh; Wan-Ning Lee; Yi-Hsuan Chu; Hank Hui-Hsiang Lin; Angela Yu-Chen Lin (Chemosphere, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Therapy of liver fibrosis: From conventional approaches to nanomaterials delivery systems - Lin Chen; Yu Duan; Tingting Jiang; Chun Mao; Xinhua Zhu; Mimi Wan (Science Bulletin, 2024)

A comprehensive study combing experiment and CFD simulation on the fume hood performance for nanoparticles and isopropanol control - Guan-Yu Lin; Yi-Ming Lee; Bo-Wen Chiu; Hsuan-Yu Hsu; Chuen-Wan Chen; Chuen-Jinn Tsai (Process Safety and Environmental Protection, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Characteristics and formation of rare-metal pegmatites and granites in the Duanfengshan-Guanyuan district of the northern Mufushan granite complex in South China - Lu Zhang; Shao-Yong Jiang; Rolf L. Romer; Hao-Xiang Zhang; Song-Lin Wan (Lithos, 2024)

Formation mechanism of polycyclic aromatic hydrocarbons during mineral oil pyrolysis: A ReaxFF molecular dynamics study - Linlin Xu; Gan Wan; Lushi Sun; Li Lin (Fuel, 2024)

Identification of toll-like receptor family and the immune function of new Sptlr-6 gene of Scylla paramamosain - Bohao Peng; Jiaming Lin; Haifu Wan; Pengfei Zou; Ziping Zhang; Yilei Wang (Fish & Shellfish Immunology, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

From theory to practice: Dissociation of AsMA under reactive metal perturbations for the harmlessness and resourcefulness of copper slag - Xingyuan Wan; Kaixi Jiang; Ting'an Zhang; Kun Wang; Han Yang; Shengnan Lin (Chemical Engineering Journal, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

Environmental Flow Increases The Riparian Vegetation Diversity And Community Similarity - Min Guo; Wan-Lai Xue; Chen Wang; Wen-Zhong Li; He Gao; Neil Saintilan; Cheng-Lin Li; Geng Huang; Yu-Yu Wang (Wetlands, 2024)

Arbuscular mycorrhizal fungal diversity associated with an endangered species, Chamaecyparis formosensis, in the nature habitat - Tzu-Chao Lin; Wan-Rou Lin; Lei-Chen Lin; Pi-Han Wang (Tropical Ecology, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Spatially confined CuFe2O4 nanosphere in N/O-codoped porous carbon mimetics for triple-mode sensing of antibiotics and visual detection of neurotransmitters in biofluids - Ying Lin; Wan-Wan Shao; Dan Wu; Tong Zhang; Dan-Ni Fei; Ya-Nan Kong; Yi-Fan Gao; Shu-Chang Zhao; Rui-Lin Liu (Analytica Chimica Acta, 2024)

PARP-2 mediates cardiomyocyte aging and damage induced by doxorubicin through SIRT1 Inhibition - Chaoming Huang; Xuan Zhang; Shulin Wang; Ao Shen; Tianfen Xu; Yanhong Hou; Shuhan Gao; Yongwan Xie; Yi Zeng; Jiayu Chen; Runxiang Lin; Yu Zhang; et al. (Apoptosis, 2024)

Remediation of cadmium-contaminated soil using modified activated carbon fiber combined with electrodynamic remediation technology - Dao-lin Zhou; Yue Cheng; Yu-shan Wan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Relative prevalence of top-down versus bottom-up control in planktonic ecosystem under eutrophication and climate change: A comparative study of typical bay and estuary - Xuhao Wan; Xueqiang Lu; Lin Zhu; Jianfeng Feng (Water Research, 2024)

Enhanced photodegradation of pentafluoropropionic acid (PFPA) via TiO2-synthetic zeolite composites: A sustainable approach for effective defluorination - Subham Halder; Feng-Chih Chou; Tsz-Kin Wan; Yi-Tien Tsai; Pei-Cheng Cheng; Yuan-Chung Lin (Journal of Water Process Engineering, 2024)

Novel activated NIR-II fluorescence/Ratio photoacoustic probe for dual-modality accurate imaging of palladium ions overload in mouse liver - Huayong Zhu; Wenxiu Li; Sixin Ai; Yang Wan; Weiying Lin (Journal of Hazardous Materials, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Tracking the changes of dissolved organic matter throughout the city water supply system with optical indices - Jinjin Lin; Liyang Yang; Wan-E Zhuang; Yue Wang; Xiaochen Chen; Jia Niu (Journal of Environmental Management, 2024)

3D-printed Al2O3 framework supported carbon-bridged tri-s-triazine of g-C3N4 for photocatalytic tetracycline oxidation - Chechia Hu; Lee-Lee Chang; Wei Chen; Wan-Yuan Hsu; Szu-Chia Chien; Chien-Hua Chen; Yu-Ting Lin; Tzu-Jung Hsu; Kuo-Lun Tung (Chemical Engineering Journal, 2024)

Interspecific occupancy-abundance relationship of benthic diatoms changes seasonally with attachment mode in a tropical river - Lin Tan; Yuting Liu; Muqi Shen; Guifeng Wei; Linglin Wan; Quehui Tang; Bo-Ping Han (Hydrobiologia, 2024)

Higher stochasticity in comammox Nitrospira community assembly in upland soils than the adjacent paddy soils at a regional scale - Mengmeng Feng; Yongxin Lin; Zi-Yang He; Hang-Wei Hu; Shengsheng Jin; Jia Liu; Song Wan; Yuheng Cheng; Ji-Zheng He (Science of The Total Environment, 2024)

Microplastics and cadmium affect invasion success by altering complementarity and selection effects in native community - Feng He; Jianfan Sun; Justin S.H. Wan; Mohsin Nawaz; Qaiser Javed; Linxuan Pan; Wajid Ali Khattak; Yanwen Bo; Yan Xiang; Guangqian Ren; Xin Lin; Daolin Du (Science of The Total Environment, 2024)

Heavy metal migration dynamics and solid-liquid distribution strategy in abandoned tailing soils - Bohan Wu; Quan Wan; Xiao Li; Shukun Lin; Yanqi Jiang; Xu Yang; Jingjing Li; Qingqi Lin; Jean Louis Morel; Rongliang Qiu (Journal of Hazardous Materials, 2024)

Highly water-soluble and biocompatible hyaluronic acid functionalized upconversion nanoparticles as ratiometric nanoprobes for label-free detection of nitrofuran and doxorubicin - Abdur Raheem Aleem; Rihui Chen; Tonghua Wan; Wei Song; Chuyan Wu; Xue Qiu; Qiuqiang Zhan; Kuncheng Xu; Xin Gao; Tianci Dong; Xiang Chen; Lin Yu; et al. (Food Chemistry, 2024)

Dynamic changes of zinc chemical speciation and zinc-containing peptides release in oysters (Crassostrea hongkongensis) during enzymatic hydrolysis - Ran Du; Wan Li; Jiawei Li; Shan Zeng; Zhongqin Chen; Jialong Gao; Huina Zheng; Haisheng Lin; Guoping Zhu; Xiaoming Qin; Wenhong Cao (Food Bioscience, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

MnO2 nanozyme with lanthanide-based radiosensitization for advanced radiotherapy by tumor microenvironment triggering STING pathway activation - Meiling Tan; Zhimin Gao; Xiaozhao Wang; Chen Lin; Yuchi Wan; Wenyu Xie; Wei Chen; Yaru Zhang; Zewei Quan; Zhiyao Hou (Chemical Engineering Journal, 2024)

Integration of bulk-surface charge polarization and active site manipulation for highly efficient photocatalytic aerobic oxidation of sulfides - Jun Wan; Yang-Ai Ma; Yina Nie; Junhao Cheng; Chengming Wang; Lin Liu; Feng Fu (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Dynamic changes in butyrate levels regulate satellite cell homeostasis by preventing spontaneous activation during aging - Shujie Chen; Liujing Huang; Bingdong Liu; Huimin Duan; Ze Li; Yifan Liu; Hu Li; Xiang Fu; Jingchao Lin; Yinlan Xu; Li Liu; Dan Wan; et al. (Science China Life Sciences, 2024)

Rhaponticin suppresses the hypoxia-induced factor-1 alpha-mediated aggressive phenotype of tongue squamous cell carcinoma - Yuan Wu; Xiaowen Wan; Yisen Shao; Wei Wang; Wenquan Huang; Jiajun Zhu; Lin Jiang (Molecular & Cellular Toxicology, 2024)
Background Emerging evidence suggests that rhaponticin, a stilbene monomeric compound isolated from North China rhubarb, has been shown to exhibit significant biological activity against tumors. However, the anticancer effects and mechanisms of rhaponticin in tongue squamous cell carcinoma (TSCC) remain elusive. Objective We investigated the changes of migration and invasion abilities and EMT progression of TSCC cells treated with different concentrations of rhaponticin under hypoxia, as well as the possible mechanisms, in order to initially explore the effects of rhaponticin on the biological characteristics of TSCC cells under hypoxia. Results The number of cell migration and invasion was prominently increased, E-cadherin protein was down-regulated, and N-cadherin and HIF-1α protein expression was elevated under hypoxia. Rhaponticin intervention strikingly prevented the increased abilities of migration and invasion and EMT of TSCC cells under hypoxia. This was followed by further validation finding that rhaponticin indeed leads to reduced HIF-1α post-transcriptional activity. Mechanistically, rhaponticin may bind to aryl-hydrocarbon nuclear translocator (ARNT) domain of HIF-1α. Conclusions Rhaponticin repressed the invasion and migration abilities and EMT process of TSCC cells under a hypoxic environment in vitro by targeted suppression of HIF-1α.

Identification, Characterization, and Probiotic Potentials of Lactobacillus pentosus SF-1 - Lin Jiao; Shufei Liang; Ruixia Chu; Wentao Wang; Kangsen Mai; Ming Liu; Min Wan (Journal of Ocean University of China, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Di-(2-ethylhexyl) phthalate exposure induces premature testicular senescence by disrupting mitochondrial respiratory chain through STAT5B-mitoSTAT3 in Leydig cell - Haiming Cao; Qigen Xie; Peng Luo; Jiaqi Chen; Kai Xia; Lin Ma; Demeng Chen; Chunhua Deng; Zi Wan (GeroScience, 2024)

New perspectives on the mechanism of curcumin in the gill mucosal immune barrier damaged by ochratoxin A in juvenile grass carp (Ctenopharyngodon idella) - Piao Zhao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; He-Qun Shi; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2024)

Enhancing urban climate resilience: A holistic evaluation of urban forest disservices in the aftermath of typhoons - Wan-Yu Liu; Chen-Rui Liu; Chun-Cheng Lin (Urban Climate, 2024)

Identifying the source and fate of boron in geothermal water: Evidence from B/Na and B isotopes - Ying Tan; Xiao-Wei Jiang; Tao-Tao Ji; Yin-Fei Luo; Wan Dai; Hong Zhang; Zhao-Xuan Niu; Yu-De Lei; Zhi-Yuan Zhang; Tian-Yi Lin; Hua-Ming Guo (Science of The Total Environment, 2024)

Origin and geological significance of the first discovered seafloor oil seepage in the Beikang Basin, southern South China Sea - Wei Huang; Hongfei Lai; Zhifeng Wan; Wei Zhang; Miaomiao Meng; Jiujing Shang; Jinqiang Liang; Mengjie Xu; Lin Lin (Journal of Asian Earth Sciences, 2024)

Unraveling metabolic fate of a veterinary antibiotic thiamphenicol via the multi-omic approach - Jiayu Zhang; Fangliang Guo; Hebin Liang; Ke Yu; Wan Cai; Lin Lin; Xiaoyan Li; Bing Li (Chemical Engineering Journal, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

An Intriguing Structural Modification in Neutrophil Migration Across Blood Vessels to Inflammatory Sites: Progress in the Core Mechanisms - Zexu Wang; Yufang Guo; Yulei Zhang; Liangquan Wu; Li Wang; Qiuqi Lin; Bing Wan (Cell Biochemistry and Biophysics, 2024)

Microbiota-mediated metabolic perturbations in the gut and brain of mice after microplastic exposure - Sheng-Han Lee; Wan-Yu Lin; Tsun-Jen Cheng (Chemosphere, 2024)

The improved resistance of germinated spores to ultraviolet irradiation: Comparison with chlorine - Ruihua Cao; Lili Tan; Qiqi Wan; Gehui Wu; Jingyi Wang; Yingzi Lin; Tinglin Huang; Gang Wen (Chemosphere, 2024)

Immunomodulation of potassium diformate in juvenile grass carp (Ctenopharyngodon idella) after Aeromonas hydrophila infection: T-cell differentiation and cytokine production - Qiu-Ping Chai; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2024)

A metallic phenolic network-enhanced bentonite for ammonical nitrogen removal from black-odorous water - Jialin Lin; Baihua Luo; Peng Wan; Jian Wang; Andrew S. Hursthouse; Si Li; Guocheng Zhu (Process Safety and Environmental Protection, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Electrosynthesis of peracetic acid using in-situ generated H2O2 enabled by carbon-based bifunctional electrodes - Zeheng Lin; Felice; George E.P. O'Connell; Tao Wan; Ding Zhang; Lingyi Peng; Dewei Chu; Xunyu Lu; Zhaojun Han (Chemical Engineering Journal, 2024)

Quantitative evaluation of the impact of hydrological forecasting uncertainty on reservoir real-time optimal operation - Feilin Zhu; Yaqin Wang; Bojun Liu; Qing Cao; Mingyu Han; Yurou Zeng; Meiyan Lin; Lingqi Zhao; Xinrong Wang; Zhiqi Wan; Ping-an Zhong (Stochastic Environmental Research and Risk Assessment, 2024)

A Spleen Tyrosine Kinase’s Sky in Neuronal Degeneration - Wan-Yun Zhang; Sen Lin (Neuroscience Bulletin, 2024)

The source of rock moisture in a sandstone cave in arid northern China: rainfall infiltration or vapor condensation? - Xiao-Wei Jiang; Kai-Gao Ouyang; Xu-Lin Tang; Shu-Cong Tan; Jia-Xin Shi; Na Li; Hong-Bin Yan; Jian-Guang Ren; Li Wan (Hydrogeology Journal, 2024)

Region and cloud regime dependence of parametric sensitivity in E3SM atmosphere model - Yun Qian; Zhun Guo; Vincent E. Larson; L. Ruby Leung; Wuyin Lin; Po-Lun Ma; Hui Wan; Hailong Wang; Heng Xiao; Shaocheng Xie; Ben Yang; Kai Zhang; et al. (Climate Dynamics, 2024)
The Department of Energy (DOE)’s Energy Exascale Earth System Model (E3SM), including its atmosphere model (EAM), has many relatively new features. In a previous study we conducted a systematic parametric sensitivity analysis for EAM based on short, perturbed parameter ensemble (PPE) simulations, mainly focusing on global mean climate features and metrics. While parameter values in global climate models are generally invariant in space and time, model response to parameters perturbation may vary by regions and climate regimes, which motivates the need to better understand the EAM model behaviors and physics at regional scale and process level. In this study, using the same set of PPE simulations and a similar sensitivity analysis framework, we identify parameters that cause largest sensitivities over different regions and compare model responses in fast atmospheric processes to the parameters across different cloud regimes for several important cloud-related fidelity metrics. We find that cloud forcing has opposite response to some parameters over mid-latitude vs. tropical land. We also analyze how the parametric sensitivity varies as stratocumulus transitions to shallow convection and to deep convection over ocean. Low cloud forcing and shortwave cloud forcing in the subtropical eastern Pacific are most sensitive to the parameters controlling the width of the probability density function (PDF) of the subgrid vertical velocity ( w’ ) ( gamma ) and the damping of the w’ skewness ( c8 ) near the coast but become more sensitive to the parameter affecting the damping of the w’ variance ( c1 ) further offshore. Detailed interpretation of the spatial dependence of parametric sensitivity is provided. We also investigate how the parametric sensitivity evolves with prediction duration. This study improves our process-level understanding of cloud physics and parameterization and provides insights for developing more advanced regime-aware parameterization schemes in global climate model.

Human milk oligosaccharides and the association with microbiota in colostrum: a pilot study - Wen Sun; Lin Tao; Chen Qian; Peipei Xue; Xiankun Tong; Li Yang; Fang Lu; Hua Wan; Yingna Tao (Archives of Microbiology, 2024)
HMOs (Human milk oligosaccharide) has an impact on maternal and infant health. Colostrum samples of 70 breastfeeding women in China were collected and recorded clinical characteristics. The major oligosaccharides and microbiota were quantitated in colostrum. The concentration of fucosylated HMOs in primipara was higher than that of multipara ( p = 0.030). The concentration of N-acetylated HMOs in vaginal delivery milk was less than that of cesarean ( p = 0.038). Non-fucosylated HMOs of breastfeeding women were less than that of breast pump ( p = 0.038). Meanwhile, the concentration of LNT was positively correlated with Lactobacillus ( r = 0.250, p = 0.037). DS-LNT was negatively correlated with Staphylococcus ( r = – 0.240, p = 0.045). There was a positive correlation of Streptococcus with LNFP II ( r = 0.314, p = 0.011) and 3-SL ( r = 0.322, p = 0.009). In addition, there was a negative correlation between 2'-FL and 3-FL ( r = – 0.465, p = 0.001). There was a positive correlation between LNT and LNnT ( r = 0.778, p = 0.001). Therefore, the concentration of HMOs is related to number of deliveries, delivery mode, lactation mode and perinatal antibiotic. The concentration of HMOs is related to Lactobacillus , Streptococcus and Streptococcus in colostrum. In addition, there are connections between different oligosaccharides in content. The study protocol was also registered in the ClinicalTrails.gov (ChiCTR2200064454) (Oct. 2022).

Spatiotemporal distribution, source analysis and ecological risk assessment of polychlorinated biphenyls (PCBs) in the Bohai Bay, China - Shan Jiang; Mengmeng Wan; Kun Lin; Yanshan Chen; Rui Wang; Liju Tan; Jiangtao Wang (Marine Pollution Bulletin, 2024)

Insights into the influence and mechanism of biomass substrate and thermal conversion conditions on FeN doped biochar as a persulfate activator for sulfamethoxazole removal - Yining Lin; Qiang Ge; Jinquan Wan; Yan Wang; Congyun Zhu (Science of The Total Environment, 2024)

Enhanced humus synthesis from Chinese medicine residues composting by lignocellulose-degrading bacteria stimulation: Upregulation of key enzyme activity and neglected indirect effects on humus formation - Chuan-Ming Xing; Zi-Lin He; Tian Lan; Bo Yan; Qi Zhao; Qing-Lian Wu; Hua-Zhe Wang; Cai-Xia Wang; Wan-Qian Guo (Science of The Total Environment, 2024)

Water rather than nitrogen availability predominantly modulates soil microbial beta-diversity and co-occurrence networks in a secondary forest - Jiayin Feng; Huixia Ma; Chunyu Wang; Jingjing Gao; Changchun Zhai; Lin Jiang; Shiqiang Wan (Science of The Total Environment, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Diverse Late Triassic arc magmatism and porphyry Cu deposits in the southeastern Tibetan Plateau: Related to slab tear along a subducting passive margin? - Wan-Li Tang; Jian-Lin Chen; Tian-Nan Yang; An Yin; Ji-Feng Xu; Jiang-Bo Ren (Lithos, 2024)

Electrochemically mediated phosphorus and energy recovery from digested effluent - Ling-ling Lai; Si-zhuo Wan; Mahmood Qaisar; Yi-fan Yang; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2024)

Eupatilin inhibits xanthine oxidase in vitro and attenuates hyperuricemia and renal injury in vivo - Guitao Xu; Lele Wu; Hongxuan Yang; Tianfeng Liu; Ying Tong; Jiliang Wan; Bin Han; Lin Zhou; Xuguang Hu (Food and Chemical Toxicology, 2024)

Fast ion/electron transport enabled by MXene confined bimetallic sulfides with heterostructure toward highly effective lithium/sodium storage - Yun-Lei Hou; Jing-Zhou Chen; Bo-Han Zhang; Hua-Ying Wang; Wan-Xin Wen; Dong-Lin Zhao (Chemical Engineering Journal, 2024)

Ammonium intercalation engineering regulated structural stability of V6O13 cathodes for durable zinc ion batteries - Ziang Wu; Jia Yao; Chi Chen; Xiang Chen; Xiaoxin Pan; Junjie Zheng; Yi Gan; Jingying Li; Xingtai Liu; Chao Xia; Lin Lv; Hao Wang; et al. (Chemical Engineering Journal, 2024)

A predictive model incorporating geomorphic factors for assessing the longevity of landslide-dammed lakes - Shao-Wei Wu; Wan-Yu Chan; Chao-Yuan Lin (Landslides, 2024)

Impact of Pacific–Japan pattern on temperature and heatwave events in summer over Taiwan - Wan‐Ling Tseng; Szu‐Ying Lin; Yi‐Chi Wang; Shih‐How Lo; Min‐Hui Lo; Shih‐Yu Lee; Chieh‐Ting Tsai; Huang‐Hsiung Hsu (International Journal of Climatology, 2023)
The prediction of heatwave events is vital to provide information on possible hazards caused by extremely high temperature. The Pacific–Japan (PJ) pattern is a significant climate variability that controls the summer climate over East Asia. Previous studies have reported that the meridional propagating wave structure associated with the PJ pattern can modulate summer temperature and heatwave characteristics over northeast Asian countries, such as Korea and Japan. Nevertheless, its impacts on the subtropical regions, including Taiwan, a mountainous subtropical island with an approximate population of 24 million, is not yet fully understood. In this study, we investigate the impacts of the PJ pattern on the summer temperature and heatwave characteristics in Taiwan on the interannual timescale using long‐term station‐based temperature and rainfall dataset. We found an island‐wide increase in temperature during the positive phase of the PJ pattern, which is characterized by an anticyclonic anomalous circulation over Taiwan. Meanwhile, the averaged effective area and frequency of heatwave extremes over Taiwan have increased significantly, indicating an increase of exposure to heatwaves. Our examinations of large‐scale environment suggest that the adiabatic warming due to subsidence anomaly associated with the anticyclone over Taiwan is primary contributor of surface warming, which is balanced by diabatic cooling and meridional advective cooling on a seasonal timescale. Our study consolidated the links between the PJ pattern as a climate driver, hot summers and increased summer heatwave events over Taiwan. By combining with the seasonal prediction systems and early warning systems, such understanding can help sectors that are vulnerable to heat stress to prepare for potential hazards.

Disruption of sex steroid hormones biosynthesis by short-term enrofloxacin antibiotic exposure in Carassius auratus var. Pengze - Jiming Ruan; Gen Wan; Zhen Lin; Jianzhen Huang; Xiaochen Tang; Huazhong Liu (Chemosphere, 2023)

Fragmentation of continental subduction is ending the Himalayan orogeny - Xiaofeng Liang; Yang Chu; Bo Wan; Ling Chen; Lin Chen; Eric Sandvol; Stephen P. Grand; Yibing Li; Minling Wang; Xiaobo Tian; Yun Chen; Tao Xu; et al. (Science Bulletin, 2023)

Thickness-variation-insensitive near-infrared quantum dot LEDs - Wan-Shan Shen; Yang Liu; Luke Grater; So Min Park; Haoyue Wan; Yan-Jun Yu; Jia-Lin Pan; Fan-Cheng Kong; Qi-Sheng Tian; Dong-Ying Zhou; Zeke Liu; Wanli Ma; et al. (Science Bulletin, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

The 4 January 2020 offshore Pearl River Estuary earthquake sequence in South China: Implications for seismic potential of the NW-striking local faults - Shaohong Xia; Jiangnan Lin; Dapeng Zhao; Jinghe Cao; Changrong Zhang; Xinyang Wang; Kuiyuan Wan; Chaoyan Fan (Journal of Asian Earth Sciences, 2023)

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

Spatial distribution and migration of lead and zinc and the influence of parent materials in typical paddy soils of Hunan Province, China - Yi-fan Xiang; Da-juan Wan; Chen-ran Wang; Jun-lin Huang; Xue-ying Cao; Jia-qi Chen; Ning-xiang Ouyang (Environmental Monitoring and Assessment, 2023)

Diel Variation in Phytoplankton Biomass Driven by Hydrological Factors at Three Coastal Monitoring Buoy Stations in the Taiwan Strait - Cun Jia; Lei Wang; Youquan Zhang; Meihui Lin; Yan Wan; Xiwu Zhou; Chunsheng Jing; Xiaogang Guo (Journal of Marine Science and Engineering, 2023)
To investigate the diurnal variation in phytoplankton biomass and its regulating factors during the diurnal cycle, we conducted in situ observations in June 2018 at three buoy stations, including Douwei Buoy Station, Minjiang Estuary Buoy Station, and Huangqi Buoy Station on the western side of the Taiwan Strait. The calibration of buoy sensor data, including temperature, salinity, dissolved oxygen, pH, chlorophyll, and phycoerythrin, was conducted simultaneously. In addition, water sampling was conducted to measure chlorophyll a and phycoerythrin concentrations at hourly time intervals. The results showed that the 24 h cumulative chlorophyll a concentration order for the buoys was Minjiang Estuary (10.280 μg/L) > Huangqi (7.411 μg/L) > Douwei (4.124 μg/L). The Minjiang Estuary had a lower nighttime biomass proportion than Douwei and Huangqi. The diurnal variation in phytoplankton was jointly regulated by water masses, tides, and light. There were three response patterns, including the “light trumps tidal influences” pattern at Douwei, the “Low-tide, High-biomass” pattern at Minjiang Estuary, and the “High-tide, High-biomass” pattern at Huangqi. The prediction of algal blooms and hypoxia using buoy monitoring needs to be based on seasonal water mass background and tidal influence.

Deployment priority of public charging speeds for increasing battery electric vehicle usability - Wan Li; Zhenhong Lin; Shiqi(Shawn) Ou; Boyu Wang (Transportation Research Part D: Transport and Environment, 2023)

Effect of cavitation on fluid-structure interaction of a cantilever hydrofoil - Jian Hu; Xusheng Li; Jiangbo Zhu; Xiaoshen Ning; Qingyuan Wan; Changgang Lin (Ocean Engineering, 2023)

Propeller hydrodynamic excitation influenced by shafting whirling vibration considering different nonuniform inflow conditions: A numerical study - Chang-Lin Meng; Lie-Yi Dong; Dong-Hua Wang; Jia-Xuan He; Zhi-Jun Shuai; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Ocean Engineering, 2023)

Numerical analysis of wake field and unsteady forces on submarine propeller with twisted rudders - Jin-ming Ye; Di Zhang; Zi-han Zheng; Wan-li Yang; Lin Ke (Ocean Engineering, 2023)

Inspiration or perspiration: Diffusion of China's low-carbon city pilot policies nationwide - Xiang Luo; Guodong Lin; Qing Wan; Gui Jin (Journal of Cleaner Production, 2023)

Zero-valent iron-peroxydisulfate as synergistic co-milling agents for enhanced mechanochemical destruction of 2,4-dichlorophenol: Coupling reduction with oxidation - Ludi Song; Lvren Lin; Wenjia Wei; Shengkun Zhang; Lei Wan; Zimo Lou; Jianming Yu; Xinhua Xu (Journal of Environmental Management, 2023)

TBBPA and lead co-exposure induces grass carp liver cells apoptosis via ROS/JAK2/STAT3 signaling axis - Lu Li; Wan Li; Yufeng Liu; Xin Jin; Yanbo Yu; Hongjin Lin (Fish & Shellfish Immunology, 2023)

mitfa deficiency promotes immune vigor and potentiates antitumor effects in zebrafish - Wan-Ping Bian; Shao-Lin Xie; Chao Wang; Grigoriy G. Martinovich; Yan-Bo Ma; Pan-Pan Jia; De-Sheng Pei (Fish & Shellfish Immunology, 2023)

Quantifying the potential effects of air pollution reduction on population health and health expenditure in Taiwan - Yi-Hsuan Roger Chen; Wan-Chen Lee; Bo-Chen Liu; Po-Chieh Yang; Chi-Chang Ho; Jing-Shiang Hwang; Tzu-Hsuan Huang; Hsien-Ho Lin; Wei-Cheng Lo (Environmental Pollution, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Improvement of membrane-forming ability and separation performance of hydroxylated BN membrane by GO via π-π interaction - Lin-Lin Ye; Xi Chen; Yan Chen; Xi Yan; Xiao-Jing Guo; Wan-Zhong Lang (Desalination, 2023)

Fabrication of diamond/copper composite thin plate based on a single-layer close packed diamond particles network for heat dissipation - Jia-wan Peng; Feng-lin Zhang; Yu-mei Zhou; Ling-kang Xiong; Yao-jie Huang; Hong-qun Tang (Chemical Engineering Journal, 2023)

Thermally activated delayed fluorescence emitters with bulky four-coordinate boron acceptors for high-performance solution-processed OLEDs - Bowen Li; Zhenming Ding; Zhimin Wu; Meihua Liu; Shaofeng Chen; Dongcheng Chen; Zhigao Li; Long Sang; Yu Liu; Lili Lin; Weiguo Zhu; Xiaobo Wan (Chemical Engineering Journal, 2023)

ZnFexAl2-xO4 spinel supported PdZnβ bifunctional catalyst for methanol steam reforming - Lina Zhang; Jianhuang Wang; Baoquan Zhang; Zenan Lin; Lele Liu; Xianhua Zhang; Shuai Wang; Jingdong Lin; Haifeng Xiong; Chuanqiang Wu; Yong Wang; Shaolong Wan (Chemical Engineering Journal, 2023)

Insights into the surface Structure-Sensitive photocatalytic oxidation of gaseous toluene on Pd/TiO2 catalysts - Cong Wu; Qinglong Liu; Yu Zhan; Wei Tan; Xiaoqian Wei; Qing Tong; Haiqin Wan; Lin Dong (Chemical Engineering Journal, 2023)

Repairing vacancy defects for stabilization of high surface area hexagonal boron nitride under harsh conditions - Jinshu Tian; Jian Guan; Mingliang Xu; Shuya Qian; Kai Ma; Shaolong Wan; Zhaoxia Zhang; Haifeng Xiong; Shuai Wang; Yong Wang; Jingdong Lin (Chemical Engineering Journal, 2023)

Molybdenum isotope heterogeneity of metal sulfides from magmatic hydrothermal systems - Wan-li Tang; Ji-feng Xu; Kang Cao; Jie Li; Jian-lin Chen (Chemical Geology, 2023)

Pinostrobin modulates FOXO3 expression, nuclear localization, and exerts antileukemic effects in AML cells and zebrafish xenografts - Pei-Yi Chen; Ching-Yen Lin; Chia-Ling Wu; Pei Ying Keak; Je-Wen Liou; Wan-Yun Gao; Liang-In Lin; Jui-Hung Yen (Chemico-Biological Interactions, 2023)

Homozygous variants in CDC23 cause female infertility characterized by oocyte maturation defects - Huizhen Fan; Zhou Zhou; Wei Zheng; Yichun Guan; Qingxia Meng; Wenjing Wang; Jie Dong; Liuxia Wan; Jiawei Zhu; Yang Zeng; Ruyi Liu; Hao Gu; et al. (Human Genetics, 2023)

Dual application of Tribonema sp. GXU-A10 for purifying molasses vinasse and promoting the growth and health of Oreochromis niloticus - Hong-Yu Deng; Yue-Xin Sun; Xin-Qiang Chen; Yu Jiang; Wan-Lin Gu; Luo-Dong Huang; Pei-Hong Shen (Algal Research, 2023)

The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2023)

Dietary selenium promoted muscle growth (myofiber hypertrophy rather than hyperplasia) by reducing endoplasmic reticulum stress in juvenile grass carp (Ctenopharyngodon idella) - Ya Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Xiao-Wan Jin; Jun Jiang; Jia-Yong Tang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Reduction of pesticides and bacteria on Napa cabbage by ozone microbubble water - Hsiu-Ling Chen; Rachelle D. Arcega; Pei-Yu Liao; Chih-Yao Hou; Wen-Chun Liu; Yun-Ru Chen; Jong-Shinn Wu; Wan-Ru Wang; Chia-Min Lin (Postharvest Biology and Technology, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Structural behavior of CFRP-strengthened steel beams at different service temperatures: Experimental study and FE modeling - Dong Guo; Hua-Ping Wang; Yun-Lin Liu; Wan-Yang Gao; Jian-Guo Dai (Engineering Structures, 2023)

Cellulose supported and strengthened shear stiffening gel with enhanced impact-resistant performance - Zhen Zhang; Xiaoming Lin; Junyi Lin; Nana Liu; Bolin Wan; Xiong Fang; Lingling Shui; Yingzhan Li; Kam C. Tam; Jin Huang; Guofu Zhou (Chemical Engineering Journal, 2023)

Amorphous/crystalline heterophase W-Zn(Ti)O for the removal of Cr(VI) and tetracycline in single and mixed pollutant systems - Jie Xiong; Hong-Yan Zeng; Chen-Fei Liu; Jin-Feng Peng; Zhuo-Lin Yang; Wan-Ying Ji (Chemical Engineering Journal, 2023)

New perspective on mechanism in muscle toxicity of ochratoxin A: Model of juvenile grass carp (Ctenopharyngodon idella) - Piao Zhao; Xin Liu; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Juan Yang; Xiao-Qiu Zhou (Aquatic Toxicology, 2023)

Orientin regulates the proliferation and migration of hepatocellular carcinoma cells - Jia-Yi Tao; Jing Li; Lu Wan; Bi-Zhen Dong; Yong-Jie Yu; Ye-Mao Liu; Mao-Lin Yi; Li-Peng Wan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

Improvement of CYGNSS soil moisture retrieval model considering water and surface temperature - Shuangcheng Zhang; Qinyu Guo; Qi Liu; Zhongmin Ma; Ning Liu; Shengwei Hu; Lin Bao; Xin Zhou; Hebin Zhao; Lifu Wang; Tianhe Wan (Advances in Space Research, 2023)

MSGNet: multi-source guidance network for fish segmentation in underwater videos - Peng Zhang; Hong Yu; Haiqing Li; Xin Zhang; Sixue Wei; Wan Tu; Zongyi Yang; Junfeng Wu; Yuanshan Lin (Frontiers in Marine Science, 2023)
Fish segmentation in underwater videos provides basic data for fish measurements, which is vital information that supports fish habitat monitoring and fishery resources survey. However, because of water turbidity and insufficient lighting, fish segmentation in underwater videos has low accuracy and poor robustness. Most previous work has utilized static fish appearance information while ignoring fish motion in underwater videos. Considering that motion contains more detail, this paper proposes a method that simultaneously combines appearance and motion information to guide fish segmentation in underwater videos. First, underwater videos are preprocessed to highlight fish in motion, and obtain high-quality underwater optical flow. Then, a multi-source guidance network (MSGNet) is presented to segment fish in complex underwater videos with degraded visual features. To enhance both fish appearance and motion information, a non-local-based multiple co-attention guidance module (M-CAGM) is applied in the encoder stage, in which the appearance and motion features from the intra-frame salient fish and the moving fish in video sequences are reciprocally enhanced. In addition, a feature adaptive fusion module (FAFM) is introduced in the decoder stage to avoid errors accumulated in the video sequences due to blurred fish or inaccurate optical flow. Experiments based on three publicly available datasets were designed to test the performance of the proposed model. The mean pixel accuracy ( mPA ) and mean intersection over union ( mIoU ) of MSGNet were 91.89% and 88.91% respectively with the mixed dataset. Compared with those of the advanced underwater fish segmentation and video object segmentation models, the mPA and mIoU of the proposed model significantly improved. The results showed that MSGNet achieves excellent segmentation performance in complex underwater videos and can provide an effective segmentation solution for fisheries resource assessment and ocean observation. The proposed model and code are exposed via Github 1 .

In situ generated of hybrid interface in poly(1,3-dioxolane) quasi solid electrolyte and extended sulfone cosolvent for lithium-metal batteries - Bo-Han Zhang; Wan-Xin Wen; Hua-Ying Wang; Yun-Lei Hou; Jing-Zhou Chen; Dong-Lin Zhao (Chemical Engineering Journal, 2023)

Recognition of multivariate geochemical anomalies using a geologically-constrained variational autoencoder network with spectrum separable module – A case study in Shangluo District, China - Bo Zhao; Dehui Zhang; Panpan Tang; Xiaoyan Luo; Haoming Wan; Lin An (Applied Geochemistry, 2023)

A novel electrochemical aptasensor based on eco-friendly synthesized titanium dioxide nanosheets and polyethyleneimine grafted reduced graphene oxide for ultrasensitive and selective detection of ciprofloxacin - Yangguang Zhu; Xiufen Li; Mengfan Wu; Mingjiao Shi; Qichen Tian; Li Fu; Hsu-Sheng Tsai; Wan-Feng Xie; Guosong Lai; Gang Wang; Nan Jiang; Chen Ye; et al. (Analytica Chimica Acta, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Assessing the environmental sustainability of different soil disinfestation methods used in solar greenhouse vegetable production systems - Li Wan; Yiming Zhao; Longlong Xia; Jing Hu; Tongxin Xue; Haofeng Lv; Zhisheng Yao; Fanqiao Meng; Guoyuan Li; Shan Lin; Klaus Butterbach-Bahl (Science of The Total Environment, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

Effects of winemaking techniques on the phenolics, organic acids, and volatile compounds of Muscat wines - Yan-lun Ju; Xue-lei Xu; Yi-ke Yu; Meng Liu; Wan-ni Wang; Jin-ren Wu; Bo-chen Liu; Yang Zhang; Yu-lin Fang (Food Bioscience, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Biomineralization behavior and mechanism of microbial-mediated removal of arsenate from water - Xiang Liu; Wanqing Ren; Miao Lin; Xuejun Tan; Chunli Wan (Environmental Research, 2023)

Hierarchical CoMn-LDH based photothermal membrane with low evaporation enthalpy and narrow bandgap toward highly efficient Solar-Driven evaporation - Ruoxuan Zheng; Tong Lin; Wan-Lei Zhao; Rutao Yin; Hongqiang Li; Zhuoqun Deng; Wei Chen; Yu-Fei Song (Chemical Engineering Journal, 2023)

Regulating energy gap in Ir-based ionic complexes to generate near-infrared emissions: Application in solid-state light-emitting electrochemical cells - Yan-Ding Lin; Pei-Wan Hsiao; Wun-Yu Chen; Sih-Yu Wu; Wei-Min Zhang; Chin-Wei Lu; Hai-Ching Su (Chemical Engineering Journal, 2023)

A visible and near-infrared light dual-responsive PEC immunosensor for archaeological silk microtrace detection based on in situ growth of Ag2S on ZnO-MXene nanocomposites - Qingqing Zhou; Yong Liu; Lin Wang; Kun Wang; Haodong Chen; Hailing Zheng; Yang Zhou; Zhiwen Hu; Zhiqin Peng; Junmin Wan; Bing Wang (Chemical Engineering Journal, 2023)

Water-dispersible and stable polydopamine coated cellulose nanocrystal-MXene composites for high transparent, adhesive and conductive hydrogels - Bolin Wan; Nana Liu; Zhen Zhang; Xiong Fang; Yugao Ding; Haosheng Xiang; Yunqing He; Mingxian Liu; Xiaoming Lin; Juntao Tang; Yingzhan Li; Biao Tang; et al. (Carbohydrate Polymers, 2023)

Correction: Common Subtype of Small Renal Mass MR Imaging Characterisation: A Medical Center Experience in Taiwan - Ming-Cheng Liu; Yi-Jui Liu; Yen-Ting Lin; Siu-Wan Hung; Jyh-Wen Chai; Si-Wa Chan; Kun-Yuan Chiu; Ya-Ling Tsou (Journal of Medical and Biological Engineering, 2023)

Assessing Carbon Abatement Costs Considering Forest Carbon Sequestration and Carbon Offset Mechanism: Evidence from Taiwan - Wan-Yu Liu; Yi-Hsin Lu; Chun-Cheng Lin (Forest Science, 2023)
Based on the Greenhouse Gas Reduction and Management Act passed in 2015 and the carbon neutral target in 2050, Taiwan will most likely follow international trends by imposing carbon taxes and establishing carbon offset markets. The positive and negative effects of carbon taxes and carbon offset markets on the economy and the environment merit further investigation. Accordingly, this study adopted a carbon emission reduction (CER) cost prediction model to assess the carbon abatement costs under three scenarios: (1) a carbon offset market exists, and forest carbon sequestration can be used as carbon offsets; (2) a carbon offset market exists, but forest carbon sequestration cannot be used as carbon offsets; and (3) a carbon offset market does not exist. Forests in Taipei (with low carbon emissions) and Kaohsiung (with high carbon emissions) were selected as research sites to explore the benefits of carbon emissions trading and forest carbon sequestration. The results show that CER costs are the lowest in scenario 1 and are the highest in scenario 3. The CER costs of Kaohsiung are higher than those of Taipei. The higher the carbon price, the greater the difference in CER costs between the two cities. Study Implications: The objective of this study was to identify the optimal policy for Taiwan to effectively slow climate change. This study showed that the opening of carbon offset markets and the use of forest carbon sequestration as carbon offsets may prompt regions to increase their forest stock to lower their emission reduction costs. However, achieving 2050 carbon neutral target by solely using forest carbon sequestration is not sufficient in Taiwan.

From Tethyan subduction to Arabia-Eurasia continental collision: Multiple geo-thermochronological signals from granitoids in NW Iran - Zhiyong Zhang; Thomas Zack; Barry Kohn; Marco G. Malusà; Lin Wu; Mahnaz Rezaeian; Nan Wang; Dunfeng Xiang; Chao Guo; Rasoul Esmaeili; Bo Wan; Wenjiao Xiao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Co-transport of biochar nanoparticles (BC NPs) and rare earth elements (REEs) in water-saturated porous media: New insights into REE fractionation - Quan Wan; Beibei Liu; Miaoyue Zhang; Man Zhao; Yuan Dai; Wenshen Liu; Kengbo Ding; Qingqi Lin; Zhuobiao Ni; Jingjing Li; Shizhong Wang; Chao Jin; et al. (Journal of Hazardous Materials, 2023)

Intestine epithelial cell-derived extracellular vesicles alleviate inflammation induced by Clostridioides difficile TcdB through the activity of TGF-β1 - Shuangshuang Wan; Guangzhong Song; Hui Hu; Yaqing Xu; Peng Zeng; Shan Lin; Jun Yang; Jinqin Jiang; Xiaojun Song; Yongneng Luo; Dazhi Jin (Molecular & Cellular Toxicology, 2023)
Background Clostridioides difficile infection (CDI) has been primarily associated with the toxin B (TcdB), one of the three known protein toxins secreted by C. difficile , which can activate the intestinal immune system and lead to pathological damage. Even though the biological functions of intestine epithelial cell-derived extracellular vesicles (I-Evs) have been well documented, the role of I-Evs in the process of CDI is still unknown. Objectives The protective effect of I-Evs against C. difficile TcdB was investigated both in cultured murine colon carcinoma MC38 cells and a mouse model used in this study. Results Mouse I-Evs with mean diameter ranging from 100 to 200 nm and a density of 1.09–1.17 g/mL were obtained and confirmed containing the Ev-associated specific surface markers CD63 and TSG101 as well as high level of TGF-β1. In MC38 cells, I-Evs were able to decrease the gene expression of IL-6, TNF-α, IL-1β, and IL-22 induced by C. difficile TcdB, but to increase both the gene expression and protein levels of TGF-β1. I-Evs treatment via intraperitoneal administration alleviates C. difficile TcdB-induced local colon inflammation in mice and increased their survival rate from 50% up to 80%. Furthermore, I-Evs induced an increase in the proportion of CD4 + Foxp3 + Tregs in vitro and in vivo through a TGF-β1-dependent mechanism by activating the TGF-β1 pathway and prompting phosphorylation of the downstream proteins Smad 2/3. Conclusion For the first time, our study demonstrated that I-Evs originated from intestine epithelial cells can alleviate inflammation induced by C. difficile TcdB both in vitro and in vivo. Therefore, I-Evs might be potentially a novel endogenous candidate for effective treatment of CDI.

Remarkably efficient Pt/CeO2–Al2O3 catalyst for catalytic hydrodeiodination of monoiodoacetic acid: Synergistic effect of Al2O3 and CeO2 - Minghui Li; Wen Li; Yaning Yang; Dailiang Yu; Jingling Lin; Rui Wan; Hongjie Zhu (Chemosphere, 2023)

Numerical study on unsteady propeller exciting characteristics considering shafting whirling vibration effect - Chang-Lin Meng; Zhi-Jun Shuai; Tao Yu; Ke-Xin Ren; Jie Jian; Xi Wang; Dong-Hua Wang; Wan-You Li; Chen-Xing Jiang (Ocean Engineering, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

Shape-Controlled synthesis of conjugated microporous polymer nanotubes and their implementation in continuous flow polymerization - Xue Li; Xi Juan Zhang; Wan Lin Guo; Yuan Huang; Tao Cai (Chemical Engineering Journal, 2023)

The genetic basis of the leafy seadragon’s unique camouflage morphology and avenues for its efficient conservation derived from habitat modeling - Meng Qu; Yingyi Zhang; Zexia Gao; Zhixin Zhang; Yali Liu; Shiming Wan; Xin Wang; Haiyan Yu; Huixian Zhang; Yuhong Liu; Ralf Schneider; Axel Meyer; et al. (Science China Life Sciences, 2023)

Characteristics and provenances of rare earth elements and Nd isotopes in surface sediments of mangrove wetlands in the Jiulong River Estuary, China - Bo-sen Weng; Rui-an Wan; Rui-lian Yu; Gong-ren Hu; Yu Yan; Cheng-qi Lin; Hua-bin Huang (Environmental Science and Pollution Research, 2023)

Enhanced selective separation of vanadium(V) and chromium(VI) using the CeO2 nanorod containing oxygen vacancies - Ruixi Lin; Jiarong Li; Xuequan Jing; Meina Guo; Guoqing Ren; Haonan Qin; Zhangwei Yao; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; et al. (Environmental Science and Pollution Research, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

Characteristics and driving factors of abandoned cultivated land in the hilly regions of southern China: A case study in Longnan, Jiangxi Province - Ze-bin Chen; Yong-lin Chen; Chao-jun Li; Jian-ping Lin; Pei-ru Chen; Wei-wei Sun; Zhi-wei Wan (Journal of Mountain Science, 2023)

Integrated Model for Wave-Induced Oscillatory and Residual Soil Response in a Poro-Elastic Seabed: Partially Dynamic Model - Zhipeng Wan; Lin Cui; Dong-Sheng Jeng (Journal of Marine Science and Engineering, 2023)
The evaluation of wave-induced residual pore pressure in a porous seabed and associated seabed liquefaction is essential for designing marine infrastructure foundations. The strength and stiffness of the seabed could be weakened due to the build-up of pore pressures under cyclic wave action, further leading to residual liquefaction. Existing models for residual liquefaction are limited to the quasi-static uncoupled approaches, which do not account for the effect of oscillatory pore pressure on the accumulative pore pressure acceleration of solid particles, despite the mutual influence of these two mechanisms. To overcome these limitations, this paper proposes a new model for residual soil response with u−p approximation (partial dynamic model) that couples oscillatory and residual mechanisms. The proposed model is validated through wave flume tests and centrifuge tests. Based on the coupling model, a new criterion of liquefaction integrating both oscillatory and residual mechanisms is also proposed. Numerical examples demonstrate that the coupling effect significantly affects the wave-induced seabed liquefaction potential. Furthermore, a new parameter (Ω) representing the ratio of oscillatory and residual pore pressure is introduced to clarify which mechanism dominates the pore pressure development.

A cross-sectional study of the association between heavy metals and pan-cancers associated with sex hormones in NHANES 1999–2018 - Hai-ming Cao; Ya-zhu Yang; Bao-yi Huang; Yunzhe Zhang; Yu Wu; Zi Wan; Lin Ma (Environmental Science and Pollution Research, 2023)

Toxicologic effect of short-term enrofloxacin exposure on brain of Carassius auratus var. Pengze - Zhen Lin; Gen Wan; Jiayi Wu; Huazhong Liu; Fan Zhang; Xiaochen Tang; Jiming Ruan (Science of The Total Environment, 2023)

Long-term adaptation to elevated temperature but not CO2 alleviates the negative effects of ultraviolet-B radiation in a marine diatom - Peng Jin; Jiaofeng Wan; Xiaoying Dai; Yunyue Zhou; Jiali Huang; Jiamin Lin; Yucong Lu; Shiman Liang; Mengting Xiao; Jingyuan Zhao; Leyao Xu; Mingke Li; et al. (Marine Environmental Research, 2023)

Water transport in continental subduction zones: Constraints from eclogite from the Dabie orogen, east-central China - Zhi-Min Wang; Ren-Xu Chen; Yong-Fei Zheng; Shuning Li; Lin Zhu; Bing Gong; Xiang-Ping Zha; Wan-Cai Li (Journal of Asian Earth Sciences, 2023)

Assessing the ecosystem services provided by conventional and organic farmlands: A better outcome for organic farmlands? - Ching-Hua Hsieh; Hsing-Wei Lin; Wan-Yu Liu (Ecosystem Services, 2023)

Long-term manure amendment reduces nitrous oxide emissions through decreasing the abundance ratio of amoA and nosZ genes in an Ultisol - Song Wan; Yongxin Lin; Guiping Ye; Jianbo Fan; Hang-Wei Hu; Yong Zheng; Sheng-Sheng Jin; Chunjian Duan; Ji-Zheng He (Applied Soil Ecology, 2023)

Paper-based analytical device coupled with Bi-MOF: Electric field amplification and fluorescence sensing of glyphosate - Chao-Qun Wan; Yue-Hong Pang; Qiu-Yu Yang; Cheng-Lin Yang; Xiao-Fang Shen (Analytica Chimica Acta, 2023)

The impacts of extreme marine weather and marine scientific and technological innovation on marine economic development: Evidence form China’s coastal regions - Chenggang Li; Hongye Jia; Yikang Wan; Yongxiang Hu; Bingying Zeng; Wanyue Zhang; Xiangbo Fan; Tao Lin; Guofei Shang; Weiyan Wang (Frontiers in Marine Science, 2023)
The extreme marine weather is a very vital factor and has important implications for of marine economic development. However, there is a lack of systematic and quantitative analyses of its impact on the marine economic development. Here, we study the impacts of extreme marine weather on marine economic development of 11 coastal regions in China, using the dynamic panel model. We found that extreme marine weather exerts a significant negative impact on the marine economic development. The marine scientific and technological innovation promotes marine economic development in a prominent manner. The marine scientific and technological innovation slows down the unfavorable impact of extreme marine weather on the marine economy. After considering different industries for marine economic development and heterogeneity, we found that extreme marine weather and marine scientific and technological innovation have a great impact on marine economic development in the tertiary industry and the areas with high development concerning marine economy level, while deliver a small impact on the marine economic development in the primary industry and the areas low development level. This paper empirically studies the relationship between the two variables of marine extreme weather and marine science and technology innovation and its impact on marine economic development, enriches the research perspective of extreme weather on marine economic development, and provides new method evidence for improving the level of marine scientific and technological innovation and promoting the development of marine economy.

Different responses of nitrous oxide emissions to liming and manure amendment of an acidic ultisol are controlled by autotrophic and heterotrophic nitrification - Song Wan; Yongxin Lin; Jianbo Fan; Hang-Wei Hu; Jinbo Zhang; Sheng-Sheng Jin; Milin Deng; Christoph Müller; Ji-Zheng He (Soil Biology and Biochemistry, 2023)

UV-B regulates seasonal greening of albino leaves by modulating CsHY5-inhibiting chlorophyll biosynthesis in Camellia sinensis cv. Huangkui - Xuyang Liu; Xin Cheng; Jingjie Cao; Wenfeng Zhu; Ying Sun; Ning Lin; Xiaochun Wan; Linlin Liu (Plant Science, 2023)

Effects of palm olein and palm stearin on cecal and fecal microbiota of C57BL/6J mice under low and high fat intakes - Liting Wan; Lin Li; Xia Zhang; Bing Li; Janette M. Harro; Mark E. Shirtliff (Food Chemistry, 2023)

Effects of mannoprotein on the stability and in vitro digestion of cyanidin-3-glucoside - Meizhi Wan; Sixu Lin; Chang Tan; Mingyue Wang; Yuqi Tong; Yang Zhao; Yanwen Kong; Haotian Deng; Xianjun Meng; Yan Ma (Food Chemistry, 2023)

Spatially dual-confined metallic selenide double active centers for boosting potassium ion storage - Juan Gong; Rui Zhang; Xijun Wei; Yu Liu; Qing Luo; Qi Wan; Qiaoji Zheng; Lei Wang; Shude Liu; Dunmin Lin (Chemical Engineering Journal, 2023)

Soil microbial community is resilient to thinning disturbance - Wan-Rou Lin; Wen-Cheng Chen; Pi-Han Wang (Tropical Ecology, 2023)

Method research and effect analysis of fuel-assembly bowing on neutron-physics simulations of HPR1000 - Chenghui Wan; Lin Guo; Jiahe Bai (Annals of Nuclear Energy, 2023)

Application of the Gini Index on the Evaluation of the Environmental Heterogeneity and Habitat Suitability Index for Larval Gobies - Lu Zhai; Rong Wan; Siquan Tian; Zengguang Li; Pengbo Song; Jun Lin (Journal of Marine Science and Engineering, 2023)
Spatial environmental heterogeneity in the Yangtze River Estuary (YRE) is always mentioned but rarely quantified and included in the evaluation process. This study introduced the habitat suitability index evaluation model based on the Gini index (HSIgini) to evaluate the optimal ranges of suitable environmental factors for three typical estuarine gobies, i.e., Rhinogobius giurinus, Acentrogobius pflaumii, Odontamblyopus rubicundus, and their habitat quality. The evaluation was carried out based on field surveys conducted in the spring and summer of 2018–2020. The Lorentz curve and Gini index were used to evaluate the spatial environmental heterogeneities in the YRE. The spatial heterogeneity of environmental factors in the Yangtze Estuary ranged from 0.62 to 0.05, with the highest Gini index for salinity and the lowest for temperature. The combination of environmental factors had significant spatial effects on habitat, with temperature showing mainly seasonal effects. The study indicated that the YRE is a good habitat for gobies and that there is spatial and seasonal differentiation in the habitats of different species, greatly reducing interspecific competition. Environmental heterogeneity is important for biological processes and should be incorporated into the modeling of bio–environmental relationships in future research to provide a basis for environmental and biological conservation and management.

Establishing a high-performance anti-fouling PEI-ZIF-PAA membrane with improved Lewis acid-base interactions and hydrophilicity - Zhang-Hong Wan; Jing Guan; Chun-Miao Zhang; Wen-Qing Fei; Lin Wang; Shu-Guang Wang; Xue-Fei Sun (Chemosphere, 2023)

Condition optimization of iron-air fuel cell to treat phosphate-containing wastewater regarding sustainable development - Ling-ling Lai; Chao Liu; Meng-yu Liu; Si-zhuo Wan; Zhi-guo Zhao; Ru Wang; Lin-jiang Yuan (Chemosphere, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Molecular cloning and characterization of NLRX1 from orange-spotted grouper (Epinephelus coioides) as a mediator of ROS production through its LRR domains - Xu Ding; Yaosi Liang; Qinghua Hou; Shuisheng Li; Wan Peng; Ruozhu Li; Haoran Lin; Yong Zhang; Danqi Lu (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

A novel monoclonal antibody efficiently blocks the infection of duck adenovirus 3 by targeting Fiber-2 - Yun Lin; Wenyuan Zhang; Jing Xie; Quan Xie; Tuofan Li; Zhimin Wan; Hongxia Shao; Aijian Qin; Jianqiang Ye (Veterinary Microbiology, 2023)

Contaminant characterization at pesticide production sites in the Yangtze River Delta: Residue, distribution, and environmental risk - Mei Li; Qiang Chen; Lu Yang; Ya Zhang; Jinlin Jiang; Shaopo Deng; Jinzhong Wan; Tingting Fan; Tao Long; Shengtian Zhang; Yusuo Lin (Science of The Total Environment, 2023)

Impact of ozonation on the optical properties and photo-reactivity of dissolved organic matter - Xiaoliang Chen; Lin Deng; Yong Chen; Dong Wan (Journal of Environmental Chemical Engineering, 2023)

Tourists' preference for colors of forest landscapes and its implications for forest landscape planning policies - Wan-Yu Liu; Chen Tsao; Chun-Cheng Lin (Forest Policy and Economics, 2023)

ZIF-67 loaded lotus leaf-derived biochar for efficient peroxymonosulfate activation for sustained levofloxacin degradation - Jingwei Yan; Lin Gong; Senyou Chai; Cong Guo; Wei Zhang; Hongyou Wan (Chemical Engineering Journal, 2023)

One-step coaxial spinning of core-sheath hydrogel fibers for stretchable ionic strain sensors - Hui Wu; Lin Wang; Hengyi Lou; Junmin Wan; Xiong Pu (Chemical Engineering Journal, 2023)

Biomimetic bone tissue structure: An ultrastrong thermal energy storage wood - Xianxian Lin; Chendong Qiu; Kailin Wang; Yi Zhang; Caichao Wan; Mizi Fan; Yiqiang Wu; Weisheng Sun; Xi Guo (Chemical Engineering Journal, 2023)

Iron–polyphenol dendritic complexes for regulating amplification of phenolic hydroxyl groups to improve magnetic resonance imaging - Ying Wan; Lu An; Zixuan Zhu; Qiwei Tian; Jiaomin Lin; Shiping Yang (Chemical Engineering Journal, 2023)

p-n heterojunctions of Si@WO3 mimicking thylakoid for photoelectrocatalytic CO2 reduction to C2+ products — Morphology control - Wenrui Wan; Qiaolan Zhang; Yan Wei; Youzhi Cao; Jiaxiu Hou; Chunyan Liu; Lin Hong; Hong Gao; Jiazang Chen; Huanwang Jing (Chemical Engineering Journal, 2023)

Immune‐enhancing effects of Astragalus polysaccharides and Ganoderma lucidum polysaccharides on Vibrio harveyi flgJ DNA vaccine in grouper - Guixiang Lin; Fan Da; Xiaoju Wan; Yucong Huang; Shiping Yang; Jichang Jian; Shuanghu Cai (Journal of Fish Diseases, 2023)
Astragalus polysaccharides (APS) and Ganoderma lucidum polysaccharides (GLP) have been shown to possess strong immunoregulatory properties in aquatic animals. In this study, the fragment containing Vibrio harveyi flgJ gene was ligated into pcDNA3.1(+) vector and pcDNA3.1(+)‐flgJ was constructed as DNA vaccine. APS and GLP were used as DNA vaccine adjuvants to evaluate the immunoregulatory effect by intramuscular injection to pearl gentian grouper ( ♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus ). The results showed that pcDNA3.1(+)‐flgJ combined with APS or GLP could significantly up‐regulate the innate and adaptive immune response in fish, including serum‐specific antibody titres, catalase and lysozyme activities. At the same time, DNA vaccine combined with APS or GLP significantly up‐regulated the expression levels of CD8α , IgM , IL‐1β , MHC‐Iα , MyD88 and TLR3 genes in thymus, head kidney, spleen and liver of pearl gentian grouper in comparison with those of the pFlgJ group. After 42 days post‐vaccination, V. harveyi was used to challenge pearl gentian grouper by intraperitoneal injection. The relative percentage of survival (RPS) of pFlgJ, pFlgJ +APS, pFlgJ +GLP and pFlgJ+APS+GLP groups were 69%, 81%, 77% and 88%, respectively. These results suggested APS and GLP were potential adjuvants for DNA vaccine against V. harveyi infection in pearl gentian grouper.

A fluorescent probe based on a phenylalanine derivative is capable of sequential detection of Zn2+ and Cys/His - Qiu-Yu Yu; Chuan-Wan Wei; Xiao-Juan Wang; Shu-Qin Gao; Xin-Yi Tong; Ying-Wu Lin (JBIC Journal of Biological Inorganic Chemistry, 2023)

Seismic Multiple Attenuation in the Continent–Ocean Transition Zone of the Northern South China Sea - Nan Chen; Chun-Feng Li; Yong-Lin Wen; Peng Wang; Xiu-Lian Zhao; Xiao-Li Wan (Journal of Marine Science and Engineering, 2023)
In this study, we process four new multichannel reflection seismic profiles acquired in 2015 and 2016 in the continent–ocean transition zone (COT) of the northern South China Sea (SCS). We apply a multi-domain, progressive, and seabed-controlled denoising technique and obtain a good denoising effect. Combining velocity analysis in the multi-round time domain and forward modeling, we analyze the types and characteristics of multiples in the study area and formulate an effective demultiple technique to attenuate strong seabed multiples, diffracted multiples from rough seafloor, and other multiples from deep reflectors. The processing results show that the sea surface-related multiple elimination technique predicts the sea surface-related multiples accurately by data convolution, and has a good effect in attenuating seabed multiples. Diffracted multiple attenuation method extracts high-frequency and high-energy diffracted multiples, and suppresses multiples by the energy ratios of multiples to primary events. To attenuate deep multiples, we select predictive deconvolution to attenuate periodic deep multiples after many trials and detailed analysis. The combination of these different techniques in sequence proves to be quite effective in attenuating different seismic multiples in the COT. The imaged crustal structures near the COT often show strong magmatism and/or basement uplifting. The faulted and thinned continental crust adjacent to the COT corresponds to the lowest free-air gravity anomalies. Gravity anomalies often increase from the COT to the oceanic crust. An exception is to the northeast of the SCS, where the relatively wide COT shows very high gravity anomalies, likely induced by mantle upwelling and serpentinization.

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

VUV/UV oxidation performance for the elimination of recalcitrant aldehydes in water and its variation along the light-path - Wan-Yue Ouyang; Wen-Long Wang; Yi-Lin Zhang; Han-Ying Cai; Qian-Yuan Wu (Water Research, 2023)

Seasonal variation and ecological risk assessment of Pharmaceuticals and Personal Care Products (PPCPs) in a typical semi-enclosed bay — The Bohai Bay in northern China - Kun Lin; Rui Wang; Tongzhu Han; Liju Tan; Xue Yang; Mengmeng Wan; Yanshan Chen; Ting Zhao; Shan Jiang; Jiangtao Wang (Science of The Total Environment, 2023)

Organic matter accumulation mechanism under global/regional warming: Insight from the Late Barremian calcareous shales in the Qiangtang Basin (Tibet) - Ying Nie; Xiugen Fu; Xianchuan Liu; Hengye Wei; Shengqiang Zeng; Fei Lin; Youli Wan; Chunyan Song (Journal of Asian Earth Sciences, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Developing membrane reactors with suspended polyphthalocyanine nanoplatelets for upscaling syntheses of protein-polymer bioconjugates - Wen Fang Wei; Wan Lin Guo; Min Jian; Liu Shu Qin; Xue Li; Tao Cai (Chemical Engineering Journal, 2023)

Generation of reactive oxygen species through dissolved oxygen activation on defected porous carbon for efficient degradation of antibiotics - Jiaming Liu; Zhangwei Yao; Genping Qiu; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; Wenjing Yuan; Peihai Ju; Ruixi Lin; Hengcheng Zhou; et al. (Chemical Engineering Journal, 2023)

Robust emission in near-infrared II of lanthanide nanoprobes conjugated with Au (LNPs-Au) for temperature sensing and controlled photothermal therapy - Guofeng Liu; Zhenxing Wang; Wan Sun; Xiaohui Lin; Rui Wang; Chonghui Li; Li Zong; Zuoling Fu; Hanping Liu; Shicai Xu (Chemical Engineering Journal, 2023)

Dual-site oxygen activation for enhanced photocatalytic aerobic oxidation by S-scheme Ni2P/Bi3O4Br-OVs heterojunction - Weijie Yang; Kailong Sun; Jun Wan; Yang-Ai Ma; Yu Wang; Lin Liu; Bicheng Zhu; Feng Fu (Chemical Engineering Journal, 2023)

Water-assistant ultrahigh fluorescence enhancement in perovskite polymer-encapsulated film for flexible X-ray scintillators - Yue Li; Qian-Li Li; Yan Li; Yun-Ling Yang; Shao-Lin Zhang; Jingtai Zhao; Jieqiong Wan; Zhijun Zhang (Chemical Engineering Journal, 2023)

Flexible and highly piezoelectric nanofibers with organic–inorganic coaxial structure for self-powered physiological multimodal sensing - Xingyi Wan; Zhuo Wang; Xinyang Zhao; Quanhong Hu; Zhou Li; Zhong Lin Wang; Linlin Li (Chemical Engineering Journal, 2023)

Lightweight Flexible Polyimide-Derived Laser-Induced Graphenes for High-Performance Thermal Management Applications - Yu-Sheng Hsiao; Cai-Wan Chang-Jian; Tzu-Yen Huang; Ying-Lin Chen; Chung-Wei Huang; Jen-Hsien Huang; Nian-Jheng Wu; Shih-Chieh Hsu; Chih-Ping Chen (Chemical Engineering Journal, 2023)

A peptide Epitope − Synthetic hydrogel polymer conjugate that mimics insecticidal protein Receptors. Application in environmental and biological analysis - Zihao Wan; Yalu Chen; Senhua Hu; Qiaolian Chen; Yuxin Li; Xiuhua Chen; Wenfeng Tan; Yongjun Lin; Kenneth J. Shea; Mingming Liu (Chemical Engineering Journal, 2023)

A symbiosis between Euploea butterflies and yeasts - Wan-Rou Lin; Yi-Ping Chang; Hui-Lin Wu; I-Cheng Hsu; Pi-Han Wang (Symbiosis, 2023)

Liming shifts the chemical properties and microbial community structures of peanut soils with different initial pH values - Ya Lu; Hongcui Dai; Kazem Zamanian; Qiqi Sun; Caibin Wang; Zhengfeng Wu; Yongmei Zheng; Lin Li; Shubo Wan; Tianyi Yu (Applied Soil Ecology, 2023)

Cloning, characterization and expression analysis of caspase-8 genes from the golden pompano (Trachinotus ovatus) - Fan Da; Xiaoju Wan; Guixiang Lin; Jichang Jian; Shuanghu Cai (Frontiers in Marine Science, 2022)
Bacterial infection triggers apoptosis and immunity by regulating the expression of caspases. In this article, we report two caspase-8 paralogs, termed ToCas8 and ToCas8 -like, from an economically important teleost golden pompano ( Trachinotus ovatus ). Caspase-8 is a classic cysteine protease that is essential for the initiation and execution of apoptosis and is a critical regulator in initiating death receptor-induced programmed cell death. The two proteins encoded by ToCas8 and ToCas8 -like were characterized by multiple sequence alignment and protein structure analysis showing similarity to their counterparts in vertebrates and exhibiting typical features of the Caspase-8 protein family. Gene synteny analysis further confirmed that two isoforms of caspase-8 genes exactly existed in golden pompano. Phylogenetic analysis showed that the Caspase-8 proteins of the selected species in the study were clustered together, and Cas8 and Cas8-like were clustered into two different subgroups. In addition, ToCas8 and ToCas8 -like were widely distributed and both were expressed at high levels in gill, kidney and intestinal tissues. Transcript levels of ToCas8 and ToCas8 -like were significantly upregulated in response to LPS and Poly(I:C) challenges, suggesting that caspase-8 genes are involved in the immune response to pathogens. In summary, we have identified two isoforms of caspase-8 in golden pompano that are involved in the immune response. These findings will expand our understanding of the evolutionary history and functional characteristics of caspase-8 genes in vertebrates.

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

Effects of simulated nitrogen deposition on the ecophysiological responses of Populus beijingensis and P. cathayana under intra- and interspecific competition - Lianghua Chen; Jiaxuan Mi; Linting Hao; Fang He; Hanbo Yang; Xueqin Wan; Fan Zhang; Yang Liu; TianTian Lin (Plant and Soil, 2022)

Transcranial Direct-Current Stimulation Regulates MCT1-PPA-PTEN-LONP1 Signaling to Confer Neuroprotection After Rat Cerebral Ischemia–Reperfusion Injury - Xiangyi Kong; Wenjie Hu; Yu Cui; Jingchen Gao; Xujin Yao; Jinyang Ren; Tao Lin; Jiangdong Sun; Yunyi Gao; Xiaohua Li; Hui Wang; Huanting Li; et al. (Molecular Neurobiology, 2022)
Propionic acid (PPA) is a critical metabolite involved in microbial fermentation, which functions to reduce fat production, inhibit inflammation, and reduce serum cholesterol levels. The role of PPA in the context of cerebral ischemia–reperfusion (I/R) injury has yet to be clarified. Increasing evidence indicate that transcranial direct-current stimulation (tDCS) is a safe approach that confers neuroprotection in cerebral ischemia injury. Here, we show that the levels of PPA were reduced in the ischemic brain following a rat cerebral I/R injury and in the cultured rat cortical neurons after oxygen–glucose deprivation (OGD), an in vitro model of ischemic injury. We found that the decreased levels of transporter protein monocarboxylate transporter-1 (MCT1) were responsible for the OGD-induced reduction of PPA. Supplementing PPA reduced ischemia-induced neuronal death after I/R. Moreover, our results revealed that the neuroprotective effect of PPA is mediated through downregulation of phosphatase PTEN and subsequent upregulation of Lon protease 1 (LONP1). We demonstrated that direct-current stimulation (DCS) increased MCT1 expression and PPA level in OGD-insulted neurons, while tDCS decreased the brain infarct volume in the MCAO rats via increasing the levels of MCT1 expression and PPA. This study supports a potential application of tDCS in ischemic stroke.

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

CircCERS6 Suppresses the Development of Epithelial Ovarian Cancer Through Mediating miR-630/RASSF8 - Xiaoqin Li; Xuemei Jiang; Jing Lu; Yuting Lin; Lan Jiang; Yan Li; Feng Wan; Changmin Wang (Biochemical Genetics, 2022)

Nitrogen enrichment alters multiple dimensions of grassland functional stability via changing compositional stability - Qianna Xu; Xian Yang; Jian Song; Jingyi Ru; Jianyang Xia; Shaopeng Wang; Shiqiang Wan; Lin Jiang (Ecology Letters, 2022)
Anthropogenic nutrient enrichment is known to alter the composition and functioning of plant communities. However, how nutrient enrichment influences multiple dimensions of community‐ and ecosystem‐level stability remains poorly understood. Using data from a nitrogen (N) and phosphorus (P) addition experiment in a temperate semi‐arid grassland that experienced a natural drought, we show that N enrichment, not P enrichment, decreased grassland functional and compositional temporal stability, resistance and recovery but increased functional and compositional resilience. Compositional stability and species asynchrony, rather than species diversity, were identified as key determinants of all dimensions of grassland functional stability, except for recovery. Whereas grassland functional recovery was decoupled from compositional recovery, N enrichment altered other dimensions of functional stability primarily through changing their corresponding compositional stability dimensions. Our findings highlight the need to examine ecological stability at the community level for a more mechanistic understanding of ecosystem dynamics in the face of environmental change.

Biophysical controls on spatial and summer/winter distributions of total and chromophoric dissolved organic matter in the Taiwan Strait - Jia-Jang Hung; Wan-Tzu Lu; Hsin-Mei Yang; Yen-Hui Lin; Laodong Guo (Frontiers in Marine Science, 2022)
This study examined the physical and biogeochemical processes that determine the spatial and summer/winter distributions of dissolved organic matter (DOM) and chromophoric dissolved organic matter (CDOM) in the Taiwan Strait (TS). The hydrological conditions in the TS varied between early summer and winter because of differences in terrestrial input as well as input from the poleward South China Sea Water (SCSW) during the warm summer and the strong, nutrient-rich, equatorward China Coastal Water (CCW) in winter. Concentrations of dissolved organic carbon (DOC) ranged from 60 to 100 μM-C in early summer and from 70 to 144 μM-C in winter. The average stoichiometric ratio of DOC : DON:DOP was high (353:49:1) in the land-source impacted zones and low (168:21:1) in the SCSW-laden areas, both of which are higher than the Redfield ratio. The concentrations of DOC and nutrients were higher in the western TS (on the coast of China) than in the eastern TS (on the coast of Taiwan), and the highest concentrations were mostly found in the Minjiang River plume, reflecting the profound effects of freshwater input in early summer and CCW inflow in winter. The absorption and emission characteristics of the CDOM varied to a large extent with locations because of the mixing of the shelf water with different source waters. Although the absorption coefficient (a CDOM (325)) and fluorescence intensity of the terrestrial humic-like CDOM (Ft: Ex/Em= 260/400-460) were both strongly inversely correlated with salinity, as an optical tracer, Ft may be more effective than a CDOM (325) in examining the mixing among source waters, given that a CDOM (325) may be subject to various photobleaching effects in the TS. Ft was also significantly correlated with the concentrations of terrestrially derived nitrate and nitrite (N+N) and silicate. The results of factor analysis elucidated the complexity of the hydrological and biological processes that affect the distributions of DOM and CDOM in the TS.

Assessment of trends in an integrated climate metric—analysis of 200 mbar zonal wind for the period 1958–2021 - Nenghan Wan; Xiaomao Lin; Roger A. Pielke (Theoretical and Applied Climatology, 2022)
Using two reanalysis datasets on latitude bands of nearly equal area, we analyze the trend of 200 mbar zonal wind anomalies for the period 1958–2021 as well as annual-mean latitude of the zonal mean jet stream. We do not find much change of 200 mbar zonal wind in both two datasets although the increasing trend over the high latitude bands from 45 to 61°S for both datasets, and the decreasing trend in 0–5°N and 0–10°S for ERA5 are significant with small magnitudes. In addition, the polar jet core moves poleward in the Northern Hemisphere, but the movement is not statistically significant, while no poleward shift at all has occurred in the Southern Hemisphere. This work provides us a way to look for the long-term changes and variability in atmospheric circulation.

Associations of exposure to lead and cadmium with risk of all-cause and cardiovascular disease mortality among patients with type 2 diabetes - Kai Zhu; Yuge Zhang; Qi Lu; Tingting Geng; Rui Li; Zhenzhen Wan; Xuena Zhang; Yujie Liu; Lin Li; Zixin Qiu; Meian He; Liegang Liu; et al. (Environmental Science and Pollution Research, 2022)

Associations of metal profiles in blood with thyroiditis: a cross-sectional study - Yaosheng Luo; Huixian Zeng; Yanshi Ye; Genfeng Yu; Cheng Song; Siyang Liu; Xingying Chen; Yuqi Jiang; Hualin Duan; Yue Li; Shengqing He; Zhi Chen; et al. (Environmental Science and Pollution Research, 2022)
Autoimmune thyroiditis (AIT) is increasingly common, and serological markers include thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). To determine if selected metals influence thyroiditis antibody positivity, this cross-sectional study investigated associations between metals and thyroiditis antibody status. Healthy individuals ( n = 1104) completed a questionnaire and underwent checkups of anthropometric parameters, thyroid function status, and levels of seven metals in blood (magnesium, iron, calcium, copper, zinc, manganese, and lead). Associated profiles of glyco- and lipid metabolism were also established. Logistic regression and restricted cubic spline (RCS) regression analysis were applied to adjudge associations between metals and TPOAb and TgAb status. It was found that, after adjusting for likely cofounding factors, participants with antibody positivity had significantly lower serum concentrations of magnesium and iron. When serum magnesium levels were analyzed in quartiles, the odds ratios of quartile 4 were 0.329–fold (95% confidence interval (CI): 0.167–0647) and 0.259-fold (95% CI 0.177–0.574) that of quartile 1 regarding TPOAb and TgAb positivity ( P = 0.004, 0.003). After adjustment, the RCS analysis detected nonlinear associations between iron and TPOAb and TgAb positivity ( P < 0.01, both). In stratified analyses, these associations regarding magnesium and iron remained for women of reproductive age, but not for postmenopausal women and men. We conclude that lower serum levels of magnesium and iron are associated with incremental positivity of thyroiditis antibodies and may be among the most important metals contributing to AIT in women of reproductive age.

Plasma Matrix Metalloproeteinase-9 Is Associated with Seizure and Angioarchitecture Changes in Brain Arteriovenous Malformations - Yo-Tsen Liu; Cheng-Chia Lee; Chun-Fu Lin; Hsiu-Mei Wu; Wan-Yuo Guo; Huai-Che Yang; Feng-Chi Chang; Kang-Du Liou; Chung-Jung Lin (Molecular Neurobiology, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

Effects of soil organic matter components and iron aluminum oxides on aggregate stability during vegetation succession in granite red soil eroded areas - Zhe Lin; Zhi-gang Huang; Da-lan Liao; Wan-xia Huang; Juan Huang; Yu-song Deng (Journal of Mountain Science, 2022)

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

Spatial patterns and driving factors of carbon stocks in mangrove forests on Hainan Island, China - Yuchen Meng; Ruikun Gou; Jiankun Bai; David Moreno‐Mateos; Charles C. Davis; Luoma Wan; Shanshan Song; Hongsheng Zhang; Xiaoshan Zhu; Guanghui Lin (Global Ecology and Biogeography, 2022)
Aim Mangrove forests are important coastal wetlands for the blue carbon budget and play a significant role in mitigating global climate change. However, spatial patterns of carbon stocks in mangrove forests on an island scale have not been quantified owing to methodological limitations and lack of understanding of controlling factors. We took the entire Hainan Island as a case study and aimed to carry out a comprehensive investigation of the spatial patterns and driving factors of carbon stocks in mangrove forests. Location Southern China. Time period 2017–2020. Major taxa studied Mangrove forest. Methods The upscaling method combined with field surveys and Sentinel‐2 imagery analysis were used to compare different models for optimization of mangrove ecosystem carbon stock estimations. We also used structural equation modelling (SEM) to evaluate the factors driving the distributional patterns of mangrove carbon stocks on an island scale. Results The current total mangrove carbon stock of the entire Hainan Island was estimated to be 703,181 Mg C (with a mean density of 192 Mg C/ha), with the above‐ and below‐ground carbon stocks averaging at 44.7 and 147.3 Mg C/ha, respectively. The mangrove carbon storage in the north‐eastern region of the island was the highest and in the west region the lowest. Sediment nitrogen content and plant species diversity had the most positive driving effects on the distribution of total carbon stock for Hainan Island mangroves. Main conclusions The combination of field surveys and Sentinel‐2 imagery analysis can be applied to regional‐scale estimations of carbon stocks for mangrove forests. Spatial pattens of mangrove carbon stocks vary among locations on Hainan Island, and soil nutrient (especially nitrogen) availability is the dominant factor regulating carbon stock variations along the land‐to‐sea gradient. Our findings have significant implications for better understanding the distribution of mangrove carbon stocks and quantification of the global blue carbon budget.

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Plant secondary metabolite and temperature determine the prevalence of Arsenophonus endosymbionts in aphid populations - Chun‐Yan Chang; Xiao‐Wan Sun; Pan‐Pan Tian; Ning‐Hui Miao; Yu‐Lin Zhang; Xiang‐Dong Liu (Environmental Microbiology, 2022)
Summary Transmission rate and role in hosts contribute to the prevalence of an endosymbiont. However, factors affecting transmission and role of facultative endosymbionts are still not well understood. Here, we illustrated that host plants and environmental temperatures affected the transmission, relative abundance and role of Arsenophonus in the cotton aphid Aphis gossypii . The transmission rate of this endosymbiont from mother aphids to offspring was relatively lower. High temperatures impeded the transmission, and infection rates declined as aphids were exposed to 30°C. Contents of amino acids and secondary metabolites were remarkably different among host plants. Aphids feeding on zucchini leaves containing a higher titre of amino acids and lower secondary metabolites harboured a relatively lower abundance of Arsenophonus . Concentrations of an amino acid and a plant secondary metabolite, cucurbitacin B, in aphid diet were not associated with Arsenophonus abundance. However, gossypol, another plant secondary metabolite, was strongly related with the abundance. Arsenophonus imparted a fitness benefit to aphids, and the benefit was dependent on host plants and gossypol concentration. In sum, plant secondary metabolite and environmental temperature affect transmission, relative abundance and role of Arsenophonus , which determine the endosymbiont prevalence in aphid populations.

Research on an Extensible Monitoring System of a Seafloor Observatory Network in Laizhou Bay - Jie Chen; Hailin Liu; Bin Lv; Chao Liu; Xiaonan Zhang; Hui Li; Lin Cao; Junhe Wan (Journal of Marine Science and Engineering, 2022)
An extensible remote monitoring system for a seafloor observatory network in Laizhou Bay was established to realize long-term, continuous and on-line monitoring for a marine ranching environment. This paper deals with data communication, device management and data quality control. A control model is introduced that is structured into four layers, enabling bidirectional information flow. Based on the control model, the standardized communication protocol and device object model-oriented dynamic management method are designed as plug-and-play, for data processing and control of a large number of devices. An improved data quality control method is proposed to reduce the data error rate. The monitoring system was developed based on socket network programming, MySQL database technologies and modular ideas. The seafloor observatory network was successfully deployed in Laizhou Bay marine ranching. The experimental results demonstrate that the monitoring system obtains better performance. The proposed algorithms can also be used in many other similar systems with adaptive requirements.

Fissistiganoids A and B: two new flavonoids from the Fissistigma tungfangense - Wan-Lin Zhong; Xue-Ming Zhou; Ji-Ling Yi; Xin-Ming Song; Bin Zhang; Jing-Yu Yang; Guang-Ying Chen (Natural Product Research, 2022)

EMS-CDNet: an efficient multi-scale-fusion change detection network for very high-resolution remote sensing images - Zhi Zheng; Yi Wan; Yongjun Zhang; Kun Yang; Rang Xiao; Chao Lin; Qiong Wu; Daifeng Peng (International Journal of Remote Sensing, 2022)

Isolation of Three Coliphages and the Evaluation of Their Phage Cocktail for Biocontrol of Shiga Toxin-Producing Escherichia coli O157 in Milk - Lili Zhu; Yanyan Hou; Xi Huang; Shuang Wang; Rui Xie; Jie Yang; Qingjie Lv; Lin Hua; Wan Liang; Zhong Peng; Bin Wu (Current Microbiology, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Hasubanan alkaloids with anti-inflammatory activity from Stephania longa - Hui Liu; Wan-Qin Liao; Rong-Xiao Lin; Lixia Fan; Jinyan Sun; Hong-Yuan Chen; Fang Liu; An-Ping Yang (Natural Product Research, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Development of novel polymorphic microsatellite markers for Picea brachytyla - Shuai-Peng Si; Chun-Jing Wang; Ji-Zhong Wan; Yu-Lin Qian; Chun-Hui Zhang (Molecular Biology Reports, 2022)

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

Follicular Fluid-Derived Exosomal MicroRNA-18b-5p Regulates PTEN-Mediated PI3K/Akt/mTOR Signaling Pathway to Inhibit Polycystic Ovary Syndrome Development - Zhi Zhou; Zhihua Tu; Juan Zhang; Can tan; Xiaoyong Shen; Bangbei Wan; Yejuan Li; Anguo Wang; Liqiang Zhao; Jiajia Hu; Ning Ma; Jing Zhou; et al. (Molecular Neurobiology, 2022)

Effects of Environmental and Spatial Variables on Bacteria in Zhanjiang Mangrove Sediments - Di-Hua Zhu; Qing-Lang Song; Fang-Hong Nie; Wan Wei; Meng-Meng Chen; Min Zhang; Hong-Ying Lin; Dan-Ju Kang; Zhi-Bao Chen; Anthony G. Hay; Jin-Jun Chen (Current Microbiology, 2022)

Knockout of GGPPS1 restrains rab37-mediated autophagy in response to ventilator-induced lung injury - Zexu Wang; Meizi Chen; Xia Pan; Li Wang; Cheng Yin; Qiuqi Lin; Jingjing Jiang; Yunlei Zhang; Bing Wan (Human Cell, 2022)

Characterization of a Diguanylate Cyclase VAGM001033 of Vibrio alginolyticus and Protective Efficacy as a Live Attenuated Vaccine Candidate in Pearl Gentian Grouper - Huiming Tan; Fan Da; Guixiang Lin; Xiaoju Wan; Jichang Jian; Shuanghu Cai (Frontiers in Marine Science, 2022)
Vibrio alginolyticus ( V. alginolyticus ) is one of the important epizootic pathogens in marine animals. VAGM001033 belongs to a diguanylate cyclase, responsible for the synthesis of dimeric guanosine monophosphate (c-di-GMP), a ubiquitous second messenger involved in the function of biofilm formation, motility, and virulence. This study confirmed that VAGM001033 was an active diguanylate cyclase by Congo red assay. The red-stained, dry, and rough form of colonies were observed with the increasing concentration of the L-arabinose on Congo red plates. Also, an in-frame deleted Δ VAGM001033 mutant was constructed and changes of Δ VAGM001033 mutant in physiology and pathogenicity were detected. The Δ VAGM001033 mutant displayed similar morphology and growth curve with the wild-type strain showing no significant differences. The swarming ability of the Δ VAGM001033 mutant was significantly enhanced showing bigger swarming circles, while the biofilm formation, extracellular proteases, and virulence were significantly attenuated. The results of the test for antibiotic susceptibility showed that the wild type and Δ VAGM001033 mutant had similar sensitivity or resistance to most antibiotics used in this study, except cefotaxime and nitrofurantoin. The mutant was sensitive to cefotaxime and nitrofurantoin, while the wild type was intermediate. A total of 756 differentially expressed genes (DEGs) were identified by RNA-seq, of which 109 were upregulated and 647 were downregulated. Flagellar assembly, two-component system, ATP-binding cassette (ABC) transporters, and peptidoglycan biosynthesis were significantly enriched in the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway. Moreover, the Δ VAGM001033 mutant induced high antibody titers and provided immune protectivity with a relative percent survival (RPS) of 82%. Immune-related genes of pearl gentian grouper ( ♀Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus ), namely, IgM , MHC-I α, interleukin-1β ( IL-1 β), interleukin-16 ( IL-16 ), and tumor necrosis factor-α ( TNF- α) were upregulated after vaccination. Overall, the results suggested that VAGM001033 plays a crucial role in V. alginolyticus . The Δ VAGM001033 mutant might be applied as an effective live vaccine candidate against V. alginolyticus .

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

Association of genetic polymorphisms of VAX1, MAFB, and NTN1 with nonsyndromic cleft lip with or without cleft palate in Chinese population - Li Peng; Zhenmin Niu; Jiapei Chen; Teng Wan; Dandan Wu; Yusheng Yang; Guomin Wang; Lin Yang; Wei Huang; Zhenqi Chen (Molecular Genetics and Genomics, 2022)

Spatiotemporal distribution and the passive dispersal of fungal spores through HVAC systems - Wan-Rou Lin; Yung-Hung Ho; Wai Kwan Lee; Hsuan-Min Cheng; Pi-Han Wang (Aerobiologia, 2022)

The potential importance of soil denitrification as a major N loss pathway in intensive greenhouse vegetable production systems - Waqas Qasim; Yiming Zhao; Li Wan; Haofeng Lv; Shan Lin; Gretchen M. Gettel; Klaus Butterbach-Bahl (Plant and Soil, 2022)
Background About 30 % of vegetables in China are produced in intensively managed greenhouses comprising flood irrigation and extreme rates of nitrogen fertilizers. Little is known about denitrification N losses. Methods Soil denitrification rates were measured by the acetylene inhibition technique applied to anaerobically incubated soil samples. Four different greenhouse management systems were differentiated: Conventional flood irrigation and over-fertilization (CIF, 800 kg N ha −1 , 460 mm); CIF plus straw incorporation (CIF+S, 889 kg N ha −1 , 460 mm); Drip fertigation with reduced fertilizer application rates (DIF, 314 kg N ha −1 , 190 mm); DIF plus straw incorporation (DIF+S, 403 kg N ha −1 , 190 mm). Soil denitrification was measured on nine sampling dates during the growing season (Feb 2019-May 2019) for the top-/ subsoil (0 – 20/ 20- 40 cm) and on three sampling dates for deep soils (40-60/ 80-100 cm). Data was used to constrain N-input-output balances of the different vegetable production systems. Results Rates of denitrification were at least one magnitude higher in topsoil than in sub- and deep soils. Total seasonal denitrification N losses for the 0 – 40 cm soil layer ranged from 76 (DIF) to 422 kg N ha −1 (CIF+S). Straw addition stimulated soil denitrification in top- and subsoil, but not in deep soil layers. Integrating our denitrification data (0-100 cm) with additional data on N leaching, N 2 O emissions, plant N uptake, and NH 3 volatilization showed, that on average 50 % of added N fertilizers are lost due to denitrification. Conclusions Denitrification is likely the dominant environmental N loss pathway in greenhouse vegetable production systems. Reducing irrigation and fertilizer application rates while incorporating straw in soils allows the reduction of accumulated nitrate.

Common Subtype of Small Renal Mass MR Imaging Characterisation: A Medical Center Experience in Taiwan - Ming-Cheng Liu; Yi-Jui Liu; Yen-Ting Lin; Siu-Wan Hung; Jyh-Wen Chai; Si-Wa Chan; Kun-Yuan Chiu; Ya-Ling Tsou (Journal of Medical and Biological Engineering, 2022)
Purpose Many studies have shown that multiparametric magnetic resonance imaging (MRI) may be helpful for differentiating malignant renal cell carcinomas (RCCs) from benign lesions. However, the key imaging characteristics that differ between malignant and benign tumors still require further discussion. Methods We analyzed 60 adult patients diagnosed with 72 small renal masses (SRMs) who received preoperative MRI from 2014 to 2019 at a hospital in Taiwan. The MRI features included conventional MRI parameters, diffusion-weighted imaging (DWI) data, and dynamic contrast-enhanced (DCE) patterns, which were documented and compared among the four common subtypes: clear cell RCC (ccRCC), papillary RCC (pRCC), angiomyolipoma (AML) and other types of RCC. The apparent diffusion coefficient (ADC) values of high- and low-grade RCCs were also analyzed. Results The results show that ccRCC had higher T2-weighted signal intensity than the other three subgroups, a higher arterial wash-in index (AWI) and ADC value than AML and pRCC, and manifested a plateau ( n = 9, 25%) or washout (n = 27, 75%) enhancement pattern. AMLs exhibited more intravoxel fat than the other three subtype groups, and half of the AMLs (6 in 12) contained bulk fat. pRCC demonstrated a more progressive (n = 3, 60%) enhancement pattern than the other three subgroups. The ADC value of high-grade RCCs was significantly lower than that of low-grade RCCs. Conclusion These findings may indicate that multiparametric MRI is useful in differentiating among four common pathological types of SRMs, and the ADC value may be helpful in evaluating the histological grade of malignancy.

Pathogen resistance in Sphagneticola trilobata (Singapore daisy): molecular associations and differentially expressed genes in response to disease from a widespread fungus - Shan-Shan Qi; Bharani Manoharan; Vignesh Dhandapani; Sridharan Jegadeesan; Susan Rutherford; Justin S. H. Wan; Ping Huang; Zhi-Cong Dai; Dao-Lin Du (Genetica, 2022)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Changes in the growth performance, antioxidant enzymes and stress resistance caused by dietary administration of synbiotic (fructooligosaccharide and probiotics) in juvenile Chinese Mitten Crab, Eriocheir sinensis - Jin-Juan Wan; Jian-lin Pan; Mei-Fang Shen; Hui Xue; Meng-lin Sun; Mei-Qin Zhang; Xi-He Zhu; Xing-kong Ma (Aquaculture International, 2022)

An innovative targeted therapy for fluoroscopy-induced chronic radiation dermatitis - Kai-Che Wei; Shih-Fan Lai; Wei-Lun Huang; Kuo-Chung Yang; Ping-Chin Lai; Wan-Ju Wei; Tsung-Hsien Chang; Yun-Chen Huang; Ya-Chuan Tsai; Shin-Chih Lin; Sun-Jang Lin; Shih-Chieh Lin (Journal of Molecular Medicine, 2022)
Fluoroscopy-induced chronic radiation dermatitis (FICRD) is a complication of fluoroscopy-guided intervention. Unlike acute radiation dermatitis, FICRD is different as delayed onset and usually appears without preexisting acute dermatitis. Unfortunately, the chronic and progressive pathology of FICRD makes it difficult to treat, and some patients need to receive wide excision and reconstruction surgery. Due to lack of standard treatment, investigating underlying mechanism is needed in order to develop an effective therapy. Herein, the Hippo pathway is specifically identified using an RNA-seq analysis in mild damaged skin specimens of patients with FICRD. Furthermore, specific increase of the Yes-associated protein (YAP1), an effector of the Hippo pathway, in skin region with mild damage plays a protective role for keratinocytes via positively regulating the numerous downstream genes involved in different biological processes. Interestingly, irradiated-keratinocytes inhibit activation of fibroblasts under TGF-β1 treatment via remote control by an exosome containing YAP1. More importantly, targeting one of YAP1 downstream genes, nuclear receptor subfamily 3 group C member 1 (NR3C1), which encodes glucocorticoid receptor, has revealed its therapeutic potential to treat FICRD by inhibiting fibroblasts activation in vitro and preventing formation of radiation ulcers in a mouse model and in patients with FICRD. Taken together, this translational research demonstrates the critical role of YAP1 in FICRD and identification of a feasible, effective therapy for patients with FICRD. Key messages • YAP1 overexpression in skin specimens of radiation dermatitis from FICRD patient. • Radiation-induced YAP1 expression plays protective roles by promoting DNA damage repair and inhibiting fibrosis via remote control of exosomal YAP1. • YAP1 positively regulates NR3C1 which encodes glucocorticoid receptor expression. • Targeting glucocorticoid receptor by prednisolone has therapeutic potential for FICRD patient.

The Effects of Limosilactobacillus reuteri LR-99 Supplementation on Body Mass Index, Social Communication, Fine Motor Function, and Gut Microbiome Composition in Individuals with Prader–Willi Syndrome: a Randomized Double-Blinded Placebo-Controlled Trial - Xue-Jun Kong; Kevin Liu; Patrick Zhuang; Ruiyi Tian; Siyu Liu; Cullen Clairmont; Xiaojing Lin; Hannah Sherman; Junli Zhu; Yelan Wang; Michelle Fong; Alice Li; et al. (Probiotics and Antimicrobial Proteins, 2021)
Prader–Willi syndrome (PWS) is a rare genetic disorder associated with developmental delay, obesity, and neuropsychiatric comorbidities. Limosilactobacillus reuteri ( Lactobacillus reuteri , Lact. reuteri ) has demonstrated anti-obesity and anti-inflammatory effects in previous studies. In the present study, we aim to evaluate the effects of Lact. reuteri supplementation on body mass index (BMI), social behaviors, and gut microbiota in individuals with PWS. We conducted a 12-week, randomized, double-blind, placebo-controlled trial in 71 individuals with PWS aged 6 to 264 months (64.4 ± 51.0 months). Participants were randomly assigned to either receive daily Lact. reuteri LR-99 probiotic (6 × 10 10 colony forming units) or a placebo sachet. Groupwise differences were assessed for BMI, ASQ-3, and GARS-3 at baseline, 6 weeks, and 12 weeks into treatment. Gut microbiome data was analyzed with the QIIME2 software package, and predictive functional profiling was conducted with PICRUSt-2. We found a significant reduction in BMI for the probiotic group at both 6 weeks and 12 weeks relative to the baseline ( P < 0.05). Furthermore, we observed a significant improvement in social communication and interaction, fine motor function, and total ASQ-3 score in the probiotics group compared to the placebo group ( P < 0.05). Altered gut microbiota was observed in the probiotic group to favor weight loss and improve gut health. The findings suggest a novel therapeutic potential for Lact. reuteri LR-99 probiotic to modulate BMI, social behaviors, and gut microbiota in Prader–Willi syndrome patients, although further investigation is warranted. Trial registration Chinese Clinical Trial Registry: ChiCTR1900022646

Identification and characterization of L-type lectin receptor-like kinases involved in Glycine max–Phytophthora sojae interaction - Mengzhu Zeng; Bowen Wan; Lei Wang; Zhiyuan Chen; Yachun Lin; Wenwu Ye; Yan Wang; Yuanchao Wang (Planta, 2021)

Evolutionary characteristics and phylogeny of cotton chloroplast tRNAs - Ning Wang; Wan-Lin Dong; Xiao-Jing Zhang; Tong Zhou; Xiao-Juan Huang; Bao-Guo Li; Jian-Ni Liu; Xiong-Feng Ma; Zhong-Hu Li (Planta, 2021)

The r-X1 deletion induces terminal deficiencies in the maize B chromosome - Yen-Hua Huang; Tzu-Che Lin; Wan-Yi Chiou; Ya-Ming Cheng (Chromosome Research, 2021)

Mesenchymal stem cell-derived exosomes block malignant behaviors of hepatocellular carcinoma stem cells through a lncRNA C5orf66-AS1/microRNA-127-3p/DUSP1/ERK axis - Hao Gu; Chao Yan; Haijun Wan; Lin Wu; Junjie Liu; Zhiqiang Zhu; Dazhi Gao (Human Cell, 2021)

Untargeted metabolomic analysis of urine samples for diagnosis of inherited metabolic disorders - Hao Liu; Jiang Zhu; Qiu Li; Dongjuan Wang; Kexing Wan; Zhaojian Yuan; Juan Zhang; Lin Zou; Xiaoyan He; Jingkun Miao (Functional & Integrative Genomics, 2021)

The Decision Strategies of Adolescents with Different Emotional Stabilities in Unfair Situations - Yajing Si; Lin Jiang; Chanlin Yi; Qi Zhang; Cunbo Li; Jing Yu; Peiyang Li; Qiang Liu; Feng Wan; Fali Li; Dezhong Yao; Peng Xu (Neuroscience Bulletin, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Evaluation of the RNA extraction methods in different Ginkgo biloba L. tissues - Xiao-lin Zhang; Xiao-li Huang; Jia Li; Mei Mei; Wan-qi Zeng; Xiu-jun Lu (Biologia, 2021)

Prenylated xanthones and biphenyls from Garcinia esculenta with antistaphylococcal activity - Dan Zheng; Hong Zhang; Jia-Ming Jiang; Yu-Yu Chen; Shi-Jie Wan; Zhi-Xiu Lin; Hong-Xi Xu (Natural Product Research, 2021)

Design, synthesis, and antidepressant/anticonvulsant activities of 3H-benzo[f]chromen chalcone derivatives - Qiu-Wan Tan; Li-Ya He; Zhi-Wen He; Wei-Hua Liu; Shan-Shan Zhang; Lin Lin; Hong-Li Yang; Li-Ping Guan (Medicinal Chemistry Research, 2021)

Long non-coding RNA FGD5-AS1 enhances osteosarcoma cell proliferation and migration by targeting miR-506-3p/RAB3D axis - Congda Li; Xiangbo Lin; Caiyun Zhang; Lei Wan; Jijun Yin; Bin Wang (Human Cell, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

A ~ 230-year dust storm record from China’s Lake Gonghai on the northeast Loess Plateau - Lishuai Xu; Dejun Wan; Yonghong Duan; Yongchong Lin; Guijin Mu; Zhilei Zhen; Yongsheng Yang (Arabian Journal of Geosciences, 2021)

Germination dynamics of allergenic fungal spores in respiratory mucus - Wan-Rou Lin; Szu-Yu Chen; Shih-Ching Hsiao; Pi-Han Wang (Aerobiologia, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Genome-wide identification and expression analysis of the MADS-box transcription factor family in Camellia sinensis - Zai-Bao Zhang; Yuan-Jin Jin; Hou-Hong Wan; Lin Cheng; Zhi-Guo Feng (Journal of Applied Genetics, 2021)

Pomc Plays an Important Role in Sexual Size Dimorphism in Tilapia - Z. Y. Wan; V. C. L. Lin; Yue Gen Hua (Marine Biotechnology, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Clinical phenotypes combined with saturation genome editing identifying the pathogenicity of BRCA1 variants of uncertain significance in breast cancer - Qiting Wan; Li Hu; Tao Ouyang; Jinfeng Li; Tianfeng Wang; Zhaoqing Fan; Tie Fan; Benyao Lin; Ye Xu; Yuntao Xie (Familial Cancer, 2021)

Western North Pacific Tropical Cyclone Database Created by the China Meteorological Administration - Xiaoqin Lu; Hui Yu; Ming Ying; Bingke Zhao; Shuai Zhang; Limin Lin; Lina Bai; Rijin Wan (Advances in Atmospheric Sciences, 2021)
This paper describes the access to, and the content, characteristics, and potential applications of the tropical cyclone (TC) database that is maintained and actively developed by the China Meteorological Administration, with the aim of facilitating its use in scientific research and operational services. This database records data relating to all TCs that have passed through the western North Pacific (WNP) and South China Sea (SCS) since 1949. TC data collection has expanded over recent decades via continuous TC monitoring using remote sensing and specialized field detection techniques, allowing collation of a multi-source TC database for the WNP and SCS that covers a long period, with wide coverage and many observational elements. This database now comprises a wide variety of information related to TCs, such as historical or real-time locations (i.e., best track and landfall), intensity, dynamic and thermal structures, wind strengths, precipitation amounts, and frequency. This database will support ongoing research into the processes and patterns associated with TC climatic activity and TC forecasting.

Estimating Chinese residential populations from analysis of impervious surfaces derived from satellite images - Shan Wei; Yinyi Lin; Hongsheng Zhang; Luoma Wan; Hui Lin; Zhifeng Wu (International Journal of Remote Sensing, 2021)

Effects of Grazing, Wind Erosion, and Dust Deposition on Plant Community Composition and Structure in a Temperate Steppe - Mengmei Zheng; Jian Song; Jingyi Ru; Zhenxing Zhou; Mingxing Zhong; Lin Jiang; Dafeng Hui; Shiqiang Wan (Ecosystems, 2021)

Evaluation of reanalysis surface wind products with quality-assured buoy wind measurements along the north coast of the South China Sea - Jing Cha; Xinyu Lin; Xiaogang Guo; Xiaofang Wan; Dawei You (Acta Oceanologica Sinica, 2021)

High expression of NEK2 promotes gastric cancer progression via activating AKT signaling - Hao Wan; Lin Xu; Huangbin Zhang; Feixiang Wu; Weiqiang Zeng; Taiyuan Li (Journal of Physiology and Biochemistry, 2021)

Analysis of Meteorological Drought Resilience and Risk Assessment of Groundwater Using Signal Analysis Method - Yuan-Chien Lin; En-Dian Kuo; Wan-Ju Chi (Water Resources Management, 2021)

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

Overexpression of circ_0001445 decelerates hepatocellular carcinoma progression by regulating miR-942-5p/ALX4 axis - Qinhong Xu; Lijing Zhou; Ganghua Yang; Fandi Meng; Yong Wan; Lin Wang; Lei Zhang (Biotechnology Letters, 2020)

Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - Jie Lan; Qibing Lin; Chunlei Zhou; Yakun Ren; Xi Liu; Rong Miao; Ruonan Jing; Changling Mou; Thanhliem Nguyen; Xingjie Zhu; Qian Wang; Xin Zhang; et al. (Plant Molecular Biology, 2020)

Activation of p62-Keap1-Nrf2 Pathway Protects 6-Hydroxydopamine-Induced Ferroptosis in Dopaminergic Cells - Yiran Sun; Libo He; Taoyu Wang; Wan Hua; Huan Qin; Jingjin Wang; Li Wang; Wanqin Gu; Tingting Li; Na Li; Xinanbei Liu; Fang Chen; et al. (Molecular Neurobiology, 2020)

Genetic diversity analysis reveals new badnaviruses infecting banana in South China - Xue-Qin Rao; Zi-Lin Wu; Wan Wang; Lin Zhou; Jie Sun; Hua-Ping Li (Journal of Plant Pathology, 2020)

Effects of high-intensity interval training on gut microbiota profiles in 12 months’ old ICR mice - Guiping Wang; Huanhuan Zhou; Lin Zhang; Ruyi Li; Li Luo; Zengli Yu; Zhongxiao Wan (Journal of Physiology and Biochemistry, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Typical gene expression profile of pseudorabies virus reactivation from latency in swine trigeminal ganglion - Hai-Hua Wang; Jie Liu; Lin-Tao Li; Huan-Chun Chen; Wan-Po Zhang; Zheng-Fei Liu (Journal of NeuroVirology, 2020)

Neglect of Presence of Bacteria Leads to Inaccurate Growth Parameters of the Oligotrich Ciliate Strombidium sp. During Grazing Experiments on Nanoflagellates - Wan-Lin Chen; Kuo-Ping Chiang; Sheng-Fang Tsai (Frontiers in Marine Science, 2020)

Correction to: Telomerase reconstitution contributes to resetting of circadian rhythm in fibroblasts - Yi Qu; Meng Mao; Xihong Li; Yanyou Liu; Jianmin Ding; Zhou Jiang; Chaomin Wan; Lin Zhang; Zhengrong Wang; Dezhi Mu (Molecular and Cellular Biochemistry, 2020)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Rehabilitation effect of the combined application of bamboo biochar and coal ash on ion-adsorption-type rare earth tailings - Qin Zhang; Guangyue Wan; Caiyun Zhou; Jie Luo; Jianping Lin; Xiaomin Zhao (Journal of Soils and Sediments, 2020)

Functional analysis of miR-767-5p during the progression of hepatocellular carcinoma and the clinical relevance of its dysregulation - Lei Zhang; Zhimin Geng; Yong Wan; Fandi Meng; Xiankui Meng; Lin Wang (Histochemistry and Cell Biology, 2020)

Drug vector representation: a tool for drug similarity analysis - Liping Lin; Luoyao Wan; Huaqin He; Wei Liu (Molecular Genetics and Genomics, 2020)

A novel hydrogel for highly efficient adsorption of Cu(II): synthesis, characterization, and mechanisms - Jun Wan; Lin Chen; Qiang Li; Yuxuan Ye; Xiaonan Feng; Aijiao Zhou; Xuejun Long; Dongsheng Xia; Tian C. Zhang (Environmental Science and Pollution Research, 2020)

Epidemiological and genetic characteristics of porcine reproduction and respiratory syndrome virus 2 in mainland China, 2017–2018 - Sisi Xie; Wan Liang; Xueying Wang; Hongjian Chen; Jie Fan; Wenbo Song; Lin Hua; Xibiao Tang; Huanchun Chen; Zhong Peng; Bin Wu (Archives of Virology, 2020)

Grenville-age orogenic event along the northeastern margin of the Quanji massif, NW China: constraints from ~1.1 Ga migmatite - Zhouxuan Xiao; Licheng Ma; Wan Jiang; Ran Wang; Yuyan Yao; Jie Cai; Jingyu Lin; Lu Li (Geosciences Journal, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

Effects of Elevated Ozone Concentrations on Root Characteristics and Soil Properties of Elaeocarpus sylvestris and Michelia chapensis - Lan Pan; Wan-qi Lin; Ming Yu; Gan-wen Lie; Li Xue; Hong-yue Chen (Bulletin of Environmental Contamination and Toxicology, 2020)

Correction to: Whole Exome Sequencing Identifies Two Novel Mutations in the Reticulon 4–Interacting Protein 1 Gene in a Chinese Family with Autosomal Recessive Optic Neuropathies - Xiao-Huan Zou; Xin-Xin Guo; Hui-Zhen Su; Chong Wang; En-Lin Dong; Ning Wang; Wan-Jin Chen; Qi-Jie Zhang (Journal of Molecular Neuroscience, 2020)

Cross-Strait climate change and agricultural product loss - Hsing-Chun Lin; Li-Chen Chou; Wan-Hao Zhang (Environmental Science and Pollution Research, 2020)

High prevalence and viremia of human pegivirus 2 in the HIV-infected population in Honghe Prefecture, Yunnan Province - Tianyi Li; Shixing Tang; Yingying Su; Zuoyi Bao; Xiaolin Wang; Yongjian Liu; Hanping Li; Jingwan Han; Zhichao Pei; Zhengwei Wan; Hang Fan; Yigang Tong; et al. (Archives of Virology, 2020)

Characterization of Fracture Process in Sandstone: A Linear Correspondence Between Acoustic Emission Energy Density and Opening Displacement Gradient - Qing Lin; Siqi Wang; Bin Wan; Yunhu Lu; Yan Wang (Rock Mechanics and Rock Engineering, 2020)

Allelopathy confers an invasive Wedelia higher resistance to generalist herbivore and pathogen enemies over its native congener - Shan-Shan Qi; Yan-Jie Liu; Zhi-Cong Dai; Ling-Yun Wan; Dao-Lin Du; Rui-Ting Ju; Justin S. H. Wan; Stephen P. Bonser (Oecologia, 2020)

Applying Iterative Method to Solving High-Order Terms of Seafloor Topography - Diao Fan; Shanshan Li; Shuyu Meng; Yi Lin; Zhibin Xing; Chi Zhang; Junjun Yang; Xiaoyun Wan; Zhenhao Qu (Marine Geodesy, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Study on adverse effects of groundwater level rising induced by land creation engineering in hilly and gully area of the Loess Plateau - Xu Duan; Qi Dong; Wan-jun Ye; Jia-lin Zhou; Erwin Oh (Journal of Mountain Science, 2019)

Age Matters: an Atypical Association Between Polymorphism of MTHFR and Clinical Phenotypes in Children with Schizophrenia - Lin Wan; Yuhong Li; Yuming Zhou; Rena Li; Yi Zheng (Journal of Molecular Neuroscience, 2019)

Adsorption Removal of Cr(VI) with Activated Carbon Prepared by Co-pyrolysis of Rice Straw and Sewage Sludge with ZnCl2 Activation - Liangqian Fan; Wenxin Wan; Xianda Wang; Jie Cai; Fenghui Chen; Wei Chen; Lin Ji; Hongbing Luo; Lin Cheng (Water, Air, & Soil Pollution, 2019)

Three new Coccomyces species from Shennongjia National Nature Reserve in China - Tu Lv; Wan-Peng Tang; Shu-Rui Cai; Cheng-Lin Hou (Mycological Progress, 2019)

Using two contrasting methods with the same tracers to trace the main sediment source in a mountainous catchment - Han Wu; Dong-hong Xiong; Su Zhang; Yong Yuan; Wan-Xin Li; Lin Liu; Zheng-an Su; Xiao-ning Lu (Journal of Mountain Science, 2019)

Profiling the microbial contamination in aviation fuel from an airport - Dong Hu; Wenfang Lin; Jie Zeng; Peng Wu; Menglu Zhang; Lizheng Guo; Chengsong Ye; Kun Wan; Xin Yu (Biofouling, 2019)

The effects of simulated deposited nitrogen on nutrient dynamics in decomposing litters across a wide quality spectrum using a 15N tracing technique - Xue-Min Ye; Yang Zhang; Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Xiao-Fan Lin; Song-Ze Wan; Ping He (Plant and Soil, 2019)

Liposome production and concurrent loading of drug simulants by microfluidic hydrodynamic focusing - Wan-Zhen Sophie Lin; Noah Malmstadt (European Biophysics Journal, 2019)

The impact and mechanism of quaternary ammonium compounds on the transmission of antibiotic resistance genes - Yue Han; Zhen-Chao Zhou; Lin Zhu; Yuan-Yuan Wei; Wan-Qiu Feng; Lan Xu; Yang Liu; Ze-Jun Lin; Xin-Yi Shuai; Zhi-Jian Zhang; Hong Chen (Environmental Science and Pollution Research, 2019)

Interpreting air temperature generated from urban climatic map by urban morphology in Taipei - Yu-Cheng Chen; Tzu-Wen Lo; Wan-Yu Shih; Tzu-Ping Lin (Theoretical and Applied Climatology, 2019)

Thymosin Alpha-1 Inhibits Complete Freund’s Adjuvant-Induced Pain and Production of Microglia-Mediated Pro-inflammatory Cytokines in Spinal Cord - Yunlong Xu; Yanjun Jiang; Lin Wang; Jiahua Huang; Junmao Wen; Hang Lv; Xiaoli Wu; Chaofan Wan; Chuanxin Yu; Wenjie Zhang; Jiaying Zhao; Yinqi Zhou; et al. (Neuroscience Bulletin, 2019)

Steroid-Enriched Fraction of Achyranthes bidentata Protects Amyloid β Peptide 1–40-Induced Cognitive Dysfunction and Neuroinflammation in Rats - Li-Wei Lin; Fan-Hsuan Tsai; Wan-Cheng Lan; Yih-Dih Cheng; Sheng-Chi Lee; Chi-Rei Wu (Molecular Neurobiology, 2019)

Whole Exome Sequencing Identifies Two Novel Mutations in the Reticulon 4–Interacting Protein 1 Gene in a Chinese Family with Autosomal Recessive Optic Neuropathies - Xiao-Huan Zou; Xin-Xin Guo; Hui-Zhen Su; Chong Wang; En-Lin Dong; Ning Wang; Wan-Jin Chen; Qi-Jie Zhang (Journal of Molecular Neuroscience, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Expression and localization of MrgprD in mouse intestinal tract - Chenxing Zhou; Jia Li; Lin Liu; Zongxiang Tang; Fengyi Wan; Lei Lan (Cell and Tissue Research, 2019)

Environment‐ and trait‐mediated scaling of tree occupancy in forests worldwide - Haibao Ren; Petr Keil; Xiangcheng Mi; Keping Ma; Zhanqing Hao; Wanhui Ye; Luxiang Lin; Renato Valencia; Christine Dawn Fletcher; Duncan W. Thomas; Robert W. Howe; James Lutz; et al. (Global Ecology and Biogeography, 2019)
Aim The relationship between the proportion of sites occupied by a species and the area of a site [occupancy–area relationship (OAR)] offers key information for biodiversity management and has long fascinated ecologists. We quantified the variation in OAR for 3,157 woody species in 17 forest plots worldwide and tested the relative importance of environment and species traits for explaining this variation and evaluated overall model predictive ability. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We used mixed‐effect regression to examine the observed shape of the OAR (its “slope”) against species‐specific and plot‐wide predictors: coarse‐grain occupancy, tree size, plot species richness, energy availability and topographic complexity. Results We found large variation in OAR slopes, and the variation was strongest among species within plots. The OAR slopes showed a latitudinal trend and were steeper near the equator. As predicted, coarse‐grain occupancy and tree size negatively affected OAR slopes, whereas species richness had a positive effect and explained most of the variance between plots. Although hypothesized directionalities were broadly confirmed, traits and environment had relatively limited overall predictive power. Main conclusions These results document the variation of the OAR for 3,157 species at near‐global extent. We found a latitudinal gradient in OAR slopes and confirmed key hypothesized predictors. But at this global extent and over the large set of species analysed, the remaining unexplained variation in OAR slopes was substantial. Nevertheless, this large‐scale empirical analysis of the OAR offers an initial step towards a more general use of OARs for the fine‐scale prediction of species distributions and abundance.

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Development of InDel Markers for Identification of a Single Mendelian Locus Controlling Leaf Shape in Kenaf (Hibiscus cannabinus) - Liemei Zhang; Xuebei Wan; Lilan Zhang; Yi Xu; Jiantang Xu; Lihui Lin; Jianmin Qi; Liwu Zhang (Tropical Plant Biology, 2019)

Bacillus thuringiensis targets the host intestinal epithelial junctions for successful infection of Caenorhabditis elegans - Liting Wan; Jian Lin; Hongwen Du; Yulan Zhang; Alejandra Bravo; Mario Soberón; Ming Sun; Donghai Peng (Environmental Microbiology, 2019)
Summary Pathogenic bacteria use different strategies to infect their hosts, including the simultaneous production of pore forming toxins and several virulence factors that may synergize their pathogenic effects. However, how the pathogenic bacteria are able to break out the host intestinal barrier is poorly understood. The infectious cycle of Bacillus thuringiensis (Bt) bacterium in Caenorhabditis elegans is a powerful model system to study the early stages of the infection process. Bt produces Cry pore‐forming toxins during the sporulation phase that are key virulence factors involved in its pathogenesis. In this study, we show that Bt disrupts the intestinal epithelial junctions of C. elegans at early stages of infection allowing Bt bacterium to complete its life cycle in the worm. We further confirmed that the vegetative Bt cells trigger a quorum sensing response that is activated by PlcR regulator, resulting in production of different virulence factors, such as the metalloproteinases ColB and Bmp1, that besides Cry toxins are necessary to disrupt the nematode epithelial junctions causing efficient bacterial host infection and death of the nematode. Our work provides new insights into the pathogenesis of Bt and highlights the importance of breaking down host epithelial junctions for a successful infection. A similar mechanism could be used by other pathogen‐host interactions since epithelial junctions are conserved structures from insects to mammals.

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

The Mycobacterial Adjuvant Analogue TDB Attenuates Neuroinflammation via Mincle-Independent PLC-γ1/PKC/ERK Signaling and Microglial Polarization - Mahendravarman Mohanraj; Ponarulselvam Sekar; Horng-Huei Liou; Shwu-Fen Chang; Wan-Wan Lin (Molecular Neurobiology, 2019)

Changes of mycorrhizal fungal community occurring during the natural restoration after the chi-chi earthquake in Taiwan - Tzu-Chao Lin; Pi-Han Wang; Wan-Rou Lin (Symbiosis, 2019)

The analgesic effect and possible mechanisms by which koumine alters type II collagen-induced arthritis in rats - Gui-Lin Jin; Jian Yang; Wan-Qing Chen; Jie Wang; Hong-Qiang Qiu; Ying Xu; Chang-Xi Yu (Journal of Natural Medicines, 2019)

Insights into removal of tetracycline by persulfate activation with peanut shell biochar coupled with amorphous Cu-doped FeOOH composite in aqueous solution - Jian Xu; Xueliang Zhang; Cheng Sun; Jinzhong Wan; Huan He; Fei Wang; Yuxuan Dai; Shaogui Yang; Yusuo Lin; Xinhua Zhan (Environmental Science and Pollution Research, 2019)

The influences of industrial gross domestic product, urbanization rate, environmental investment, and coal consumption on industrial air pollutant emission in China - Wei-yu Zhou; Wen-lin Yang; Wen-xin Wan; Jing Zhang; Wei Zhou; Hao-shen Yang; Hua Yang; Hong Xiao; Shi-huai Deng; Fei Shen; Ying-jun Wang (Environmental and Ecological Statistics, 2018)

Investigation on fatal accidents in Chinese construction industry between 2004 and 2016 - Wan-Lin Meng; Shuilong Shen; Annan Zhou (Natural Hazards, 2018)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Detection, sequence analysis, and antibody prevalence of porcine deltacoronavirus in Taiwan - Tien-Huan Hsu; Hao-Ping Liu; Chieh-Yu Chin; Chinling Wang; Wan-Zhen Zhu; Bing-Lin Wu; Yu-Chung Chang (Archives of Virology, 2018)

Mangrove Species Discrimination from Very High Resolution Imagery Using Gaussian Markov Random Field Model - Luoma Wan; Hongsheng Zhang; Ting Wang; Gang Li; Hui Lin (Wetlands, 2018)

The Divalent Elements Changes in Early Stages of Chronic Kidney Disease - Wan-Ju Kung; Ching-Tang Shih; Chien-Hung Lee; Ching-Chiang Lin (Biological Trace Element Research, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Multiscale analyses on a massive immigration process of Sogatella furcifera (Horváth) in south-central China: influences of synoptic-scale meteorological conditions and topography - Qiu-Lin Wu; John K. Westbrook; Gao Hu; Ming-Hong Lu; Wan-Cai Liu; Gregory A. Sword; Bao-Ping Zhai (International Journal of Biometeorology, 2018)

Modeling and multi-objective optimization for ANAMMOX process under COD disturbance using hybrid intelligent algorithm - Bin Xie; Yong-wen Ma; Jin-quan Wan; Yan Wang; Zhi-cheng Yan; Lin Liu; Ze-yu Guan (Environmental Science and Pollution Research, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

c.835-5T>G Variant in SMN1 Gene Causes Transcript Exclusion of Exon 7 and Spinal Muscular Atrophy - Shuang Wu; Yun-Lu Li; Ning-Yi Cheng; Chong Wang; En-Lin Dong; Ying-Qian Lu; Jin-Jing Li; Xin-Xin Guo; Xiang Lin; Lu-Lu Lai; Zhi-Wei Liu; Ning Wang; et al. (Journal of Molecular Neuroscience, 2018)

Effects of nitrogen during nursery stage on flower bud differentiation and early harvest after transplanting in strawberry - Chunyan Wan; Lin Mi; Bingyi Chen; Jinfeng Li; Hengzhi Huo; Jintao Xu; Xueping Chen (Brazilian Journal of Botany, 2018)

OPEN GLUME1: a key enzyme reducing the precursor of JA, participates in carbohydrate transport of lodicules during anthesis in rice - Xiaohui Li; Yihua Wang; Erchao Duan; Qi Qi; Kunneng Zhou; Qiuyun Lin; Di Wang; Yunlong Wang; Wuhua Long; Zhigang Zhao; Zhijun Cheng; Cailin Lei; et al. (Plant Cell Reports, 2018)

Genomic analysis of a recombinant NADC30-like porcine reproductive and respiratory syndrome virus in china - Lin-jian Wang; Bo Wan; Zhenhua Guo; Songlin Qiao; Rui Li; Sha Xie; Xin-xin Chen; Gaiping Zhang (Virus Genes, 2018)

Intramuscular Delivery of scAAV9-hIGF1 Prolongs Survival in the hSOD1G93A ALS Mouse Model via Upregulation of D-Amino Acid Oxidase - HuiQian Lin; HaoJie Hu; WeiSong Duan; YaLing Liu; GuoJun Tan; ZhongYao Li; YaKun Liu; BinBin Deng; XueQin Song; Wan Wang; Di Wen; Ying Wang; et al. (Molecular Neurobiology, 2018)

Variations of Laohugou Glacier No. 12 in the western Qilian Mountains, China, from 1957 to 2015 - Yu-shuo Liu; Xiang Qin; Ji-zu Chen; Zhen-lin Li; Jing Wang; Wen-tao Du; Wan-qin Guo (Journal of Mountain Science, 2018)

Differential hydric deficit responses of Robinia pseudoacacia and Platycladus orientalis in pure and mixed stands in northern China and the species interactions under drought - Lin Wang; Yongxin Dai; Jiazhe Sun; Xianchong Wan (Trees, 2017)

Finite element simulations of different hamstring tendon graft lengths and related fixations in anterior cruciate ligament reconstruction - Chao Wan; Zhixiu Hao; Zhichang Li; Jianhao Lin (Medical & Biological Engineering & Computing, 2017)

Transcriptome Profiling Reveals the Important Role of Exogenous Nitrogen in Alleviating Cadmium Toxicity in Poplar Plants - Fan Zhang; Junqiang Li; Jinliang Huang; Lihua Lin; Xueqin Wan; Jinglong Zhao; Jifei Dong; Lingxia Sun; Qibing Chen (Journal of Plant Growth Regulation, 2017)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Effects of normoxic and hypoxic exercise regimens on lymphocyte apoptosis induced by oxidative stress in sedentary males - Jong-Shyan Wang; Yi-Ching Chen; Wan-Ling Chen; Chin-Pu Lin (European Journal of Applied Physiology, 2017)

Analysis of gene expression and functional characterization of XPR1: a pathogenic gene for primary familial brain calcification - Xiang-Ping Yao; Miao Zhao; Chong Wang; Xin-Xin Guo; Hui-Zhen Su; En-Lin Dong; Hai-Ting Chen; Jing-Hui Lai; Yao-Bin Liu; Ning Wang; Wan-Jin Chen (Cell and Tissue Research, 2017)

Comparison of the effectiveness of resistance training in women with chronic computer-related neck pain: a randomized controlled study - Xiao Li; Caina Lin; Cuicui Liu; Songjian Ke; Qing Wan; Haijie Luo; Zhuxi Huang; Wenjun Xin; Chao Ma; Shaoling Wu (International Archives of Occupational and Environmental Health, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

ACOS5 is required for primexine formation and exine pattern formation during microsporogenesis in Arabidopsis - Hui-hui Xie; Lin Chen; Fa-qing Xu; Wan-sheng Guo; Shui Wang; Zhong-nan Yang; Sen Zhang (Journal of Plant Biology, 2017)

Quantification of mycotoxins in vegetable oil by UPLC-MS/MS after magnetic solid-phase extraction - Yan Zhao; Li-Hong Wan; Xiao-Lin Bai; Yi-Ming Liu; Feng-Ping Zhang; Yao-Min Liu; Xun Liao (Food Additives & Contaminants: Part A, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Novel avian leukosis viruses from domestic chicken breeds in mainland China - Hongxia Shao; Lin Wang; Jianjun Sang; Tuofan Li; Yuelong Liu; Zhimin Wan; Kun Qian; Aijian Qin; Jianqiang Ye (Archives of Virology, 2017)

Decolorization of textile dye RB19 using volcanic rock matrix immobilized Bacillus thuringiensis cells with surface displayed laccase - Juan Wan; Xiaowen Sun; Cheng Liu; Mengjun Tang; Lin Li; Hong Ni (World Journal of Microbiology and Biotechnology, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Involvement of FMRP in Primary MicroRNA Processing via Enhancing Drosha Translation - Rui-Ping Wan; Lin-Tao Zhou; Hai-Xuan Yang; Yong-Ting Zhou; Shun-Hua Ye; Qi-Hua Zhao; Mei-Mei Gao; Wei-Ping Liao; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2017)

Dimeric furanocoumarins from the roots of Angelica dahurica - Wan-Qing Yang; Zhi-Xiang Zhu; Yue-Lin Song; Bo-Wen Qi; Juan Wang; Cong Su; Peng-Fei Tu; She-Po Shi (Natural Product Research, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Effects of soybean meal processing treatments on growth performance, nutrient digestibility, nitrogen and phosphorus excretion in red swamp crayfish, Procambarus clarkii - Jin-juan Wan; Mei-fang Shen; Jian-qing Tang; Hai Lin; Wei-hui Yan; Jia-jia Li; Lin Zhu (Aquaculture International, 2017)

An Experimental Investigation into the Effects of the Anisotropy of Shale on Hydraulic Fracture Propagation - Chong Lin; Jianming He; Xiao Li; Xiaole Wan; Bo Zheng (Rock Mechanics and Rock Engineering, 2017)

Comparative Efficacy and Safety of Nine Anti-Platelet Therapies for Patients with Ischemic Stroke or Transient Ischemic Attack: a Mixed Treatment Comparisons - Hua-Pin Huang; Wan-Hui Lin; Sheng-Gen Chen; Li-Zhen Chen; Min-Yi Chen; Chun-Hui Che (Molecular Neurobiology, 2017)

PGRN Is Associated with Late-Onset Alzheimer’s Disease: a Case–Control Replication Study and Meta-analysis - Hui-Min Xu; Lin Tan; Yu Wan; Meng-Shan Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Ecotoxicological bioassays of sediment leachates in a river bed flanked by decommissioned pesticide plants in Nantong City, East China - Yan Zhou; Fenghe Wang; Jinzhong Wan; Jian He; Qun Li; Qiang Chen; Jay Gao; Yusuo Lin; Shengtian Zhang (Environmental Science and Pollution Research, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Ommaya reservoir in the treatment of cryptococcal meningitis - Baozhu Wei; Cheng Qian; Yang Liu; Xuan Lin; Jing Wan; Yanggan Wang (Acta Neurologica Belgica, 2017)

Dissolution sequestration mechanism of CO2 at the Shiqianfeng saline aquifer in the Ordos Basin, northwestern China - Yuyu Wan; Shanghai Du; Guangyu Lin; Fengjun Zhang; Tianfu Xu (Arabian Journal of Geosciences, 2017)

Daytime warming lowers community temporal stability by reducing the abundance of dominant, stable species - Zhongling Yang; Qian Zhang; Fanglong Su; Chunhui Zhang; Zhichao Pu; Jianyang Xia; Shiqiang Wan; Lin Jiang (Global Change Biology, 2017)
Daytime warming and nighttime warming have the potential to influence plant community structure and ecosystem functions. However, their impacts on ecological stability remain largely unexplored. We conducted an eight‐year field experiment to compare the effects of daytime and nighttime warming on the temporal stability of a temperate steppe in northern China. Our results showed that the cover and stability of dominant species, stability of subordinate species, and compensatory dynamics among species strongly influenced community‐level stability. However, daytime, but not nighttime, warming significantly reduced community temporal stability mainly through the reduction in the abundance of dominant, stable species. These findings demonstrate the differential effects of daytime and nighttime warming on community stability and emphasize the importance of understanding the changes of dominant species for accurately predicting community dynamics under climate warming.

Molecular characterization and expression analysis of AMPK α subunit isoform genes from Scophthalmus maximus responding to salinity stress - Lin Zeng; Bin Liu; Chang-Wen Wu; Ji-Lin Lei; Mei-Ying Xu; Ai-Yi Zhu; Jian-She Zhang; Wan-Shu Hong (Fish Physiology and Biochemistry, 2016)

Soil properties and species composition under different grazing intensity in an alpine meadow on the eastern Tibetan Plateau, China - Zhen’an Yang; Wan Xiong; Yingyi Xu; Lin Jiang; Erxiong Zhu; Wei Zhan; Yixin He; Dan Zhu; Qiuan Zhu; Changhui Peng; Huai Chen (Environmental Monitoring and Assessment, 2016)

WSL3, a component of the plastid-encoded plastid RNA polymerase, is essential for early chloroplast development in rice - Liwei Wang; Chunming Wang; Yihua Wang; Mei Niu; Yulong Ren; Kunneng Zhou; Huan Zhang; Qibing Lin; Fuqing Wu; Zhijun Cheng; Jiulin Wang; Xin Zhang; et al. (Plant Molecular Biology, 2016)

Tetramethylpyrazine Promotes Migration of Neural Precursor Cells via Activating the Phosphatidylinositol 3-Kinase Pathway - Xiangying Kong; Micun Zhong; Xiaohui Su; Qingxia Qin; Hongchang Su; Hongye Wan; Cuiling Liu; Jiajia Wu; Hongcai Shang; Yanjun Zhang; Na Lin (Molecular Neurobiology, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

The catalytic subunit of magnesium-protoporphyrin IX monomethyl ester cyclase forms a chloroplast complex to regulate chlorophyll biosynthesis in rice - Weiyi Kong; Xiaowen Yu; Haiyuan Chen; Linglong Liu; Yanjia Xiao; Yunlong Wang; Chaolong Wang; Yun Lin; Yang Yu; Chunming Wang; Ling Jiang; Huqu Zhai; et al. (Plant Molecular Biology, 2016)

Wax crystal-sparse leaf 3 encoding a β-ketoacyl-CoA reductase is involved in cuticular wax biosynthesis in rice - Lu Gan; Xiaole Wang; Zhijun Cheng; Linglong Liu; Jiulin Wang; Zhe Zhang; Yulong Ren; Cailin Lei; Zhichao Zhao; Shanshan Zhu; Qibing Lin; Fuqing Wu; et al. (Plant Cell Reports, 2016)

A new phenolic compound with antioxidant activity from the branches and leaves of Pyrus pashia - Zhen-Jie Li; Xi Zheng; Chun-Ping Wan; Le Cai; Ying Li; Lin Huang; Zhong-Tao Ding (Natural Product Research, 2016)

Pollen and seed flow under different predominant winds in wind-pollinated and wind-dispersed species Engelhardia roxburghiana - Zheng-Feng Wang; Ju-Yu Lian; Wan-Hui Ye; Hong-Lin Cao; Qian-Mei Zhang; Zhang-Ming Wang (Tree Genetics & Genomes, 2016)

Oasis microclimate effect on the dust deposition in Cele Oasis at southern Tarim Basin, China - Lishuai Xu; Guijin Mu; Xiao Ren; Dejun Wan; Junxia He; Yongchong Lin (Arabian Journal of Geosciences, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Inhibition of AMPK through Lyn-Syk-Akt enhances FcεRI signal pathways for allergic response - Kai-Chun Lin; Duen-Yi Huang; De-Wei Huang; Shiang-Jong Tzeng; Wan-Wan Lin (Journal of Molecular Medicine, 2016)

Tumor MICA status predicts the efficacy of immunotherapy with cytokine-induced killer cells for patients with gastric cancer - Yu Chen; Wan-song Lin; Wei-feng Zhu; Jing Lin; Zhi-feng Zhou; Chuan-zhong Huang; Gang Chen; Yi Shi; Zeng-qing Guo; Yun-bin Ye (Immunologic Research, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

The RNA-binding protein Sam68 regulates tumor cell viability and hepatic carcinogenesis by inhibiting the transcriptional activity of FOXOs - Tingting Zhang; Chunhua Wan; Weidong Shi; Jian Xu; Hui Fan; Shusen Zhang; Zhipeng Lin; Runzhou Ni; Xiubing Zhang (Journal of Molecular Histology, 2015)

Ecological status classification of the Taizi River Basin, China: a comparison of integrated risk assessment approaches - Juntao Fan; Elena Semenzin; Wei Meng; Elisa Giubilato; Yuan Zhang; Andrea Critto; Alex Zabeo; Yun Zhou; Sen Ding; Jun Wan; Mengchang He; Chunye Lin (Environmental Science and Pollution Research, 2015)

Protein complex and proteomic profile in the roots of Oryza sativa L. in response to cadmium toxicity - Shoukai Lin; Weifeng Wan; Tian Tian; Yuxia Wang; Qiulin Liu; Wenfeng Zhang; Yufang Ai; Lichun Xue; Huaqin He (Acta Physiologiae Plantarum, 2015)

Peanut violaxanthin de-epoxidase alleviates the sensitivity of PSII photoinhibition to heat and high irradiance stress in transgenic tobacco - Sha Yang; De-Yun Meng; Lin-Lin Hou; Yan Li; Feng Guo; Jing-Jing Meng; Shu-Bo Wan; Xin-Guo Li (Plant Cell Reports, 2015)

Altered microRNA Expression in Peripheral Blood Mononuclear Cells from Young Patients with Schizophrenia - Hui-min Fan; Xin-yang Sun; Wei Niu; Lin Zhao; Qiao-Li Zhang; Wan-shuai Li; Ai-fang Zhong; Li-yi Zhang; Jim Lu (Journal of Molecular Neuroscience, 2015)

The determination of sex type of the cultured murine cell with quantitative PCR technique - Qian Wan; Liang Ni; Lintao Wu; Lin Zhang; Mianxue Liu; Xiaohui Jiang (Human Cell, 2015)

Experimental Investigation About Influence of Pre-existing Fracture on Hydraulic Fracture Propagation Under Tri-axial Stresses - Wan Cheng; Yan Jin; Qing Lin; Mian Chen; Yakun Zhang; Ce Diao; Bing Hou (Geotechnical and Geological Engineering, 2015)

Pectobacterium chrysanthemi as the dominant causal agent of bacterial soft rot in Oncidium “Grower Ramsey” - Yi-Hsien Lin; Pei-Ju Lee; Wan-Ting Shie; Lih-Ling Chern; Yung-Chun Chao (European Journal of Plant Pathology, 2015)

Mapping QTLs related to rice seed storability under natural and artificial aging storage conditions - Ngo Thi Hang; Qiuyun Lin; Linglong Liu; Xi Liu; Shijia Liu; Wenyan Wang; Linfang Li; Niqing He; Zhou Liu; Ling Jiang; Jianmin Wan (Euphytica, 2015)

Duodenal Neuroendocrine Carcinoma Presenting with Disseminated Liver and Bone Metastases as the Primary Manifestation: Case Report and Literature Review - Tao Guo; Ka Kei Ng; Hoi Wan Chiang; Man Fei Ma; Yi Lin; Jia Ming Qian (Cell Biochemistry and Biophysics, 2015)

Gene knockout of glutathione reductase 3 results in increased sensitivity to salt stress in rice - Tsung-Meng Wu; Wan-Rong Lin; Ching Huei Kao; Chwan-Yang Hong (Plant Molecular Biology, 2015)

Erratum to: Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2015)

Simultaneous reduction in incidence of Bemisia tabaci (Hemiptera: Aleyrodidae) and Sylepta derogata (Lepidoptera: Pyralidae) using velvetleaf, Abutilon theophrasti as a trap crop - Kejian Lin; Yanhui Lu; Peng Wan; Yizhong Yang; Kris A. G. Wyckhuys; Kongming Wu (Journal of Pest Science, 2015)

Construction of knowledge-based spatial decision support system for landslide mapping using fuzzy clustering and KPSO analysis - Shiuan Wan; Jia Yi Yen; Cho Yi Lin; Tein Yin Chou (Arabian Journal of Geosciences, 2015)

Response of archaeal communities to water regimes under simulated warming and drought conditions in Tibetan Plateau wetlands - Jianqing Tian; Chi Shu; Huai Chen; Yuchen Qiao; Gang Yang; Wan Xiong; Lin Wang; Jingzu Sun; Xingzhong Liu (Journal of Soils and Sediments, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Up- and Down-regulated Expression of OsCPK25/26 Results in Increased Number of Stamens in Rice - Wei Zhang; Bingliang Wan; Fei Zhou; Hao Chen; Xianghua Li; Yongjun Lin (Plant Molecular Biology Reporter, 2014)

Permian ultrafelsic A-type granite from Besar Islands group, Johor, peninsular Malaysia - Azman A Ghani; Fatin Izzani Hazad; Azmiah Jamil; Quek Long Xiang; Wan Nur Atiqah Wan Ismail; Sun-Lin Chung; Yu-Ming Lai; Muhammad Hatta Roselee; Nur Islami; Kyaw Kyaw Nyein; Meor Hakif Amir Hassan; Mohd Farid Abu Bakar; et al. (Journal of Earth System Science, 2014)

Genetic diversity and identification of race 3 of Fusarium oxysporum f. sp. lactucae in Taiwan - Ying-Hong Lin; Po-Jung Lai; Tao-Ho Chang; Yu-Ling Wan; Jenn-Wen Huang; Jin-Hsing Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2014)

Verification of serological relationship between two phylogenetically related peanut-infecting Tospovirus species - Ya-Chi Kang; Shyi-Dong Yeh; Chih-Hsuan Liao; Wan-Chen Chou; Fang-Lin Liu; Jia-Hong Dong; Tsung-Chi Chen (European Journal of Plant Pathology, 2014)

Association Study Between Macrophage Migration Inhibitory Factor-173 Polymorphism and Acute Myeloid Leukemia in Taiwan - Latha Ramireddy; Chien-Yu Lin; Su-Ching Liu; Wan-Yu Lo; Rouh-Mei Hu; Yi-Chin Peng; Ching-Tien Peng (Cell Biochemistry and Biophysics, 2014)

Long-term monitoring and modeling of polychlorinated dibenzo-p-dioxins and dibenzofurans from municipal solid waste incinerators and surrounding area in northern Taiwan - Hsiao-Hsuan Mi; Wan-Ju Wang; Sheng-Lun Lin; Yi-Chieh Lai; John Kennedy Mwangi; Lin Chi Wang; Guo-Ping Chang-Chien (Environmental Science and Pollution Research, 2014)

Novel quasi-subgenotype D2 of hepatitis B virus identified in Taiwanese aborigines - Huy Tran; Ming-Lung Yu; Chia-Yen Dai; I-Ling Lin; Ming-Lun Yeh; Wan-Long Chuang; Kenji Abe (Virus Genes, 2014)

OsLOX2, a rice type I lipoxygenase, confers opposite effects on seed germination and longevity - Jiexue Huang; Maohong Cai; Qizhang Long; Linglong Liu; Qiuyun Lin; Ling Jiang; Saihua Chen; Jianmin Wan (Transgenic Research, 2014)

Differential Regulation of Lipid Metabolism Genes in the Brain of Acetylcholinesterase Knockout Mice - Huang-Quan Lin; Yan Wang; Kam-Leung Chan; Tsz-Ming Ip; Chi-Cheong David Wan (Journal of Molecular Neuroscience, 2014)

Characteristics of endogenous γ-aminobutyric acid (GABA) in human platelets: functional studies of a novel collagen glycoprotein VI inhibitor - Kuan-Hung Lin; Wan-Jung Lu; Shwu-Huey Wang; Tsorng-Harn Fong; Duen-Suey Chou; Chao-Chien Chang; Nen-Chung Chang; Yung-Chen Chiang; Shih-Yi Huang; Joen-Rong Sheu (Journal of Molecular Medicine, 2014)

Differential expression of speckled POZ protein, SPOP: Putative regulation by miR-145 - Chiu-Jung Huang; Hsing-Yu Chen; Wan-Yi Lin; Kong Bung Choo (Journal of Biosciences, 2014)

Increased risk of colorectal malignant neoplasm in patients with nonalcoholic fatty liver disease: a large study - Xian-Feng Lin; Ke-Qing Shi; Jie You; Wen-Yue Liu; Ying-Wan Luo; Fa-Ling Wu; Yong-Ping Chen; Danny Ka-Ho Wong; Man-Fung Yuen; Ming-Hua Zheng (Molecular Biology Reports, 2014)

miR-27b targets LIMK1 to inhibit growth and invasion of NSCLC cells - Li Wan; Lin Zhang; Kai Fan; Jianjun Wang (Molecular and Cellular Biochemistry, 2014)

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite - Ya-Ting Chao; Chun-Lin Su; Wen-Han Jean; Wan-Chieh Chen; Yao-Chien Alex Chang; Ming-Che Shih (Plant Molecular Biology, 2014)

Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2014)

3D-QSAR study on 2,3-dihydroimidazo[4,5]-pyridin-2-one derivatives with a meta substitution pattern as V600EBRAF inhibitors - Xiaoyun Wu; Shanhe Wan; Zhonghuang Li; Lin Yang; Jiajie Zhang; Shuguang Wu (Medicinal Chemistry Research, 2014)

The relationship between typhoons' peripheral circulation and ground-level ozone concentrations in central Taiwan - Wan-Li Cheng; Li-Wei Lai; Walter Den; Meng-Ting Wu; Chao-An Hsueh; Pay-Liam Lin; Chueh-Ling Pai; Yeou-Lih Yan (Environmental Monitoring and Assessment, 2014)

Development of elite rice restorer lines in the genetic background of R022 possessing tolerance to brown planthopper, stem borer, leaf folder and herbicide through marker-assisted breeding - Bingliang Wan; Zhongping Zha; Jinbo Li; Mingyuan Xia; Xueshu Du; Yongjun Lin; Desuo Yin (Euphytica, 2014)

Genetic diversity and hybridization of Pulsatilla tongkangensis based on the nrDNA ITS region sequence - Yan-Lin Sun; Wan-Geun Park; Hyun-Kyung Oh; Soon-Kwan Hong (Biologia, 2014)

Antibacterial mechanisms of methyl gallate against Ralstonia solanacearum - Wan-Wan Fan; Gao-Qing Yuan; Qi-Qin Li; Wei Lin (Australasian Plant Pathology, 2014)

EGCG inhibit chemical reactivity of iron through forming an Ngal–EGCG–iron complex - Guan-Hu Bao; Jie Xu; Feng-Lin Hu; Xiao-Chun Wan; Shi-Xian Deng; Jonathan Barasch (BioMetals, 2013)

Isolation, Identification and Characterization of Lactic Acid Bacteria From Shao-jiou-luo (Fermented Zoned Cerith), a Traditional Fermented Food in Taiwan - Yi-Sheng Chen; Hui-Chung Wu; Huei-Yin Lo; Wen-Hsuan Hsu; Wan-Chen Lin; Bo-Ya Lin (Journal of Aquatic Food Product Technology, 2013)

γ-Aminobutyric acid (GABA) homeostasis regulates pollen germination and polarized growth in Picea wilsonii - Yu Ling; Tong Chen; Yanping Jing; Lusheng Fan; Yinglang Wan; Jinxing Lin (Planta, 2013)

Identification and characterization of a novel chloroplast/mitochondria co-localized glutathione reductase 3 involved in salt stress response in rice - Tsung-Meng Wu; Wan-Rong Lin; Yun-Ting Kao; Yi-Ting Hsu; Ching-Hui Yeh; Chwan-Yang Hong; Ching Huei Kao (Plant Molecular Biology, 2013)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

Liver proteomic analysis of the large yellow croaker (Pseudosciaena crocea) following polyriboinosinic:polyribocytidylic acid induction - Yinnan Mu; Xiang Wan; Kebing Lin; Jingqun Ao; Xinhua Chen (Fish Physiology and Biochemistry, 2013)

Polycyclic aromatic hydrocarbons in water, sediment and soil of the Songhua River Basin, China - Wan-Li Ma; Li-Yan Liu; Hong Qi; Zi-Feng Zhang; Wei-Wei Song; Ji-Min Shen; Zhong-Lin Chen; Nan-Qi Ren; Josey Grabuski; Yi-Fan Li (Environmental Monitoring and Assessment, 2013)

qLTG-9, a stable quantitative trait locus for low-temperature germination in rice (Oryza sativa L.) - Linfang Li; Xi Liu; Kun Xie; Yihua Wang; Feng Liu; Qiuyun Lin; Wenyan Wang; Chunyan Yang; Bingyue Lu; Shijia Liu; Liangming Chen; Ling Jiang; et al. (Theoretical and Applied Genetics, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Effectiveness of participatory training for prevention of musculoskeletal disorders: a randomized controlled trial - Wenzhou Yu; Ignatius T. S. Yu; Xiaorong Wang; Zhimin Li; Sabrina Wan; Hong Qiu; Hui Lin; Shaohua Xie; Trevor Sun (International Archives of Occupational and Environmental Health, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

hPNAS-4 inhibits proliferation through S phase arrest and apoptosis: underlying action mechanism in ovarian cancer cells - Lei Li; Den-bang Chen; Chao Lin; Kang Cao; Yang Wan; Xin-yu Zhao; Chun-lai Nie; Zhu Yuan; Yu-quan Wei (Apoptosis, 2013)

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

BEAK LIKE SPIKELET1 is Required for Lateral Development of Lemma and Palea in Rice - Xiaoding Ma; Zhijun Cheng; Fuqing Wu; Mingna Jin; Liguo Zhang; Feng Zhou; Jiulin Wang; Kunneng Zhou; Jian Ma; Qibing Lin; Cailin Lei; Jianmin Wan (Plant Molecular Biology Reporter, 2013)

Alteration of discoidin domain receptor-2 expression: possible role in peroxynitrite-induced apoptosis in human cerebral vascular smooth muscle cells - Lin Li; Zhiyong Yue; Xiaojuan Wan; Guodong Zhang; Shasha Song; Xiaohui Bai; Yulian Jiao; Yuanrong Ju; Jianfeng Li (Molecular & Cellular Toxicology, 2012)

Albumin prevents reactive oxygen species-induced mitochondrial damage, autophagy, and apoptosis during serum starvation - Shu-Yu Liu; Chia-Ling Chen; Tsan-Tzu Yang; Wei-Ching Huang; Chia-Yuan Hsieh; Wan-Jou Shen; Tsung-Ting Tsai; Chi-Chang Shieh; Chiou-Feng Lin (Apoptosis, 2012)

Constitutive activation of STAT3 is predictive of poor prognosis in human gastric cancer - Hua Xiong; Wan Du; Ji-Lin Wang; Ying-Chao Wang; Jie-Ting Tang; Jie Hong; Jing-Yuan Fang (Journal of Molecular Medicine, 2012)

An analytical investigation of a sequence of unusual springtime ozone episodes over metropolitan Taichung in 2007 - Wan-Li Cheng; Li-Wei Lai; Walter Den; Shu-Ying Wang; Pay-Liam Lin; Chueh-Ying Pai (Meteorology and Atmospheric Physics, 2012)

Fasudil, a Rho-kinase inhibitor, protects against excessive endurance exercise training-induced cardiac hypertrophy, apoptosis and fibrosis in rats - Tsung-Jung Ho; Chi-Chang Huang; Chih-Yang Huang; Wan-Teng Lin (European Journal of Applied Physiology, 2012)

Disruption of Bombyx mori nucleopolyhedrovirus ORF71 (Bm71) results in inefficient budded virus production and decreased virulence in host larvae - Min-Juan Zhang; Ruo-Lin Cheng; Yi-Han Lou; Wan-Lu Ye; Tao Zhang; Xiao-Ying Fan; Hai-Wei Fan; Chuan-Xi Zhang (Virus Genes, 2012)

A dynamic evolution of chromosome in subgenus Potamogeton revealed by physical mapping of rDNA loci detection - Tao Wan; Xiao-lin Zhang; Juraj Gregan; Ying Zhang; Pin Guo; You-hao Guo (Plant Systematics and Evolution, 2012)

Quercetin modulates activities of Taiwan cobra phospholipase A2 via its effects on membrane structure and membrane-bound mode of phospholipase A2 - Yi-Ling Chiou; Shinne-Ren Lin; Wan-Ping Hu; Long-Sen Chang (Journal of Biosciences, 2012)

Diversity‐dependent stability under mowing and nutrient addition: evidence from a 7‐year grassland experiment - Haijun Yang; Lin Jiang; Linghao Li; Ang Li; Mingyu Wu; Shiqiang Wan (Ecology Letters, 2012)
Ecology Letters (2012) Abstract Anthropogenic perturbations may affect biodiversity and ecological stability as well as their relationships. However, diversity–stability patterns and associated mechanisms under human disturbances have rarely been explored. We conducted a 7‐year field experiment examining the effects of mowing and nutrient addition on the diversity and temporal stability of herbaceous plant communities in a temperate steppe in northern China. Mowing increased population and community stability, whereas nutrient addition had the opposite effects. Stability exhibited positive relationships with species richness at population, functional group and community levels. Treatments did not alter these positive diversity–stability relationships, which were associated with the stabilising effect of species richness on component populations, species asynchrony and portfolio effects. Despite the difficulty of pinpointing causal mechanisms of diversity–stability patterns observed in nature, our results suggest that diversity may still be a useful predictor of the stability of ecosystems confronted with anthropogenic disturbances.

PDGF-induced airway smooth muscle proliferation is associated with Human antigen R activation and could be weakened by AMPK activation - Pengju Zhang; Mingfeng Cao; Yi Liu; Zhimei Lv; Qingrui Yang; Xiaoyan Lin; Huaichen Li; Qiang Wan (Molecular Biology Reports, 2012)

Experimental study on the effect of waves on netting panels at a range of angles to the wave direction - Wei-hua Song; Zhen-lin Liang; Rong Wan; Fen-Fang Zhao; Kinoshita Takeshi; Liu-yi Huang; Jia-zhi Ma; Bo-hai Chen (Fisheries Science, 2012)

Persistent sodium current and Na+/H+ exchange contributes to the augmentation of the reverse Na+/Ca2+ exchange during hypoxia or acute ischemia in ventricular myocytes - Qiong Tang; Jihua Ma; Peihua Zhang; Wei Wan; Linghao Kong; Lin Wu (Pflügers Archiv - European Journal of Physiology, 2012)

Transcriptional analysis and functional characterization of XCC1294 gene encoding a GGDEF domain protein in Xanthomonas campestris pv. campestris - Yi-Min Hsiao; Wan-Ling Song; Chao-Tsai Liao; I-Hsuan Lin; Mei-Ying Pan; Ching-Fen Lin (Archives of Microbiology, 2012)

Quantitative assessment of the effect of ABCA1 R219K polymorphism on the risk of coronary heart disease - Yang Li; Kefu Tang; Kejun Zhou; Zhiyun Wei; Zhen Zeng; Lin He; Chunling Wan (Molecular Biology Reports, 2012)

Variations in thermal physiology and energetics of the tree shrew (Tupaia belangeri) in response to cold acclimation - Lin Zhang; Peng-fei Liu; Wan-long Zhu; Jin-hong Cai; Zheng-kun Wang (Journal of Comparative Physiology B, 2012)

Role of nitric oxide in amphetamine-induced sensitization of schedule-induced polydipsic rats - Yia-Ping Liu; Che-Se Tung; Pai-Jone Lin; Fang-Jung Wan (Psychopharmacology, 2011)

Hepatitis B virus X protein enhances activation of nuclear factor κB through interaction with valosin-containing protein - Bo-Yan Jiao; Wan-Song Lin; Fei-Fei She; Wan-Nan Chen; Xu Lin (Archives of Virology, 2011)

Identification and characterization of differential gene expression in the mesocarp and kernel of oil palm nuts using suppression subtractive hybridization - Li Xu; Yijun Yuan; Lin Zhang; Li Wan; Yusheng Zheng; Peng Zhou; Dongdong Li (Tree Genetics & Genomes, 2011)

New cytotoxic oxygenated sterols from marine bryozoan Bugula neritina - Fan Yang; Hong-Jun Zhang; Jian-Tao Chen; Hai-Feng Tang; Shu-Juan Piao; Wan-Sheng Chen; Hou-Wen Lin (Natural Product Research, 2011)

Genetic evidence for involvement of the alternative sigma factor SigI in controlling expression of the cell wall hydrolase gene lytE and contribution of LytE to heat survival of Bacillus subtilis - Chi-Ling Tseng; Jung-Tze Chen; Ju-Hui Lin; Wan-Zhen Huang; Gwo-Chyuan Shaw (Archives of Microbiology, 2011)

Study on roughness coefficient for unsubmerged reed in the Changjiang Estuary - Fengfeng Gu; Lin Mu; Dingman Qi; Junhua Li; Lingshuang Kong; Yuanyang Wan (Acta Oceanologica Sinica, 2011)

Idebenone inhibition of glutamate release from rat cerebral cortex nerve endings by suppression of voltage-dependent calcium influx and protein kinase A - Yi Chang; Yu-Wan Lin; Su-Jane Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

An easy and efficient protocol in the production of pflp transgenic banana against Fusarium wilt - Mei-Kuen Yip; Sin-Wan Lee; Kuei-Ching Su; Yi-Hsien Lin; Tai-Yang Chen; Teng-Yung Feng (Plant Biotechnology Reports, 2011)

Genetic diversity of the apolipoprotein E gene and diabetic nephropathy: a meta-analysis - Yang Li; Kefu Tang; Zhao Zhang; Ming Zhang; Zhen Zeng; Zangdong He; Lin He; Chunling Wan (Molecular Biology Reports, 2011)

A hybrid strategy to integrate surface-based and mutual-information-based methods for co-registering brain SPECT and MR images - Yuan-Lin Liao; Yung-Nien Sun; Wan-Yuo Guo; Yuan-Hwa Chou; Jen-Chuen Hsieh; Yu-Te Wu (Medical & Biological Engineering & Computing, 2011)

Increased intracellular calcium concentration causes electrical turbulence in guinea pig ventricular myocytes - XinRong Fan; JiHua Ma; Wei Wan; PeiHua Zhang; Chao Wang; Lin Wu (Science China Life Sciences, 2011)

Overexpression of SlCZFP1, a Novel TFIIIA-type Zinc Finger Protein from Tomato, Confers Enhanced Cold Tolerance in Transgenic Arabidopsis and Rice - Xin Zhang; Xiuping Guo; Cailin Lei; Zhijun Cheng; Qibin Lin; Jiulin Wang; Fuqing Wu; Jie Wang; Jianmin Wan (Plant Molecular Biology Reporter, 2011)

Grassland responses to grazing: effects of grazing intensity and management system in an Inner Mongolian steppe ecosystem - Philipp Schönbach; Hongwei Wan; Martin Gierus; Yongfei Bai; Katrin Müller; Lijun Lin; Andreas Susenbeth; Friedhelm Taube (Plant and Soil, 2011)

H2S Protects Hippocampal Neurons from Anoxia–Reoxygenation Through cAMP-Mediated PI3K/Akt/p70S6K Cell-Survival Signaling Pathways - Jian-Lin Shao; Xiao-Hong Wan; Yan Chen; Chun Bi; Hong-Mei Chen; Ying Zhong; Xin-Hua Heng; Jin-Qiao Qian (Journal of Molecular Neuroscience, 2011)

Celecoxib induces heme oxygenase-1 expression in macrophages and vascular smooth muscle cells via ROS-dependent signaling pathway - Jang-Shiun Wang; Feng-Ming Ho; Hao-Cheng Kang; Wan-Wan Lin; Kuo-Chin Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

The effect of excess expression of GFP in a novel heart-specific green fluorescence zebrafish regulated by nppa enhancer at early embryonic development - Wen Huang; Yun Deng; Wei Dong; Wuzhou Yuan; Yongqi Wan; Xiaoyan Mo; Yongqing Li; Zequn Wang; Yuequn Wang; Karen Ocorr; Bo Zhang; Shuo Lin; et al. (Molecular Biology Reports, 2011)

Point patterns of tree distribution determined by habitat heterogeneity and dispersal limitation - Yi-Ching Lin; Li-Wan Chang; Kuoh-Cheng Yang; Hsiang-Hua Wang; I-Fang Sun (Oecologia, 2011)

Three novel SNPs in the coding region of PPARγ gene and their associations with meat quality traits in cattle - Yue Yuan Fan; Lin Sen Zan; Chang Zhen Fu; Wan Qiang Tian; Hong Bao Wang; Yan Yan Liu; Ya Ping Xin (Molecular Biology Reports, 2011)

Change of air quality and its impact on atmospheric visibility in central-western Pearl River Delta - Jun-Ming Wan; Mang Lin; Chuen-Yu Chan; Zhi-Sheng Zhang; Guenter Engling; Xue-Mei Wang; Iat-Neng Chan; Shi-Yu Li (Environmental Monitoring and Assessment, 2011)

Genetic polymorphisms of the DNA repair geneMPG may be associated with susceptibility to rheumatoid arthritis - S. Y. Chen; L. Wan; C. M. Huang; Y. C. Huang; J. J. C. Sheu; Y. J. Lin; S. P. Liu; Y. C. Lan; C. H. Lai; C. W. Lin; C. H. Tsai; F. J. Tsai (Journal of Applied Genetics, 2010)

Activation of PPARδ promotes mitochondrial energy metabolism and decreases basal insulin secretion in palmitate-treated β-cells - Li Jiang; Jun Wan; Lin-qiu Ke; Qing-guo Lü; Nan-wei Tong (Molecular and Cellular Biochemistry, 2010)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

Subcellular localization of Mitf in monocytic cells - Ssu-Yi Lu; Hsiao-Ching Wan; Mengtao Li; Yi-Ling Lin (Histochemistry and Cell Biology, 2010)

Dual bio-responsive gene delivery via reducible poly(amido amine) and survivin-inducible plasmid DNA - Ran Namgung; Jonathan H. Brumbach; Ji Hoon Jeong; James W. Yockman; Sung Wan Kim; Chao Lin; Zhiyuan Zhong; Jan Feijen; Johan F. J. Engbersen; Won Jong Kim (Biotechnology Letters, 2010)

Temporally and spatially controlled expression of transgenes in embryonic and adult tissues - Qian Zhang; Aleata A. Triplett; Don W. Harms; Wan-Chi Lin; Bradley A. Creamer; Angie Rizzino; Kay-Uwe Wagner (Transgenic Research, 2010)

Isolation of new esters from the stems of Cinnamomum reticulatum Hay - Iung-Jr Lin; Wen-Li Lo; Yi-Chen Chia; Lee-Yu Huang; Thau-Ming Cham; Wan-Shan Tseng; Yu-Ting Yeh; Hung-Chun Yeh; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

Registration of Micro-Computed Tomography and Histological Images of the Guinea Pig Cochlea to Construct an Ear Model Using an Iterative Closest Point Algorithm - Chia-Fone Lee; Gen-Jia Li; Shu-Yen Wan; Wen-Jeng Lee; Kai-Yuan Tzen; Chiung-Hsiang Chen; Yu-Lin Song; Yuan-Fang Chou; Yuh-Shyang Chen; Tien-Chen Liu (Annals of Biomedical Engineering, 2010)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

Assessing the prospects of genome-wide association studies performed in inbred mice - Wan-Lin Su; Solveig K. Sieberts; Robert R. Kleinhanz; Karine Lux; Joshua Millstein; Cliona Molony; Eric E. Schadt (Mammalian Genome, 2010)

Metabolomics investigation of exercise-modulated changes in metabolism in rat liver after exhaustive and endurance exercises - Chi-Chang Huang; Wan-Teng Lin; Feng-Lin Hsu; Pi-Wen Tsai; Chia-Chung Hou (European Journal of Applied Physiology, 2010)

A meta-analysis of oxidative stress markers in schizophrenia - Ming Zhang; ZhongMing Zhao; Lin He; ChunLing Wan (Science China Life Sciences, 2010)

A novel polymorphism of GDF5 gene and its association with body measurement traits in Bos taurus and Bos indicus breeds - Yong Feng Liu; Lin Sen Zan; Kui Li; Shuan Ping Zhao; Ya Ping Xin; Qing Lin; Wan Qiang Tian; Zhi Wei Wang (Molecular Biology Reports, 2010)

Endurance training accelerates exhaustive exercise-induced mitochondrial DNA deletion and apoptosis of left ventricle myocardium in rats - Chi-Chang Huang; Tien-Jen Lin; Chun-Chieh Chen; Wan-Teng Lin (European Journal of Applied Physiology, 2009)

Isolation and characterization of microsatellites in Chinese white olive (Canarium album) and cross-species amplification in Canarium pimela - Xin Zhang; Wan-Hui Ye; Hong-Lin Cao; Zheng-Feng Wang; Hao Shen; Ju-Yu Lian (Conservation Genetics, 2009)

Biological impact of harmaline, ricinine and their combined effects with Bacillus thuringiensis on Spodoptera exigua (Lepidoptera: Noctuidae) - Muhammad Rizwan-ul-Haq; Qiong Bo Hu; Mei Ying Hu; Qing Shen Lin; Wan Li Zhang (Journal of Pest Science, 2009)

Antagonism between abscisic acid and ethylene in Arabidopsis acts in parallel with the reciprocal regulation of their metabolism and signaling pathways - Wan-Hsing Cheng; Ming-Hau Chiang; San-Gwang Hwang; Pei-Chi Lin (Plant Molecular Biology, 2009)

Isolation and characterization of microsatellite markers for Cycas hainanensis C. J. Chen (Cycadaceae) - Min Zhang; Zheng-Feng Wang; Shu-Guang Jian; Wan-Hui Ye; Hong-Lin Cao; Peng Zhu; Ling Li (Conservation Genetics, 2009)

Isolation and characterization of ten polymorphic microsatellite in the endangered tree Erythrophleum fordii oliv - Peng Zhu; Wan-Hui Ye; Zheng-Feng Wang; Hong-Lin Cao; Min Zhang; Ling Li; Wei Xiao (Conservation Genetics, 2009)

KIFC1 participates in acrosomal biogenesis, with discussion of its importance for the perforatorium in the Chinese mitten crab Eriocheir sinensis - Keming Yu; Lin Hou; Jun-Quan Zhu; Xue-Ping Ying; Wan-Xi Yang (Cell and Tissue Research, 2009)

Deletion analysis of the C-terminal region of a molecular chaperone DnaK from Bacillus licheniformis - Wan-Chi Liang; Min-Guan Lin; Meng-Chun Chi; Hui-Yu Hu; Huei-Fen Lo; Hui-Ping Chang; Long-Liu Lin (Archives of Microbiology, 2009)

Expression profile of calcium-dependent protein kinase (CDPKs) genes during the whole lifespan and under phytohormone treatment conditions in rice (Oryza sativa L. ssp. indica) - Shuifeng Ye; Lei Wang; Weibo Xie; Bingliang Wan; Xianghua Li; Yongjun Lin (Plant Molecular Biology, 2009)

Analysis of the mechanisms underlying the endothelium-dependent antivasoconstriction of puerarin in rat aorta - Li-Ping Yan; Yu-Lan Zhuang; Shun-Wan Chan; Shi-Lin Chen; Gang-Gang Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

A 70-kDa molecular chaperone, DnaK, from the industrial bacterium Bacillus licheniformis: gene cloning, purification and molecular characterization of the recombinant protein - Wan-Chi Liang; Xuan-Hui Wang; Min-Guan Lin; Long-Liu Lin (Indian Journal of Microbiology, 2009)

Proteome alteration of U251 human astrocytoma cell after inhibiting retinoic acid synthesis - Ming Zhang; Chunling Wan; Baohu Ji; Zhao Zhang; Hui Zhu; Nan Tian; Yujuan La; Ke Huang; Lei Jiang; Guang He; Linhan Gao; Xinzhi Zhao; et al. (Molecular and Cellular Biochemistry, 2009)

Interaction between SARS-CoV helicase and a multifunctional cellular protein (Ddx5) revealed by yeast and mammalian cell two-hybrid systems - Jin-Yan Chen; Wan-Nan Chen; Kwok-Man Vincent Poon; Bo-Jian Zheng; Xu Lin; Yong-Xiang Wang; Yu-Mei Wen (Archives of Virology, 2009)

Nonlinear cooperation of p53-ING1-induced bax expression and protein S-nitrosylation in GSNO-induced thymocyte apoptosis: a quantitative approach with cross-platform validation - Shaojin Duan; Lin Wan; Wenjiang J. Fu; Hong Pan; Qi Ding; Chang Chen; Peiwei Han; Xiaoyan Zhu; Liying Du; Hongxiao Liu; Yuxia Chen; Ximing Liu; et al. (Apoptosis, 2009)

Elevated expression of L-selectin ligand in lymph node-derived human prostate cancer cells correlates with increased tumorigenicity - Prakash Radhakrishnan; Ming-Fong Lin; Pi-Wan Cheng (Glycoconjugate Journal, 2009)

Eighteen novel polymorphic microsatellite loci developed from the Père David’s deer (Elaphurus davidianus) - Hai-Long Wu; Xiao-Wei Ni; Lin-Yuan Zhang; Jin-Shi Xia; Zhen-Yu Zhong; Guo-Ping Zhu; Qiu-Hong Wan (Conservation Genetics, 2008)

Identification and characterization of EST-SSRs and cpSSRs in endangered Cycas hainanensis - Zheng-Feng Wang; Wan-Hui Ye; Hong-Lin Cao; Zhong-Chao Li; Shao-Lin Peng (Conservation Genetics, 2008)

Telomerase reconstitution contributes to resetting of circadian rhythm in fibroblasts - Yi Qu; Meng Mao; Xihong Li; Yanyou Liu; Jianmin Ding; Zhou Jiang; Chaomin Wan; Lin Zhang; Zhengrong Wang; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

Cloning and expression of selenocysteine methyltransferase cDNA from Camellia sinensis - Lin Zhu; Chang-Jun Jiang; Wei-Wei Deng; Xuan Gao; Rang-Jian Wang; Xiao-Chun Wan (Acta Physiologiae Plantarum, 2008)

A new cytotoxic cholesterol sulfate from marine sponge Halichondria rugosa - Hong-Jun Zhang; Jing-Bo Sun; Hou-Wen Lin; Zeng-Lei Wang; Hua Tang; Ping Cheng; Wan-Sheng Chen; Yang-Hua Yi (Natural Product Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Interleukin-18 gene polymorphism, but not interleukin-2 gene polymorphism, is associated with rheumatoid arthritis - Cheng-Chun Lee; Wei-Yong Lin; Lei Wan; Yuhsin Tsai; Ying-Ju Lin; Chang-Hai Tsai; Chung-Ming Huang; Fuu-Jen Tsai (Immunogenetics, 2007)

Real-time imaging of viable-apoptotic switch in GSNO-induced mouse thymocyte apoptosis - Dan-ying Lin; Wan-yun Ma; Shao-jin Duan; Yan Zhang; Li-ying Du (Apoptosis, 2006)

Mutation analysis of 218 Chinese patients with Wilson disease revealed no correlation between the canine copper toxicosis gene MURR1 and Wilson disease - Zhi-Ying Wu; Gui-Xian Zhao; Wan-Jin Chen; Ning Wang; Bo Wan; Min-Ting Lin; Shen-Xing Murong; Long Yu (Journal of Molecular Medicine, 2006)

Grassland degradation in Northern Tibet based on remote sensing data - Qingzhu Gao; Yu’e Li; Yunfan Wan; Erda Lin; Wei Xiong; Wangzha Jiangcun; Baoshan Wang; Wenfu Li (Journal of Geographical Sciences, 2006)

Mineralogical and geochemical study of a newly discovered mafic granulite, northwest China: Implications for tectonic evolution of the Altay Orogenic Belt - Han‐Lin Chen; Zi‐Long Li; Shu‐Feng Yang; Chuan‐Wan Dong; Wen‐Jiao Xiao; Yoshiaki Tainosho (Island Arc, 2006)
A mafic granulite body was newly discovered in the Altay Orogenic Belt, northwest China. The rocks comprise a suite of coarse‐grained and fine‐grained granulites. Orthopyroxenes (hypersthenes) in the rocks have high X Mg and low Al 2 O 3 contents, whereas clinopyroxenes have low TiO 2 and Al 2 O 3 contents. Amphiboles and biotites have a high Mg/(Mg + Fe 2+ ) ratio and low contents of F and Cl. The peak metamorphic pressure–temperature (P–T) conditions are estimated as 750–780°C and 6–7 kbar, and retrograde P–T conditions are in the range of 590–620°C and 2.3–3.7 kbar, indicating significant decompression. Metamorphic reactions and P–T estimates define a clockwise P–T path. Geochemically, the rocks are high in Mg/(Mg + Fe) and Al 2 O 3 , depleted in U, Th, K and Rb, and characterized by light rare earth element enrichment and a weak positive Eu anomaly. The Altay mafic granulite shows depleted Nb, P and Ti contents in the mid‐oceanic ridge basalt normalized spider diagram. The geochemical characteristics suggest that the protolith of the Altay mafic granulite was calc‐alkaline basalt and andesite with an island‐arc affinity. The rock has a high 143 Nd/ 144 Nd ratio with ɛNd(0) > 0, indicating derivation from a mantle‐depleted source. In the present study, a two‐stage model for the evolution of the Altay mafic granulite is proposed: an early stage in which calc‐alkaline basalt and andesite with island‐arc affinity were subducted into a deeper level of the crust and subjected to granulite‐facies metamorphism generating the mafic granulite, followed by the later stage exhumation of the system into the upper crust by the late Paleozoic thrusting.

An efficient protocol for plant regeneration from protoplasts of the moss Atrichum undulatum P. Beauv in vitro - Lin-Hui Li; Xian-Ping Wang; Wan-Ru Hou; Xiang-Lin Liu; Yi-Kun He (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Stabilization of a truncated Bacillus sp. strain TS-23 α-amylase by replacing histidine-436 with aspartate - Huei-Fen Lo; Ya-Hui Chen; Nai-Wan Hsiao; Hsiang-Ling Chen; Hui-Yu Hu; Wen-Hwei Hsu; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

An interspecific somatic hybrid between Actinidia chinensis and Actinidia kolomikta and its chilling tolerance - Zun-an Xiao; Lin-chen Wan; Bi-wen Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Type III secretion of EspB in enterohemorrhagic Escherichia coli O157:H7 - Hao-Jie Chiu; Wen-Shiun Lin; Wan-Jr Syu (Archives of Microbiology, 2003)

Tidal front and the convergence of anchovy ( Engraulis japonicus ) eggs in the Yellow Sea - Wei Hao; Su Jian; Wan Ruijing; Wang Lei; Lin Yi'an (Fisheries Oceanography, 2003)
Anchovy recruitment determines fish production and thus the sustainable exploitation of anchovy in the Yellow Sea. Haizhou Bay is a traditional spawning and nursery ground for anchovy. The retention of anchovy in its early life stages appears to be related to observed fronts. Cruises have confirmed that anchovy eggs are distributed in high density patches, particularly in the tidal frontal zone. Front and egg patches shift to the shallow area in the warm season. A diagnostic Hamburg Shelf Ocean Model was applied in the East China Sea and Yellow Sea to simulate the frontal circulation and particle movement, forced by monthly wind speed and measured temperatures. It was observed that the jet along the front and upwelling in the mixed side of the front play an important role in the transport of eggs. Convergence and divergence areas are frequently induced by frontal shear instability and topography potential vorticity balance. Numerical experiments show that tidal mixing and front play an important role to converge particles like eggs. When eggs are caught in the convergence zone they are aggregated into a patch. The convergence zone has good feeding condition for eggs to hatch and larvae to grow.

Detection and analysis of QTLs for ferrous iron toxicity tolerance in rice, Oryza sativa L. - Jian-lin Wan; Hu-qu Zhai; Jian-min Wan; H. Ikehashi (Euphytica, 2003)

Chloroplast Transformation in Oilseed Rape - Bing-Kai Hou; Yi-Hua Zhou; Li-Hong Wan; Zhong-Lin Zhang; Gui-Fang Shen; Zheng-Hua Chen; Zan-Min Hu (Transgenic Research, 2003)

Oxidation of elemental sulfur in paddy soils as influenced by flooded condition and plant growth in pot experiment - Wei Zhou; Min Wan; Ping He; Shutian Li; Bao Lin (Biology and Fertility of Soils, 2002)

Downregulation of PTEN/MMAC/TEP1 expression in human prostate cancer cell line DU145 by growth stimuli - Dhundy R. Bastola; Gurcharan S. Pahwa; Ming-Fong Lin; Pi-Wan Cheng (Molecular and Cellular Biochemistry, 2002)

Spatial correlation analysis of crop yield in the middle and west of Jilin Province - Lin-yi Li; Zhao-li Liu; Chun-lin Li; En-pu Wan (Chinese Geographical Science, 2002)

Unexpectedly high coral coverage in Chinwan Inner Bay, Pescadores: a proposed site for a Marine Protection Area - Hernyi Hsieh; Nuwei Wei; Yi-lin Lu; Ming-Shiu Jeng; Wan-Shen Tsai; Chaolun Chen (Coral Reefs, 2001)

Characterization of stress-responsive genes, hrcA-grpE-dnaK-dnaJ , from phytopathogenic Xanthomonas campestris - Shu-Fen Weng; Pan-Ming Tai; Cheng-Hwa Yang; Cheng-Der Wu; Wan-Ju Tsai; Juey-Wen Lin; Yi-Hsiung Tseng (Archives of Microbiology, 2001)

Study on methods of land use dynamic monitoring at county level - Lin-yi Li; Fang Huang; Zhao-li Liu; En-pu Wan (Chinese Geographical Science, 2001)